Multi-layer sintered ceramic body

A multi-layered ceramic body with specific thermal expansion coefficients and materials like YAG and zirconia addresses corrosion and mechanical issues in semiconductor plasma processing chambers, enhancing stability and reducing contamination in large-scale applications.

JP7623492B2Active Publication Date: 2025-01-28HERAEUS CONAMIC NORTH AMERICA LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023535974
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-20
Filing Date
2021-12-17
Publication Date
2025-01-28
Estimated Expiration
2041-12-17

AI Technical Summary

Technical Problem

Existing semiconductor plasma processing chamber components face issues with corrosion, erosion, and particle contamination due to high dielectric loss, overheating, and mechanical damage, particularly in large-scale applications, leading to process fluctuations and yield losses.

Method used

A multi-layered ceramic body composed of layers with specific thermal expansion coefficients, high mechanical strength, and corrosion resistance, formed by combining materials like YAG, alumina, and zirconia, which are sintered to create a uniform and dense structure suitable for large components.

Benefits of technology

The multi-layered ceramic body provides improved corrosion resistance, mechanical strength, and reduced particle contamination, ensuring stable performance in harsh plasma environments, particularly for large-scale semiconductor processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623492000016
    Figure 0007623492000016
  • Figure 0007623492000017
    Figure 0007623492000017
  • Figure 0007623492000018
    Figure 0007623492000018
Patent Text Reader

Abstract

A multi-layer sintered ceramic body is disclosed, comprising at least one first layer comprising polycrystalline YAG, the at least one first layer comprising polycrystalline YAG having a maximum size of 0.1-5 μm, at least one second layer comprising alumina and zirconia, the zirconia comprising at least one of stabilized zirconia and partially stabilized zirconia, and at least one third layer comprising at least one selected from the group consisting of YAG, alumina and zirconia, wherein an absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first, second and third layer is 0-0.75×10 / ° C. as measured according to ASTM E228-17, and wherein the at least one first, second and third layers form a single multi-layer sintered ceramic body. Methods of fabrication are also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to corrosion-resistant multi-layer sintered ceramics and components formed therefrom, methods for making same, and their use in semiconductor plasma processing chambers. [Background technology]

[0002] Semiconductor processing requires the use of halogen-based gases in combination with high electric and magnetic fields to create a plasma environment. This plasma environment is created in a vacuum chamber to etch or deposit material on a semiconductor substrate. These vacuum chambers include components such as a disk or window, a liner, an injector, a ring, and a cylinder. During semiconductor plasma processing, the substrate is typically supported in the vacuum chamber by a substrate holder, as disclosed, for example, in U.S. Pat. Nos. 5,262,029 and 5,838,529. Process gases for creating the plasma processing environment can be supplied to the chamber by various gas delivery systems. Some processes involve the use of radio frequency (RF) fields, where the process gas is introduced into the processing chamber while the RF field is applied to the process gas to generate a plasma of the process gas. The ceramic materials used to form these components can have a molecular weight of up to 1×10, particularly for RF applications. -3It is required that the dielectric loss tangent be of the order of 0.1 to 0.5 μm. Dielectric losses higher than this will cause overheating and hot spots in the components during use, leading to process variations and yield loss. The use of components made from high purity starting powders and manufacturing processes that preserve the initial purity provide sintered ceramics that meet these low loss requirements. The harsh plasma processing environment requires the use of highly corrosion and erosion resistant materials for the chamber components. These components are formed from materials that provide resistance to corrosion and erosion in the plasma environment and are described, for example, in U.S. Pat. Nos. 5,798,016, 5,911,852, 6,123,791, and 6,352,611. Additionally, plasma processing chambers are designed to include components such as disks, rings, and cylinders that confine the plasma over the wafer being processed. However, these components used in the plasma processing chamber are continually attacked by the plasma, which ultimately results in corrosion, erosion, or accumulation of contaminants and polymer build-up. Plasma etching and deposition conditions cause erosion and roughening of the surfaces of chamber parts exposed to the plasma. This erosion contributes to wafer-level contamination through the release of particles from the component surfaces into the chamber, resulting in yield loss of semiconductor devices.

[0003] To address this, chamber components often have a surface layer that is resistant to corrosion and erosion when exposed to process gases. The surface layer may be formed on a base or substrate that may have superior mechanical, electrical or other favorable properties. For example, it is known that corrosion-resistant films or coatings of yttrium oxide or yttrium aluminum garnet (YAG) are deposited on bases or substrates formed of different materials that are cheaper and stronger than most corrosion-resistant materials. Such films or coatings have been made by several methods. Vapor deposition methods have been used to deposit corrosion-resistant films on substrates, but vapor deposition is limited to relatively thin layers due to internal film stresses, and small pores are often present in the thin films. These internal film stresses cause poor interlayer adhesion, typically resulting in delamination at the interface between the corrosion-resistant film and the substrate, making these layers prone to cracking and peeling, thereby leading to undesirable particle contamination. Corrosion-resistant coatings or films made by aerosol or plasma spray techniques typically exhibit high levels of porosity, from 3% to about 50%, and correspondingly low density. Furthermore, these films produced by aerosol or spray methods exhibit poor interfacial adhesion between the substrate material and the corrosion resistant layer, resulting in spalling and delamination and subsequent chamber contamination. Figure 1 shows a schematic of delamination and cracking of a film deposited on a ceramic substrate.

[0004] Commercially available methods for film deposition onto sintered substrates limit film thickness to less than about 0.45 mm. Such films often have pores due to non-uniformities in the base substrate, and the presence of pores and limited film thickness makes the film surface layer susceptible to cracking and exposes the base substrate to corrosive process gases and particle generation during processing.

[0005] Other approaches to forming corrosion-resistant, high-strength sintered bodies and / or components include stacking precast films, applying pressure to the films to form a stack, and then co-sintering the stack. These methods typically use pressureless sintering, and the flatness of the sintered body depends on closely matching the sintering rates of the respective films. As shown diagrammatically in FIG. 2, if the sintering rate of the top film (film A) is greater than that of the bottom film (film B), the sintered ceramic stack will have a concave curvature, whereas if the sintering rate of the bottom film (film B) is greater than that of the top film (film A), the sintered ceramic stack will have a convex curvature (both configured with the top film, film A, facing upwards). Variations in sintering rates create residual stresses in the sintered stack, making it prone to fracture, microcracks and subsequent particle ejection, especially at larger dimensions. Thus, the materials selected for co-sintering are limited to those with the same or very similar sintering profiles of time, temperature and duration, as known to those skilled in the art. Furthermore, these sintered laminates often exhibit poor interfacial adhesion between layers which, combined with low density, results in peeling and spalling of the top layers making them prone to breakage, delamination and cracking.

[0006] Drilling holes and machining features to form components from sintered ceramic bodies can result in small, visually undetectable microcracks below (subsurface) and on the surface of these brittle non-metallic materials. This surface and subsurface damage can lead to particle contamination due to erosion or spalling and / or fracture of the brittle materials. Machinability of components formed from brittle materials becomes increasingly difficult, especially at larger component sizes, to prevent particle emission into the plasma processing chamber and / or to prevent fractures and cracks.

[0007] As a result, there is a need in the art for multi-layer sintered ceramic bodies having a combination of properties of plasma resistance, high adhesion between layers, high mechanical strength, and improved machinability for use in plasma processing chambers. In particular, there is a need for corrosion-resistant, high-strength sintered ceramic bodies of large dimensions (greater than 100 mm, e.g., 100 mm to 625 mm) to enable large-scale semiconductor device manufacturing. Summary of the Invention

[0008] To meet these and other needs, and with that objective in mind, the present disclosure provides embodiments of multi-layer sintered ceramic bodies and methods for preparing large multi-layer sintered ceramic bodies having improved mechanical, electrical and thermal properties and handling capabilities.

[0009] Described herein are sintered ceramic bodies, also referred to herein as multilayer sintered ceramic bodies or corrosion resistant bodies, and methods of manufacture. These sintered ceramic bodies provide high corrosion resistance to chlorine and fluorine based process gases, low dielectric loss, high thermal conductivity, and improved machinability, and are thus desirable for use as components in semiconductor processing chambers that utilize halogen-based process gases. The ceramic bodies are particularly suitable for use as large chamber components, measuring 100 mm or greater.

[0010] Embodiment 1. A composite material comprising at least one first layer comprising polycrystalline YAG, the at least one first layer comprising polycrystalline YAG having a maximum size of 0.1-5 μm, at least one second layer comprising alumina and zirconia, the zirconia comprising at least one of stabilized zirconia and partially stabilized zirconia, and at least one third layer comprising at least one selected from the group consisting of YAG, alumina and zirconia, the at least one second layer being disposed between the at least one first layer and the at least one third layer, and the absolute value of the difference in coefficient of thermal expansion (CTE) between any of the at least one first, second and third layers is 0-0.75×10 as measured according to ASTM E228-17. -6 / °C, and at least one of the first, second and third layers form a single sintered ceramic body.

[0011] Embodiment 2. The multilayer sintered ceramic body of embodiment 1, wherein the absolute value of the difference in thermal expansion coefficient between any of the layers is 0 to 0.7×10-6 / °C.

[0012] Embodiment 3. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between any of at least one of the first, second and third layers is maintained over a temperature range of 200 to 1400°C.

[0013] Embodiment 4. The multi-layer sintered ceramic body of any one of the preceding embodiments, wherein the at least one first layer has a density of 4.47 to 4.56 g / cc as measured according to ASTM B962-17.

[0014] Embodiment 5. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein the at least one first layer has a Sa of 0.0005 to 2 μm, as measured according to ISO standard 25178-2-2012, or a Sz of 0.3 to 5 μm, as measured according to ISO standard 25178-2-2012.

[0015] Embodiment 6. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein the at least one second layer comprises zirconia in an amount of 10-30 volume percent, based on the volume of the at least one second layer.

[0016] Embodiment 7. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein the at least one second layer comprises partially stabilized zirconia.

[0017] Embodiment 8. The multilayer sintered ceramic body of any one of the preceding embodiments, having a maximum dimension of 100 to about 625 mm.

[0018] Embodiment 9. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein the at least one second layer comprises about 16 volume percent zirconia, based on the volume of the at least one second layer.

[0019] Embodiment 10. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein the at least one first layer comprises polycrystalline YAG in an amount of 98-99.9 volume percent, as measured using XRD, SEM and image processing methods, and the remainder comprising at least one crystalline phase selected from the group consisting of aluminum oxide, yttrium oxide, YAM and YAP, and combinations thereof.

[0020] Embodiment 11. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein at least one first layer comprising polycrystalline YAG comprises pores, the pores having a maximum size of 0.1 to 1 μm as measured using SEM.

[0021] Embodiment 12. At least one first layer comprising polycrystalline YAG has a thickness of about 2 to about 800 μm as measured using SEM. 2 / mm 2 3. The multilayer sintered ceramic body of any one of the preceding embodiments, having a cumulative pore distribution of:

[0022] Embodiment 13. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein at least one first layer comprising polycrystalline YAG has a porosity by surface area percentage of 0.0005-2% as measured using SEM.

[0023] Embodiment 14. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein the at least one first layer comprising polycrystalline YAG has a total impurity content of less than 5-50 ppm by weight of the at least one first layer, as measured using ICPMS techniques.

[0024] Embodiment 15. The multi-layer sintered ceramic body of any one of the preceding embodiments, wherein the at least one second layer has a density of 4.19 to 4.46 g / cc as measured according to ASTM B962-17.

[0025] Embodiment 16. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein the at least one second layer comprises zirconia in an amount of 16 volume percent and has a density of about 4.32 g / cc as measured according to ASTM B962-17.

[0026] Embodiment 17. At least one second layer has a thermal conductivity of 6.98×10 over a temperature range of 200° C. to 1400° C., as measured according to ASTM E228-17. -6 / ℃~9.26×10 -6 21. The multilayer sintered ceramic body of embodiment 20, having a coefficient of thermal expansion (CTE) of 1 / °C.

[0027] Embodiment 18. At least one second layer has a thermal conductivity of 7×10 at a frequency of 1 MHz at ambient temperature, as measured according to ASTM D150. -4 22. The multilayer sintered ceramic body according to any one of embodiments 19 to 21, having a dielectric loss of:

[0028] Embodiment 19. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein the at least one second layer has a total impurity content of 5 to 200 ppm by weight of the at least one second layer, as measured using an ICPMS method.

[0029] Embodiment 20. The multilayer sintered ceramic body of any one of the preceding embodiments, wherein at least one first layer has a thickness d1, at least one second layer has a thickness d2, and at least one third layer has a thickness d3, and the thickness d2 of the at least one second layer is 60% to 85% of the combined thickness of the at least one first, second and third layer.

[0030] Embodiment 21. A method for making a multi-layer sintered ceramic body, the method comprising the steps of: a) combining powders including yttria and alumina to make a first powder mixture; b) combining an alumina powder with at least one of a partially stabilized zirconia powder and a stabilized zirconia powder to make a second powder mixture; c) combining an alumina powder with an yttria powder and at least one of an unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia powder to make at least one third powder mixture; and d) combining the first, second, and third powder mixtures with at least one of a partially stabilized zirconia powder and a stabilized zirconia powder to make at least one third powder mixture. sintering at least one of the second and third powder mixtures by applying heat to raise the temperature of at least one of the powder mixtures to a sintering temperature and maintaining the sintering temperature to form at least one first, second, and third sintered powder mixture; and e) separately disposing the first, second, and third powder mixtures within an internal volume defined by a toolset of a sintering apparatus to form at least one layer of the first powder mixture, at least one layer of the second powder mixture, and at least one layer of the third powder mixture and creating a vacuum condition within the volume. a) discharging a powder from the die, the toolset comprising a die including a sidewall including an inner wall and an outer wall, and an upper punch and a lower punch operatively coupled to the die, the inner wall having a diameter defining an interior volume capable of receiving the powder, each of the upper punch and the lower punch having an outer wall defining a diameter smaller than the diameter of the inner wall of the die, thereby defining a gap between each of the upper punch and the lower punch and the inner wall of the die when at least one of the upper punch and the lower punch moves within the interior volume of the die, the gap being between 10 μm and 100 μm in width; and f) sintering. applying pressure to the layers of the first, second and third powder mixtures while heating to a temperature to sinter to form a multi-layer sintered ceramic body, wherein at least one layer of the first powder mixture forms at least one first layer, at least one layer of the second powder mixture forms at least one second layer, and at least one layer of the third powder mixture forms at least one third layer; and g) reducing the temperature of the multi-layer sintered ceramic body, wherein at least one first layer comprises polycrystalline YAG and at least one second layer comprises alumina;the alumina comprises at least one of stabilized zirconia and partially stabilized zirconia, the at least one third layer comprises yttria, alumina, and at least one of unstabilized zirconia, stabilized zirconia, and partially stabilized zirconia, and the at least one second layer is disposed between the at least one first layer and the at least one third layer;

[0031] Embodiment 22. The method of embodiment 21, wherein the first, second and third powder mixtures have a combined total impurity content of 200 ppm or less as measured using ICPMS.

[0032] Embodiment 23. The method of embodiment 21 or 22, wherein the second powder mixture comprises partially stabilized zirconia or stabilized zirconia in an amount of 15% by weight or more and 34% by weight or less, based on the weight of the second powder mixture.

[0033] Embodiment 24. The method of any one of embodiments 21-23, wherein the first, second and third powder mixtures are crystalline as determined by X-ray diffraction methods.

[0034] Embodiment 25. The method of any one of embodiments 21-24, wherein the second powder mixture comprises partially stabilized zirconia.

[0035] Embodiment 26. The method of any one of embodiments 21-25, wherein the second powder mixture comprises partially yttria stabilized zirconia.

[0036] Embodiment 27. The method of any one of embodiments 21-26, wherein the second powder mixture comprises 3 mole percent partially yttria stabilized zirconia.

[0037] Embodiment 28. The method of any one of embodiments 21 to 27, wherein the pressure applied to the first, second and third layers of at least one of the first, second and third powder mixtures is from 5 MPa to 100 MPa.

[0038] Embodiment 29. The method according to any one of embodiments 21 to 28, wherein the temperature of the calcination step is 600°C to 1200°C.

[0039] Embodiment 30. The method of any one of embodiments 21 to 29, wherein the sintering temperature is 1000 to 1700°C.

[0040] Embodiment 31. The method of any one of embodiments 21 to 30, further comprising the steps of: h) optionally annealing the multi-layer sintered ceramic body by applying heat to raise the temperature of the multi-layer sintered ceramic body to an annealing temperature at which annealing is performed; and i) reducing the temperature of the annealed multi-layer sintered ceramic body.

[0041] Embodiment 32.j) The method of any one of embodiments 21-31, further comprising machining the multi-layer sintered ceramic body to produce multi-layer sintered ceramic components in the shape of windows, lids, dielectric windows, RF windows, rings, focus rings, process rings, deposition rings, nozzles, injectors, gas injectors, showerheads, gas distribution plates, diffusers, ion suppressor elements, chucks, electrostatic wafer chucks (ESCs), and pucks.

[0042] Embodiment 33. A multi-layer sintered ceramic body made by the process of any one of embodiments 21-32.

[0043] Embodiment 34. The multilayer sintered ceramic body of embodiment 33 having a maximum dimension of 100 to about 625 mm.

[0044] The embodiments of the present invention may be used alone or in combination with each other. [Brief description of the drawings]

[0045] The present disclosure is best understood from the following detailed description when read in conjunction with the accompanying drawings. It is emphasized that, according to common practice, the various features of the drawings are not to scale. Conversely, dimensions of the various features have been arbitrarily expanded or reduced for clarity. The drawings include the following figures: [Figure 1] FIG. 1 shows a laminate structure known in the art. [Diagram 2] FIG. 2 shows a laminate structure known in the art. [Diagram 3] FIG. 3 shows the CTE difference between at least one phase of YAG, spinel, and yttria / zirconia (denoted as Y / Zr) compared to alumina over a temperature range. [Figure 4] FIG. 4 shows a single multi-layer structure having mismatched CTE values ​​between at least one first layer and a second layer. [Diagram 5] FIG. 5 shows an SEM micrograph of an interface of a laminate structure known in the art. [Figure 6] FIG. 6 illustrates an exemplary schematic diagram of a multi-layer sintered ceramic body according to embodiments disclosed herein. [Figure 7] FIG. 7 illustrates the variation in CTE of at least one second layer 102 comprising zirconia according to embodiments disclosed herein. [Figure 8] FIG. 8 shows an X-ray diffraction result of at least one second layer 102 according to an embodiment disclosed herein. [Figure 9-01] 9 a), b), and c) show the variation in CTE of a multi-layer sintered ceramic body including at least one first layer including YAG and at least one second layer composition according to embodiments disclosed herein. [Figure 9-02] 9 a), b), and c) show the variation in CTE of a multi-layer sintered ceramic body including at least one first layer including YAG and at least one second layer composition according to embodiments disclosed herein. [Fig.9-03]9 a), b), and c) show the variation in CTE of a multi-layer sintered ceramic body including at least one first layer including YAG and at least one second layer composition according to embodiments disclosed herein. [Figure 10] FIG. 10 shows the binary phase diagram of yttrium oxide / aluminum oxide. [Figure 11] FIG. 11(a) shows an SEM micrograph of the surface of at least one first layer 100 comprising polycrystalline YAG using backscattering detection (BSD) and FIG. 11(b) shows an SEM image from the same area of ​​the surface after thresholding to reveal the porosity and alumina phase according to embodiments disclosed herein. [Figure 12] FIG. 12(a) shows a topographical SEM micrograph (using a topographical imaging method) of the surface of at least one first layer comprising YAG of FIG. 11, and FIG. 12(b) shows a topographical SEM image from the same area of ​​the surface after thresholding to reveal the porosity and alumina phase according to an embodiment disclosed herein. [Figure 13] FIG. 13 shows an X-ray diffraction result of at least one first layer 100 including YAG according to an embodiment disclosed herein. [Figure 14] FIG. 14 shows the pore area versus pore size of a single multi-layer sintered ceramic body including at least one first layer 100 comprising YAG and at least one second layer 102 comprising approximately 16 volume percent zirconia. [Figure 15] FIG. 15 illustrates cumulative pore area versus pore size for a multilayer sintered ceramic body including at least one first layer 100 comprising YAG and at least one second layer 102 comprising approximately 16 volume percent zirconia and balance alumina according to embodiments disclosed herein. [Figure 16] FIG. 16(a) shows an SEM micrograph of the surface of at least one layer of a multilayer sintered ceramic body containing YAG, and FIG. 16(b) shows the total percentage of surface area containing porosity within the seven images of FIGS. 14 and 15. [Figure 17-01]17a), b), and c) show the variation in CTE of a multi-layer sintered ceramic body including at least one first layer 100 including spinel and at least one second layer 102 according to embodiments disclosed herein. [Figure 17-02] 17a), b), and c) show the variation in CTE of a multi-layer sintered ceramic body including at least one first layer 100 including spinel and at least one second layer 102 according to embodiments disclosed herein. [Figure 17-03] 17a), b), and c) show the variation in CTE of a multi-layer sintered ceramic body including at least one first layer 100 including spinel and at least one second layer 102 according to embodiments disclosed herein. [Figure 18] FIG. 18 shows an X-ray diffraction result of a fired powder mixture of a composition for forming at least one first layer 100 comprising magnesium aluminate spinel. [Figure 19] FIG. 19 shows an SEM micrograph of the surface of at least one first layer 100 comprising magnesium aluminate spinel according to embodiments disclosed herein. [Figure 20-01] 20a), b) and c) show the variation in CTE of a single multi-layer sintered ceramic body including at least one first layer 100 including at least one crystalline phase of a ceramic material including yttria and zirconia, and at least one second layer 102 according to embodiments disclosed herein. [Figure 20-02] 20a), b) and c) show the variation in CTE of a single multi-layer sintered ceramic body including at least one first layer 100 including at least one crystalline phase of a ceramic material including yttria and zirconia, and at least one second layer 102 according to embodiments disclosed herein. [Figure 20-03]20a), b) and c) show the variation in CTE of a single multi-layer sintered ceramic body including at least one first layer 100 including at least one crystalline phase of a ceramic material including yttria and zirconia, and at least one second layer 102 according to embodiments disclosed herein. [Figure 21] FIG. 21 a) shows the nonlinear interface 104 of a single multilayer sintered ceramic body, and FIG. 21 b) shows a 500x SEM image of the surface of at least one first layer 100 comprising about 20 mol % zirconia and about 80 mol % yttria according to an embodiment disclosed herein. [Figure 22] FIG. 22a) shows a schematic diagram of a multi-layer sintered ceramic body 98, and FIG. 22b) shows an enlarged schematic diagram showing the nonlinear interface 104 and the second interface 105 according to embodiments disclosed herein. [Diagram 23] FIG. 23 a) illustrates the tortuosity (T) and FIG. 23 b) illustrates the average interface line (IL) that characterizes the nonlinear interface 104 according to embodiments disclosed herein. [Figure 24] FIG. 24 a) shows a SEM micrograph of the nonlinear interface 104 of a multilayer sintered ceramic body at 5000x, and FIG. 24 b) shows a measurement of the tortuosity (T) of the nonlinear interface 104 according to an embodiment disclosed herein. [Diagram 25] FIG. 25a) shows the number of grains per interface length in μm of the nonlinear interface 104, and FIG. 25b) shows the tortuosity (T) of the nonlinear interface 104 according to embodiments disclosed herein. [Figure 26] Figures 26a) and b) show SEM micrographs at 1000x (and 5000x) of at least one third layer of a multilayer sintered ceramic body disclosed herein. [Figure 27] 27a), 27b), and 27c show exemplary cross-sectional views of an embodiment of a multilayer sintered ceramic body disclosed herein before and after a machining process to produce a multilayer sintered part including a through hole 112 according to an embodiment disclosed herein. [Figure 28]FIG. 28 shows a schematic diagram of a pressure assisted sintering apparatus toolset according to an embodiment disclosed herein. [Figure 29] FIG. 29 shows a cross-sectional view of an SPS sintering apparatus with the toolset positioned in a simple arrangement within a vacuum chamber (not shown) used to sinter the ceramic material. [Figure 30A] FIG. 30A shows the embodiment of FIG. 29 showing one foil layer. [Figure 30B] FIG. 30B shows an alternative embodiment to FIG. 29 showing two foil layers. [Figure 30C] FIG. 30C shows another alternative embodiment of FIG. 29 showing three foil layers. [Figure 31A] 31A and 31B are top views of the SPS sintering apparatus of FIG. [Figure 31B] 31A and 31B are top views of the SPS sintering apparatus of FIG. [Diagram 32] FIG. 32 is a graph showing the radial dispersion of the average coefficient of thermal expansion (CTE) of graphite materials A and B at 1200° C. [Diagram 33] 33-34 show semiconductor plasma processing systems 9500 and 9600. [Diagram 34] 33-34 show semiconductor plasma processing systems 9500 and 9600. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0046] The following detailed description assumes that the present disclosure is carried out in an apparatus such as an etching chamber or a deposition chamber required as part of the fabrication of devices on a semiconductor wafer substrate. However, the present disclosure is not so limited. The workpieces may be of various shapes, sizes, and materials. In addition to semiconductor wafer processing, other workpieces that may utilize the present invention include various articles such as inorganic circuit boards with fine feature sizes, magnetic recording media, magnetic recording sensors, mirrors, optical elements, micromechanical devices, and the like.

[0047] Corrosion-resistant ceramics, particularly multi-layer sintered ceramic bodies having two or more layers for use as components in semiconductor reactor chambers, and their fabrication are described herein. Semiconductor etch and deposition reactors require reactor components with surfaces that are highly resistant to corrosion and erosion by halogen-containing plasmas required for processing. The surfaces preferably minimize particle emission from the component surface into the chamber. In addition, the chamber components must have sufficient mechanical strength for handling and use, especially in large (diameter >100 mm) component sizes. The sintered ceramic bodies may be machined into sintered components, and therefore must be capable of being handled and machined in large sizes while providing corrosion resistance, low particle generation, and high mechanical strength. The sintered ceramic bodies disclosed herein are of the formula Y3Al5O4 having a garnet structure (with a composition including yttrium and alumina in a ratio of about 3.5). 12 The at least one first layer has at least one crystalline phase of a ceramic material including YAG (yttrium aluminum oxide or yttrium aluminate), spinel (magnesium aluminate spinel, MgAl2O4), yttria and zirconia, the zirconia being present in the yttria in an amount of 10 mole % or more ZrO2 and 25 mole % or less ZrO2. These materials have excellent corrosion and erosion resistance. The use of these materials results in semiconductor plasma processing chamber components having surfaces that provide improved plasma resistance over other materials when subjected to halogen-based plasma etching and deposition conditions.

[0048] In one embodiment, disclosed herein is an optical fiber comprising at least one first layer comprising a polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconia, wherein the zirconia is present in an amount of 10 mol % to 25 mol %, inclusive; at least one second layer comprising alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia; and at least one third layer comprising at least one selected from the group consisting of YAG, alumina, and zirconia, the at least one second layer being disposed between the at least one first layer and the at least one third layer, wherein an absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first, second, and third layer is between 0 and 0.75×10 as measured according to ASTM E228-17. -6 / °C, and at least one of the first, second and third layers form a single sintered ceramic body.

[0049] As the semiconductor manufacturing industry moves to larger semiconductor substrate diameters, larger sized chamber components are required, on the order of 100 to about 625 mm in diameter. Thus, the multi-layer sintered ceramic bodies disclosed herein must have sufficient strength during use and handling to avoid breakage. The multi-layer sintered ceramic bodies disclosed herein further include at least one second layer comprising zirconia and alumina, which second layer has high mechanical strength and also favorable electrical and material properties as disclosed below.

[0050] 6, disclosed is a multi-layer sintered ceramic body 98 having at least one outermost first layer 100 with a plasma-facing surface 106 that provides resistance to the corrosive and erosive effects of halogen-based plasmas and ion bombardment, controlled porosity distribution with small pore size, high purity, high density, and low surface roughness. Preferably, the at least one first layer 100 has a CTE that is between 0 and 0.75×10 and the CTE of the at least one second layer 102 and the at least one third layer 103, as measured in accordance with ASTM E228-17. -6 The multilayer sintered ceramic body 98 of the present disclosure includes a nonlinear interface 104 (see FIG. 21 ) defined by the at least one first layer 100 and the at least one second layer 102, whereby the nonlinear interface 104 can provide improved adhesion between the layers.

[0051] Embodiments of the present disclosure further relate to certain multi-layer sintered ceramic bodies including at least one second layer 102 having a compositional range including zirconia and alumina. Over the compositional range of yttria and zirconia, the at least one second layer 102 exhibits high mechanical strength, improved stiffness (Young's modulus), high thermal conductivity, low dielectric loss, high dielectric constant, and a coefficient of thermal expansion (CTE) that matches the CTE of the at least one first layer 100 and at least one third layer 103 within the disclosed ranges.

[0052] The at least one third layer 103 includes at least one of a multiphase of YAG, alumina, and zirconia, thereby providing the at least one third layer with improved machinability. The at least one third layer 103 can provide a sintering profile similar to that of the at least one first layer 100, thereby providing greater uniformity throughout the layer during sintering. The CTE of the at least one third layer 103 is CTE matched to the at least one first and second layers within the ranges disclosed herein.

[0053] At least one first, second and third layer having a CTE value within the range disclosed herein provides for the preparation of a single multi-layer sintered body and large size (100 mm to about 625 mm) chamber components manufactured therefrom. Additionally, methods for the preparation of such corrosion resistant multi-layer sintered ceramics and their use in plasma processing chambers are disclosed.

[0054] Definitions - As used herein, the following terms are defined as follows: "alumina" is understood to be aluminum oxide, which includes Al2O3, "zirconia" is understood to be zirconium oxide, which includes ZrO2, and "yttria" is understood to be yttrium oxide, which includes Y2O3.

[0055] As used herein, the terms "semiconductor wafer," "wafer," "substrate," and "wafer substrate" are used interchangeably. Wafers or substrates used in the semiconductor device industry typically have a diameter of 200 mm, or 300 mm, or 450 mm.

[0056] As used herein, the term "sintered ceramic body" is synonymous with "multilayer sintered ceramic body," "multilayer corrosion resistant ceramic," "corrosion resistant body," "sintered ceramic," "multilayer monolithic body," and similar terms, and refers to a single, integral, sintered ceramic article formed from co-compressing two or more powder mixtures by applying pressure and heat to create a single, dense, multilayer sintered ceramic body. The single multilayer sintered ceramic body can be machined into a single multilayer sintered ceramic component useful as a chamber component in plasma processing applications. Thus, the multilayer sintered ceramic bodies disclosed herein are not formed by laminating preformed layers together, i.e., the multilayer sintered ceramic bodies disclosed herein are not laminates.

[0057] As used herein, the term "co-compacting" or "co-compaction" refers to a process in which at least two bulk powder materials are placed in a die and subjected to pressure to form a powder compact that does not contain binders, dispersants, and other similar organic materials required to form green or compact bodies or tapes as is common in the art.

[0058] "Unitary" means a single piece or part that is complete by itself without additional pieces, i.e., the part is one monolithic piece formed with another part as one unit.

[0059] As used herein, the term "substantially" is a descriptive term indicating approximation, meaning to a great extent or to the majority, but not all, of what is specified, and is intended to avoid precise numerical boundaries for specified parameters.

[0060] As used herein, the term "sintered ceramic component" or "multilayer sintered ceramic component" refers to a sintered ceramic body, a multilayer sintered ceramic body, or a corrosion-resistant ceramic after machining steps that form the ceramic into the specific shape of a desired component for use in the semiconductor processing chambers disclosed herein.

[0061] As used herein, the term "powder mixture" means two or more starting powders mixed together prior to the sintering process, thereby formed into at least one layer of a multi-layer sintered ceramic body after the sintering step.

[0062] The term "annealing" as applied to ceramic heat treatment is understood herein to mean a heat treatment that may be performed in air on the disclosed multilayer sintered ceramic bodies to relieve stress and / or normalize stoichiometry.

[0063] As used herein, the term "tool set" can include at least one die and at least two punches. When fully assembled, the toolset defines a volume for placing a powder mixture as disclosed.

[0064] The term "phase" as used herein is understood to mean a distinct crystalline region, portion or layer of a sintered ceramic body having a particular crystallographic structure.

[0065] As used herein, a "solid solution" is defined as a mixture of different elements that share the same crystal lattice structure. The mixture in the lattice may be substitutional, where atoms from one starting crystal replace atoms from the other starting crystal, or interstitial, where atoms occupy positions normally vacant in the lattice.

[0066] As used herein, the term "nano powder" refers to a powder having a molecular weight of 2000 or more. 2 This is intended to include powders having a specific surface area of ​​100 / g or more.

[0067] The term "phase" as used herein is understood to mean a distinct crystalline region, portion or layer of a sintered ceramic body having a particular crystallographic structure.

[0068] As used herein, the term "layer" is understood to mean a thickness of material, typically one of several. The material can be, for example, a ceramic powder, a powder mixture, a fired powder mixture, or a sintered region or portion.

[0069] As used herein, "ambient temperature" refers to a temperature range of about 22°C to 25°C.

[0070] As used herein, the term "purity" refers to the absence of various contaminants in a) the starting materials from which the powder mixture may be formed, b) the processed powder mixture (or fired powder mixture), and c) the multi-layer sintered ceramic body or component disclosed herein. Higher purities (approaching 100%) refer to materials that are essentially free of or contain very small amounts of contaminants or impurities and that substantially contain the material composition present in the starting powders disclosed.

[0071] As used herein, the term "impurities" refers to compounds / contaminants present in the powders or sintered ceramics other than the intended compounds themselves (magnesia, alumina, yttria and zirconia starting powders, stabilizing compounds if applicable, powder mixtures and ceramics formed therefrom). Impurities may be present in the starting powders, powder mixtures, processed powder mixtures, and sintered ceramic bodies. ICPMS techniques were used to determine the impurity content of the powders, powder mixtures, and first and second layers of the sintered bodies disclosed herein.

[0072] As used herein, the term "dopant" refers to a substance that is added to a bulk material to impart desired properties to the ceramic material (e.g., to alter electrical properties). Typically, dopants, when used, are present in low concentrations, i.e., >0.002% to <0.05% by weight.

[0073] Impurities differ from dopants in that dopants, as defined herein, are compounds that are intentionally added to the starting powder or powder mixture to obtain particular electrical, mechanical, optical, or other properties, such as, for example, modifying grain size in the multi-layer sintered ceramic body. The term "dopant" as used herein does not include Hf and Y contained in the zirconium oxide starting material to the extent that they may remain in the multi-layer sintered ceramic body.

[0074] The term "sintering aid" as used herein refers to compounds such as silica (SiO2), lithia (Li2O), lithium fluoride (LiF), magnesia (MgO), and / or calcia (CaO) that increase densification and thereby reduce porosity during the sintering process. Hf and Y to the extent present in the starting powder and remaining in the sintered ceramic do not include sintering aids, impurities, or dopants as defined herein.

[0075] As used herein, the terms "substantially" and "about" are used in connection with numbers or features disclosed herein and therefore allow for a variance of plus or minus 10%.

[0076] As used herein, the term "coefficient of thermal expansion (CTE)" is measured over a temperature range of 25-200°C to 25-1400°C, preferably 25-1200°C, more preferably 25-1000°C, more preferably 25-800°C, more preferably 25-600°C, more preferably 25-400°C, more preferably 25-200°C, in accordance with ASTM E228-17. CTE describes how the size of an object changes with a change in temperature. Specifically, it measures the rate of change in size per degree of temperature change at a constant pressure. To determine the coefficient at a temperature, the volume of the material is measured at a reference temperature and the volume of the material is measured at the temperature at which one wishes to determine the CTE. The fractional change is then determined based on the difference in volume and temperature.

[0077] All CTE values ​​in this disclosure were made in accordance with ASTM E228-17. In particular, the reference temperature used was ambient temperature, specifically 25°C. Thus, when a CTE at a given temperature (i.e., 200°C) is disclosed, the CTE is determined by comparing the volume (or linear expansion of an isotropic material) at that temperature to the volume (or linear expansion of an isotropic material) at ambient temperature, specifically 25°C. In any case of conflict regarding CTE, ASTM E228-17 is always the governing disclosure. In the disclosed examples, CTE was measured using a vertical dilatometer, specifically the L75 model available from Linseis Messgeraete GmbH (Selb, Germany).

[0078] During semiconductor device processing, corrosion-resistant chamber components are used in etch and / or deposition chambers and are exposed to harsh corrosive and erosive environments that cause particle release into the chamber, resulting in yield loss due to wafer-level contamination. The multilayer sintered ceramic bodies disclosed herein and associated components manufactured therefrom provide improved plasma resistance, thermal conductivity and enhanced mechanical strength for use in semiconductor processing chambers, due to certain material properties and characteristics described below.

[0079] According to one embodiment, disclosed herein is a multi-layer sintered ceramic body comprising at least one first layer comprising at least one polycrystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria, wherein zirconia is present in an amount of 10 mol % to 25 mol %, at least one second layer comprising alumina, wherein the alumina comprises at least one of stabilized zirconia (SZ) and partially stabilized zirconia (PSZ), and at least a third layer comprising a multi-phase comprising at least YAG, alumina, and zirconia, wherein an absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first layer and the at least one second layer is 0 to 0.75×10 / ° C. (measured according to ASTM E228-17), and wherein the at least one first layer and the at least one second and third layers form a single multi-layer sintered ceramic body.

[0080] In one embodiment, each layer has a thermal conductivity of 0-0.75×10-6 / °C, preferably 0-0.7×10-6 / °C, preferably 0-0.6×10-6 / °C, preferably 0-0.5×10-6 / °C, preferably 0-0.45×10-6 / °C, preferably 0.-0.4×10-6 / °C, preferably 0-0.35×10-6 / °C, between at least one of the first, second and third layers, measured according to ASTM E228-17 over a temperature range of 25-1700°C, or over a temperature range of 200-1400°C, The absolute value of the difference in CTE of preferably 0 to 0.3×10-6 / °C, preferably 0 to 0.25×10-6 / °C, preferably 0 to 0.2×10-6 / °C, preferably 0 to 0.15×10-6 / °C, preferably 0 to 0.1×10-6 / °C, preferably 0 to 0.08×10-6 / °C, preferably 0 to 0.04×10-6 / °C, preferably 0 to 0.02×10-6 / °C is shown. These ranges of absolute values ​​of the difference in CTE between the at least one first, second, and third layer correspond to a percentage difference in CTE between any of the at least one first, second, and third layer being about 10% or less, preferably 9% or less, preferably 8% or less, preferably 6% or less, preferably 4% or less, preferably 3% or less, preferably 2.5% or less, preferably 2% or less, preferably 1.5% or less, preferably 1% or less, preferably 0.5% or less, preferably 0.25% or less of the at least one first, second, and third layer (as measured relative to the at least one first layer 100). When the CTE between the at least one first layer 100, the at least one second layer 102, and the at least one third layer 103 varies within these ranges, and more specifically when the CTE of the at least one first, second, and third layer varies within these ranges over a temperature range of ambient to about 1700°C (or about 200°C to about 1400°C as shown in the figure) as measured according to ASTM E228-17, the pressure assisted methods disclosed herein can be used to form a single multi-layered sintered ceramic body of particularly large (>100 mm to about 625 mm) dimensions having high strength and high adhesion between the layers.Due to the isotropic properties of the ceramic material comprising at least one of the first, second and third layers disclosed herein, the coefficient of thermal expansion (CTE) as used herein can interchangeably refer to either linear or volumetric CTE. The difference in CTE between the at least one of the first, second and third layers is preferably minimized to reduce interfacial stress between the layers. If the difference in CTE between the at least one of the first, second and third layers is greater than that disclosed herein, fracture and / or cracking of the multilayer sintered ceramic body may occur.

[0081] 6, a schematic diagram of a multi-layer sintered ceramic body 98 as disclosed herein is shown, where 100 represents at least one first layer having a thickness d1, 102 represents at least one second layer 102 having a thickness d2, and 103 represents at least one third layer 103 having a thickness d3. A multi-layer sintered ceramic body 98 (showing at least one first layer 100, where the first layer has a thickness, the second layer 102, where the second layer has a thickness, and the third layer 103, where the third layer has a thickness) produced according to the method disclosed herein preferably has a thickness of the second layer 102 that is 70% to 95%, preferably 70% to 90%, preferably 70% to 85%, preferably 80% to 95%, preferably 85% to 95% of the combined thickness of the three layers 100, 102, and 103.

[0082] The at least one second layer 102 provides mechanical strength and electrical properties of low dielectric loss tangent (less than 7×10 at 1 MHz) and high dielectric constant of about 12. Therefore, in some embodiments, it may be preferable for the thickness d2 to be maximized. To provide high mechanical strength and stiffness combined with machinability for forming sintered ceramic components from the multi-layer sintered body disclosed herein, the thickness d2 of the at least one second layer 102 shown in FIG. 6 is preferably greater than each of the thickness d1 of the at least one first layer 100 and / or the thickness d3 of the at least one third layer 103. The thickness d1 of at least one first layer 100 and / or the thickness d3 of at least one third layer 100 may each be 0.5 to 5 mm, preferably 0.5 to 4 mm, preferably 0.5 to 3 mm, preferably 0.5 to 2 mm, preferably 0.5 to 1 mm, preferably 0.75 to 5 mm, preferably 0.75 to 3 mm, preferably 1 to 5 mm, preferably 1 to 4 mm, preferably 1 to 3 mm. The multilayer sintered ceramic body disclosed herein may have a total thickness (d1+d2+d3) of about 5 to about 50 mm, preferably about 5 to about 40 mm, preferably about 5 to about 35 mm, preferably about 5 to about 33 mm, preferably about 5 to about 30 mm, preferably about 8 to about 25 mm, preferably about 10 to about 20 mm. In certain embodiments, it may be desirable to minimize the thickness d1 of the at least one first layer 100 and / or the thickness (d3) of the at least one third layer 103, and the multi-layer sintered ceramic body can be machined to reduce the thickness d1 and / or d3 of the layers 100 and / or 103 after sintering and / or annealing to modify electrical properties such as dielectric loss, dielectric constant, thermal conductivity or other properties of the multi-layer sintered ceramic body 98 or components formed therefrom.

[0083] The multilayer sintered ceramic body disclosed in the present specification has at least one first layer 100 having a certain thickness, at least one second layer 102 having a certain thickness, and at least one third layer 103 having a certain thickness, and the thickness of the at least one second layer 102 is 70% to 95%, preferably 70% to 90%, preferably 70% to 85%, preferably 80% to 95%, preferably 85% to 95% of the combined thickness of the three layers 100, 102 and 103.

[0084] In a particular embodiment, the thickness d2 of the at least one second layer is 60%-85%, preferably 60%-80%, preferably 60%-75%, preferably 60%-70%, preferably 70%-85%, preferably 75%-85%, preferably 70%-80%, preferably 70%-75% of the combined thickness (d1+d2+d3) of the at least one first, second and third layer. The at least one first layer having a thickness d1 comprises a plasma-facing surface 106 that provides corrosion and erosion resistance to halogen-based plasmas. In an embodiment, the thickness d1 of the at least one first layer is 0.75% to 20%, preferably 0.75% to 15%, preferably 0.75% to 12%, preferably 3% to 20%, preferably 5% to 20%, preferably 3% to 15%, preferably 5% to 12% of the combined thickness (d1+d2+d3) of the at least one first, second and third layer.

[0085] Stresses resulting from layers containing materials with CTE mismatch can affect the mechanical strength and integrity of the multi-layer sintered ceramic body. Thus, if the absolute difference in CTE between the at least one first layer 100, the at least one second layer 102, and the at least one third layer 103 of the sintered ceramic body is too large, the at least one layer of the multi-layer sintered ceramic body may crack and / or break when performing the steps of the method disclosed herein. This difference in CTE is significant over all process temperatures, especially at high temperatures such as those experienced during sintering, annealing, and cooling, and the difference in CTE can result in significant interfacial stress between the layers of the sintered body. As a result, in order to form a multi-layer unitary sintered ceramic body with high mechanical strength, high adhesion strength between the layers, and sufficient handling (no cracks or breakage), the CTE difference between the at least one first layer 100, the at least one second layer 102, and the at least one third layer 103 of the multi-layer sintered ceramic body is preferably within the disclosed ranges and more preferably matches as closely as possible. In a preferred embodiment, at least one of the first, second and third layers can have respective CTEs that are the same or substantially the same in absolute value over a temperature range of ambient temperature (or about 200° C. as disclosed in the figures) to about 1700° C. (or at least 1400° C. as shown in the figures) in accordance with the disclosed methods. As used herein, the term "CTE match" refers to a CTE that is the same or substantially the same in absolute value over a temperature range of ambient temperature (or about 200° C. as disclosed in the figures) to about 1700° C. (or at least 1400° C. as shown in the figures) in accordance with the disclosed methods. -6The term "CTE" refers to a combination of at least one first layer 100, at least one second layer 102, and at least one third layer 103 that differ in CTE by (°C). According to one embodiment, the at least one first layer 100 may comprise a polycrystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconia, where the zirconia is present in an amount of 10 mol % or more ZrO2 and 25 mol % or less ZrO2, whereby the at least one first layer 100 is CTE matched with the at least one second layer 102 (comprising alumina and at least one of stabilized zirconia and partially stabilized zirconia) and the at least one third layer 103 (comprising a combination of at least one first and second layer) to form a single multi-layer sintered ceramic body. On a percentage basis, the combination of at least one first layer 100, at least one second layer 102 and at least one third layer 103 may have CTE values ​​(over the temperature ranges disclosed herein) that match each other by a percentage of about 10% or less, preferably 9% or less, preferably 8% or less, preferably 6% or less, preferably 4% or less, preferably 3% or less, preferably 2.5% or less, preferably 2% or less, preferably 1.5% or less, preferably 1% or less, preferably 0.5% or less, preferably 0.25% or less of the at least one first, second and third layer (as measured relative to the at least one first layer 100).

[0086] The composition of the at least one second layer 102 can be selected to produce specific CTE characteristics based on the volume percent of zirconia in alumina as shown in Figure 2, and Figure 7 shows an exemplary CTE result for at least one second layer 102 disclosed herein, where the second layer includes zirconia in an amount of 10-30 volume percent, with the balance including Al2O3. The amount of zirconia, and the resulting CTE value of the at least one second layer 102, is preferably CTE matched to the at least one first and third layer over a temperature range corresponding to the temperature range of the present method, from ambient (or 200°C according to the figure) to 1700°C (or 1400°C according to the figure), to produce a single multi-layer sintered body as disclosed herein.

[0087] According to one embodiment, the at least one second layer 102 comprises alumina and zirconia, the zirconia comprising at least one of stabilized zirconia and partially stabilized zirconia in an amount of 5-30 vol%, preferably 5-25 vol%, preferably 5-20 vol%, preferably 5-16 vol%, preferably 10-30 vol%, preferably 16-30 vol%, preferably 10-25 vol%, preferably 15-20 vol%, based on the volume of the at least one second layer (the balance comprising Al2O3). These volume percentages of the at least one second layer 102 correspond to weight percentages of the second powder mixture comprising about 7% to about 40%, preferably about 7% to about 35%, preferably about 7% to about 28%, preferably about 7% to about 23%, preferably about 15% to about 40%, preferably about 23% to about 40%, preferably about 15% to about 34%, preferably about 21% to about 28%, preferably about 23% zirconia (and the remainder alumina). Over this composition and temperature range, the coefficient of thermal expansion (CTE) of the at least one second layer 102 can vary from at least one second layer 102 including 5 volume percent zirconia having a CTE of about 6.8×10 / ° C. measured at 200° C. to at least one second layer 102 including about 30 volume percent zirconia having a CTE of about 9.75×10 / ° C. measured at 1400° C. The volumetric amount of at least one of stabilized zirconia or partially stabilized zirconia in the at least one second layer 102 provides the ability to tailor the CTE such that it is the same or substantially the same as the CTE of the at least one first layer 100 and the at least one third layer 103, and within the disclosed CTE matching range.

[0088] 7, experimental data was taken to measure the coefficient of thermal expansion (CTE) of the at least one second layer 102 using dilatometry as performed in accordance with ASTM E228-17 for 10, 16, and 20 vol.% ZrO2 (and balance alumina) compositions. An exemplary at least one second layer 102 comprising about 16 vol.% zirconia had a coefficient of thermal expansion (CTE) of 6.98×10 over a temperature range of about 200° C. to about 1400° C. as measured in accordance with ASTM E228-17. -6 / ℃~9.26×10 -6The at least one second layer 102 was measured to have a coefficient of thermal expansion (CTE) of 100 / °C. The at least one second layer 102 includes at least two distinct crystalline phases of zirconia and alumina (referred to herein as a multi-oxide or particulate composite or zirconia toughened alumina (ZTA)) as shown from the X-ray diffraction results in FIG. 8. Thus, using the volumetric mixture rule known to those skilled in the art, CTE values ​​for 5, 25, and 30 volume percent zirconia were calculated (as shown in FIG. 7). The CTE value versus temperature of the at least one second layer (not shown) including 5 volume percent zirconia is typically between the range of pure alumina and the range of the at least one second layer including 10 volume percent zirconia. The ability to modify the CTE properties of the at least one second layer 102 provides a CTE match between the at least one second layer 102, the at least one third layer 103, and the at least one first layer 100, particularly over a temperature range consistent with the temperature range and sintering temperature of the methods disclosed herein. Selection of the composition of the at least one second layer 102 and the at least one third layer 103 allows for, without limitation, the use of various materials for the at least one first layer 100 that have the same or substantially the same CTE as the second layer 102 and the third layer 103 within the ranges disclosed herein. In some embodiments, over the disclosed temperature range of ambient to about 1700° C. (or from 200° C. to 1400° C. as shown in the figures), the CTE of the at least one second layer 102 may be greater than or less than the CTE of the at least one first layer, thereby having a zero CTE difference over the temperature range.In other embodiments, the CTE of the at least one second layer 102 may be either greater than or less than the CTE of the at least one first layer 100 over the disclosed temperature range (ambient to about 1700° C., or 200° C. to 1400° C., as shown in the figures), and thus the absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first layer 100 and the at least one second layer 102 is greater than or less than the ASTM CTE over the temperature range of 25-1700° C., or over the temperature range of 200-1400° C. E228-17, the temperature is 0.003×10-6 / ℃ to 0.75×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.7×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.6×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.5×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.45×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.4×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.35×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.3×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0. 6 / ℃ to 0.25×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.2×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.15×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.1×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.08×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.06×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.04×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.02×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.01×10-6 / ℃.

[0089] In other embodiments, the at least one second layer 102 may have a CTE greater than the CTE of the at least one first layer 100 over a temperature range of about 600° C. to about 1700° C. (or at least 1400° C. as shown in the figures), and a CTE less than the CTE of the at least one first layer 100 over a temperature range of ambient temperature (or at least 200° C. as shown in the figures) to about 600° C. The temperature at which the change in magnitude of the CTE between the at least one first layer and the second layer occurs may occur at any temperature between about 200° C. to about 800° C. Without intending to be bound by any particular theory, it is believed that the lower CTE of the at least one second layer 102 relative to the at least one first layer 100 at lower temperatures (e.g., from 800° C. to ambient temperature) serves to provide compression of the at least one first layer 100, thereby reducing the likelihood of crack propagation, fracture, and spalling that can result in particle generation during use as a component in a semiconductor plasma processing chamber.

[0090] The at least one third layer 103 typically has a CTE within the ranges disclosed for the at least one first and second layers. The CTE of the at least one third layer 103 can be tailored to match the CTE of the at least one first and second layers through variation of the amount of zirconia. Thus, the absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first layer 100, the at least one second layer 102, and the at least one third layer 103 is in the range of 25-1700° C. or 200-1400° C., in some embodiments, in the range of 25-1700° C. or 200-1400° C., as defined by ASTM A125. Measured according to E228-17, the temperature is 0 to 0.75×10-6 / ℃, preferably 0 to 0.7×10-6 / ℃, preferably 0 to 0.6×10-6 / ℃, preferably 0 to 0.5×10-6 / ℃, preferably 0 to 0.45×10-6 / ℃, preferably 0 to 0.4×10-6 / ℃, preferably 0 to 0.35×10-6 / ℃, preferably 0 to 0.3×10-6 / ℃, preferably 0 to 0. It may be 25×10-6 / °C, preferably 0 to 0.2×10-6 / °C, preferably 0 to 0.15×10-6 / °C, preferably 0 to 0.1×10-6 / °C, preferably 0 to 0.08×10-6 / °C, preferably 0 to 0.06×10-6 / °C, preferably 0 to 0.04×10-6 / °C, preferably 0 to 0.02×10-6 / °C, preferably 0 to 0.01×10-6 / °C.

[0091] In other embodiments, the absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first layer 100, the at least one second layer 102, and the at least one third layer 103 is greater than or equal to ASTM A 102 CTE over a temperature range of 25-1700° C. or over a temperature range of 200-1400° C. E228-17, the temperature is 0.003×10-6 / ℃ to 0.75×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.7×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.6×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.5×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.45×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.4×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.35×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.3×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0. 6 / ℃ to 0.25×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.2×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.15×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.1×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.08×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.06×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.04×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.02×10-6 / ℃, preferably 0.003×10-6 / ℃ to 0.01×10-6 / ℃.

[0092] In contrast, a material combination made by the same method but that did not meet the CTE matching requirements as disclosed herein (hence the absolute value of the CTE difference is mismatched) is shown in FIG. 4 (per “Comparative Example” in the Examples section) which shows a sintered ceramic body formed from a YAG first layer and an aluminum oxide substrate (second layer). As shown in FIG. 3, alumina is shown to have a lower CTE than both YAG, spinel and 80% yttria / 20% zirconia. The sintered ceramic body fractured in the alumina substrate near the interface between the layers during annealing. The fracture occurs at the weakest area in the sintered body, and fracture occurring in the bulk alumina may exhibit an interface strength that is approximately the same as or greater than that of the bulk alumina substrate. The location of the fracture (in the alumina) illustrates the very high interface strength (which may exceed the interface strength of the bulk first and second layers) that is achieved by using the materials and methods disclosed herein. The difference in CTE between YAG and alumina was sufficient to cause fracture in the bulk sintered body while maintaining integrity at the interface between the two layers. Film deposition and / or film lamination methods for forming laminates typically exhibit much lower interfacial strength and accordingly fracture and / or crack at the interface between the film layers (interlayer fracture or delamination as shown in the schematic diagram of FIG. 1). As shown in FIG. 3, YAG is closest to alumina in CTE match, and therefore the use of a ceramic material for at least one first layer 100 (such as a spinel as a first layer in combination with an aluminum oxide substrate layer) that has a thermal expansion coefficient that varies by a larger amount relative to alumina is expected to similarly produce a multi-layer sintered body susceptible to fracture after sintering when using alumina as the substrate material. Thus, the coefficient of thermal expansion (CTE) of alumina over the temperature range disclosed herein differs from the CTE of many corrosion-resistant materials by an amount sufficient to prevent the formation of a single multi-layer sintered body using alumina as the substrate material.

[0093] In addition to the CTE match, the multi-layer sintered ceramic body preferably has a high thermal conductivity for use as a component in a semiconductor plasma processing chamber. The zirconia-toughened alumina (ZTA) composition selected for use as the at least one second layer 102 (and at least a portion of the at least one third layer 103) significantly impacts the properties of the single multi-layer sintered body. High thermal conductivity of the at least one second layer 102 is an important material property, especially when used as a dielectric or RF window component, to effectively distribute heat and thereby avoid localized overheating within the at least one second layer during use. This localized overheating may result in cracking or fracture of the single multi-layer sintered body. Zirconia has been reported in the literature to have a lower thermal conductivity than that of alumina, and therefore the amount of zirconia affects the thermal conductivity of the at least one second layer 102. Pure aluminum oxide is known to have a high thermal conductivity, but cannot be used in combination with the materials for use as the at least one first layer 100 disclosed herein due to the CTE mismatch. For thermal conductivity reasons, there may be no practical lower limit on the minimum amount of zirconia in the at least one second layer 102, but in order to provide a CTE that matches the at least one first layer 100 and a high thermal conductivity (approximately that of alumina), at least one second layer 102 comprising at least one of stabilized zirconia and partially stabilized zirconia in an amount of about 5% to 30% by volume (with the remainder comprising about 70% to 95% by volume of the second crystalline phase of alumina) is preferred.

[0094] For example, to provide the at least one second layer 102 with sufficient thermal conductivity for use in high frequency applications (such as RF or dielectric window or lid components), at least one second layer 102 having about 30% by volume or less, and in some embodiments preferably 25% by volume or less, zirconia may be preferred. A second layer 102 having more than 30% by volume zirconia may not provide sufficient thermal conductivity for use as a component in a semiconductor plasma processing chamber where high thermal conductivity is a requirement. A composition of the at least one second layer 102 having more than 30% by volume zirconia may result in high thermal gradients in the at least one second layer 102, which may lead to fractures and / or cracks.

[0095] FIG. 7 shows the thermal expansion coefficient results from 200 to 1400° C. for at least one second layer 102 disclosed herein having zirconia present in an amount of 10 to 30 volume percent. The CTE value versus temperature for at least one second layer (not shown) containing 5 volume percent zirconia is typically between the range of pure alumina and at least one second layer containing 10 volume percent zirconia. The at least one second layer 102 contains at least two distinct crystalline phases of zirconia and alumina, as shown in FIG. 8, and therefore, the CTE values ​​for 5 volume percent, 25 volume percent, and 30 volume percent zirconia were calculated using the volumetric mixture rule known to those skilled in the art. The CTE is shown to increase with increasing volume amounts of zirconia, as shown in FIG. 7. Depending on the volume of zirconia in the at least one second layer 102, ZTA (zirconia toughened alumina), the CTE of the at least one second layer can be greater than, substantially equal, comparable, or less than (varying by amounts within the ranges disclosed herein) the CTE of the at least one first layer 100 (including YAG, spinel, or yttria and zirconia) comprising the single multi-layer sintered ceramic body. Thus, as used herein, CTE difference typically refers to the absolute value of the CTE difference, unless otherwise specified.

[0096] A high toughness value of the at least one second layer 102 is preferred to improve handling and prevent fractures and / or cracks in the multilayer sintered ceramic body. To increase the toughness of the at least one second layer 102 comprising alumina and zirconia, strengthening and / or stabilization of the at least one second layer is preferred. Without intending to be bound by a particular theory, the strengthening and stabilization mechanisms disclosed herein may serve the purpose of stabilizing the tetragonal phase of zirconia, thereby limiting the transformation (at lower temperatures) to the monoclinic phase, which involves a large volume change of about 4.5%, and favoring the phase stability of the tetragonal form of zirconia. The stabilization of tetragonal zirconia may be achieved by any stabilization method known to those skilled in the art, without limitation.

[0097] The combination of zirconia and alumina in the at least one second layer can provide a transformation strengthening effect through the dispersion of tetragonal zirconia particles, at least a portion of which transform to monoclinic upon crack propagation. The volume expansion from tetragonal to monoclinic zirconia provides a transformation or dispersion strengthening effect in the at least one second layer 102, as known to those skilled in the art. In an embodiment, the at least one second layer 102 may include a particle composite of zirconia and alumina crystalline phases (also referred to herein as composite oxide or ZTA, standing for dispersion or transformation strengthened ceramic) in the disclosed volumetric amounts. This strengthening method can be influenced by the powder particle size, shape and location of the tetragonal and monoclinic dispersed zirconia phases in the alumina matrix.

[0098] Further methods of stabilization utilize stabilizing compounds including yttria, calcia, lanthanum oxide (La2O3), ceria (CeO2), samaria (Sm2O3) and magnesia, and combinations thereof, in various molar amounts, to stabilize zirconia, preferably in the tetragonal or cubic crystalline phase (the monoclinic crystalline phase of zirconia is stable at room temperature; thus, the tetragonal and cubic phases are considered metastable phases when present at room temperature). The relative amounts and types of these stabilizing compounds can produce at least one second layer 102 comprising zirconia that includes at least one of fully stabilized (SZ) and partially stabilized (PSZ). Typically, the stabilizing compounds may be selected for their valence and atomic radius relative to zirconium (Zr). These stabilizing compounds having an atomic radius larger than zirconium are advantageous for stabilizing the tetragonal and / or cubic phases. In some embodiments, yttria may be selected as the tetragonal phase stabilizing compound having a lower valence (+3) and a larger atomic radius (180 picometers, pm) than zirconia (which has an atomic radius of 160 pm). Typically, stabilizing compounds having a lower valence state (coordination number) than zirconia are preferred. Without intending to be bound by a particular theory, the use of these stabilizing compounds having a lower valence state than that of zirconia (+4) may result in the introduction of oxygen vacancies, which may increase dielectric losses at high frequencies (e.g., RF or microwave frequencies). Thus, in some embodiments, a stabilizing compound such as cerium oxide (CeO2), which has the same valence (+4) and a larger atomic radius (185 pm) than zirconia, may stabilize the tetragonal and / or cubic phases without introducing oxygen vacancies. In some embodiments, combinations of at least two of the stabilizing compounds are preferred and may be combined in any combination in the amounts disclosed herein to stabilize the zirconia comprising at least one second layer 102 and / or at least one third layer 103. The stabilizing compounds may be added to at least one of the second and / or third powder mixtures according to the disclosed methods.Table 1 lists stabilizing compounds and their molar amounts and weight percents to produce stabilized zirconia (SZ) and / or partially stabilized zirconia (PSZ). Stabilization of zirconia using the disclosed stabilizing compounds can result in a change in the CTE of the at least one third layer, and the amount of zirconia can be adjusted accordingly.

[0099] [Table 1]

[0100] In an embodiment, the at least one second layer 102 may comprise particles or grains of zirconia (PSZ, SZ and combinations thereof) dispersed in a host matrix of alumina, the at least one second layer comprising a particle composite (composite oxide) having two distinct crystalline phases of alumina and zirconia. Preferably, the at least one second layer 102 does not form a solid solution. The formation of a solid solution may reduce thermal conductivity, therefore, the at least one second layer 102 comprises distinct crystalline phases of zirconia and alumina. FIG. 8 shows the distinct crystalline phases of zirconia and alumina from the X-ray diffraction results, confirming that the at least one second layer 102 comprises distinct crystalline phases without the formation of a solid solution. X-ray diffraction for all measurements disclosed herein was performed using a PANanlytical Aeris model XRD, which allows for crystalline phase identification to about + / - 5%. The small amount of yttria present in the x-ray diffraction pattern of FIG. 8 may result from partial zirconia stabilization (partially yttria stabilized zirconia, PYSZ) according to at least one second layer embodiment.

[0101] Furthermore, the use of compounds known to form glass as sintering aids in the at least one second layer 102 (such as magnesia, silica, and calcia) can result in a low thermal conductivity glass phase present between the crystal grains, thus adversely affecting thermal conductivity. As a result, in some embodiments, the at least one second layer 102 preferably comprises magnesia and / or calcia in the range of about 2-100 ppm, preferably about 2-75 ppm, preferably about 2-50 ppm, preferably about 2-25 ppm, preferably about 2-20 ppm, preferably about 2-10 ppm, preferably about 8 ppm, preferably about 2 ppm or less, based on the weight of the at least one second layer, as measured using ICPMS techniques. In further embodiments, the at least one second layer 102 may include silica in an amount of about 14 ppm to 100 ppm, preferably about 14 ppm to about 75 ppm, more preferably about 14 ppm to about 50 ppm, preferably about 14 ppm to about 30 ppm, preferably about 14 ppm or less (measured using ICPMS method) based on the mass of the at least one second layer 102. A second layer 102 including sintering aids within the disclosed ranges can provide a multi-layer sintered ceramic body that is free or substantially free of glass phase, providing high thermal conductivity of the multi-layer sintered ceramic body. Disclosed herein are multi-layer sintered ceramic bodies including at least one second layer 102 that is free or substantially free of the dopants and / or sintering aids disclosed herein.

[0102] Thermal conductivity was calculated (as the product of diffusivity, density, and known heat capacity) from thermal diffusivity measurements performed (at ambient temperature and 200° C.) according to ASTM E 1461-13 on at least one second layer 102 comprising about 16% by volume of partially yttria stabilized zirconia (3 mole %) and balance alumina. In an embodiment, at least one second layer 102 comprising about 16% by volume of partially yttria stabilized zirconia was calculated to have a thermal conductivity of about 25 W / mK at ambient temperature and about 14 W / mK at 200° C. Thus, at least one second layer 102 preferably comprises about 5 to about 30% by volume of zirconia, preferably about 5 to about 20% by volume of at least one second layer 102, preferably about 10 to about 20% by volume of zirconia, preferably about 15 to about 20% by volume of at least one second layer 102. At least one second layer 102 having a composition within the ranges disclosed herein provides sufficient thermal conductivity for use as, for example, a dielectric window, an RF window, a lid, and other components requiring high thermal conductivity in the plasma processing chambers disclosed herein.

[0103] Low dielectric loss is preferred, especially for RF applications, to prevent local hot spots and overheating during use. Dielectric loss can be affected by material properties such as, for example, grain size and the presence of impurities, sintering aids and / or dopants. The presence of impurities and / or sintering aids and / or dopants, especially silica, in the at least one second layer 102 can result in higher dielectric loss. The use of high purity / low impurity content starting powders and methods that maintain purity results in at least one second layer 102 of high overall purity and correspondingly low overall impurity content. Thus, in an embodiment, the at least one second layer 102 disclosed may have a total impurity content of 5-200 ppm, preferably 5-150 ppm, preferably less than 100 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably 10-100 ppm, preferably 10-80 ppm, preferably 10-60 ppm, preferably 10-40 ppm, preferably 20-80 ppm, preferably 30-60 ppm, based on the mass of the at least one second layer, as measured using ICPMS techniques. In an embodiment, the at least one second layer 102 is formed from a powder mixture including silica in an amount of about 14-100 ppm, preferably about 14-75 ppm, preferably about 14-50 ppm, preferably about 14-25 ppm, preferably about 14 ppm, based on the total mass of the calcined powder mixture. In an embodiment, the at least one second layer 102 may contain magnesia (MgO) in an amount of about 2-100 ppm, preferably about 2-75 ppm, preferably about 2-50 ppm, preferably about 2-25 ppm, preferably about 2-20 ppm, preferably about 2-10 ppm, preferably about 8 ppm or less, preferably about 2 ppm, based on the weight of the at least one second layer 102, as measured using an ICPMS method.

[0104] For use in plasma processing chambers, especially those operating in the RF range, a multi-layer sintered ceramic body 98 with low dielectric loss (tangent δ) is preferred. The at least one second layer 102 may, in embodiments, comprise the maximum thickness (and therefore maximum volume) of the multi-layer sintered ceramic body 98, and thus the associated properties of the at least one second layer may significantly affect the electrical properties of the sintered body and other properties such as thermal conductivity. The dielectric loss of the sintered body may be influenced by the purity of the at least one second layer 102, especially the silica content. Thus, the at least one second layer 102 may comprise magnesia and / or calcia in an amount of about 2-100 ppm, preferably about 2-75 ppm, preferably about 2-50 ppm, preferably about 2-25 ppm, preferably about 2-20 ppm, preferably about 2-10 ppm, preferably about 2 ppm, respectively, relative to the mass of the complex oxide second layer 102. In further embodiments, at least one second layer 102 disclosed herein may be formed from at least one powder mixture having a Si content of about 14 ppm or more, preferably 14-100 ppm, preferably 14-75 ppm, preferably 14-50 ppm, preferably 14-25 ppm, preferably 14-20 ppm, preferably about 14 ppm, based on the total mass of the second layer 102. In embodiments, the second layer may have a total impurity content of 5-200 ppm, preferably 5-150 ppm, preferably less than 100 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably 10-100 ppm, preferably 10-80 ppm, preferably 10-60 ppm, preferably 10-40 ppm, preferably 20-80 ppm, preferably 30-60 ppm, based on the total mass of the second layer.

[0105] The total impurity content of the at least one second layer 102 comprising calcia, silica, and magnesia in the amounts disclosed herein is approximately 7×10 at ambient temperature and 1 MHz frequency, as measured according to ASTM D150, as set forth in Table 7 for at least one second layer 102 comprising approximately 16 vol.% partially yttria stabilized (3 mol.% yttria) zirconia and balance alumina.-4 In an embodiment, the at least one second layer 102 is free (0 ppm or below detection limits) or substantially free (2-5 ppm) of the dopants and / or sintering aids disclosed herein. The at least one second layer 102 disclosed herein provides a multilayer sintered ceramic body or components made therefrom with low dielectric loss suitable for use as a chamber component, particularly as a window or lid component for use in high frequency RF plasma processing chambers.

[0106] Plasma processing chambers for the manufacture of semiconductor devices are designed to accommodate substrates having ever increasing diameters, requiring chamber components of correspondingly larger dimensions. These chamber components manufactured from the multilayer sintered ceramic bodies disclosed herein may have maximum dimensions of, for example, 100 to about 625 mm, preferably 100 to 622 mm, preferably 200 to about 625 mm, preferably 300 to about 625 mm, preferably 400 to about 625 mm, preferably 500 to about 625 mm, preferably 300 to 622 mm, preferably 400 to 622 mm, preferably 500 to 622 mm.

[0107] Many materials that provide resistance to corrosion and erosion are known to be difficult to sinter, resulting in low density and correspondingly low sintered strength that can break or crack. This makes it difficult to manufacture large single monolithic solid body components from these corrosion-resistant materials. To enable the manufacture of large chamber components, a high-strength material (that has a CTE match with the corrosion-resistant material disclosed herein) including at least one second layer 102 is needed. The at least one second layer 102 provides mechanical strength and stiffness to the single multi-layer corrosion-resistant sintered body (and components manufactured therefrom) disclosed herein. At least one second layer 102 may be sintered to a very high density, and in embodiments, to a sufficiently high density body, which provides the mechanical strength and rigidity required for the production of multi-layer sintered bodies of large dimensions, for example, having a maximum dimension of 100 to about 625 mm, preferably 100 to 622 mm, preferably 200 to about 625 mm, preferably 300 to about 625 mm, preferably 400 to about 625 mm, preferably 500 to about 625 mm, preferably 300 to 622 mm, preferably 400 to 622 mm, preferably 500 to 622 mm. Density measurements were performed according to ASTM B962-17 for sintered bodies having an amount of zirconia of 10 to 16 volume % (with alumina as the balance), and the density was calculated for at least one second layer having 5, 20, 25 and 30% zirconia using the volumetric rule of mixtures. 99% of the theoretical density was assumed in the calculated densities. Table 2 lists the densities of the at least one second layer comprising crystalline phases of zirconia and alumina disclosed herein.

[0108] [Table 2]

[0109] Zirconia is reported to have a theoretical density of 6.09 g / cc, and alumina is reported to have a theoretical density of 3.98 g / cc. The theoretical density of the at least one second layer 102 was calculated (using these density values ​​and the volume fractions of the respective crystalline phases of zirconia and alumina) according to volumetric mixture rules known to those skilled in the art. Very high densities (99-100% of theoretical density) have been measured for embodiments of the at least one second layer 102 as disclosed in Table 2. At least one second layer 102 including an amount of zirconia (and balance alumina) of about 16 volume % as disclosed herein was measured to have a density of about 4.32 g / cc, measured according to ASTM B962-17. These high densities provide sufficient mechanical strength and stiffness (Young's modulus) for the formation of a single multi-layered sintered body of large dimensions, with a maximum dimension of about 625 mm or less.

[0110] At least one second layer 102 comprising zirconia in an amount of about 16% by volume (and balance alumina) as disclosed herein was tested in a four-point bend test according to ASTM Standard C 1161-3 "Standard Test Method for Flexural Strength of Advanced Ceramics at Ambient Temperature" to determine flexural strength. The four-point bend test is preferred over the three-point bend test because it exposes a larger volume of the sample to a uniform maximum stress and therefore results in a strength more representative of the material being tested. The three-point bend test exposes a relatively small volume of the sample to the maximum stress and therefore the reported three-point bend test strength values ​​are often higher. Thus, comparisons between three-point and four-point bend tests pose challenges due to significant variations in their measurement setups and methods. Using ASTM Standard C 1161-3, very high strength values ​​were achieved in the four-point bend configuration for at least one second layer 102 comprising 16% by volume zirconia. Table 3 lists the flexural strength (modulus of rupture, MOR) and other material properties for at least one layer 102 that includes about 16% partially stabilized ZrO2 and the balance alumina.

[0111] During use in semiconductor reactors under vacuum conditions, corrosion-resistant multi-layer components made from the multi-layer sintered ceramic bodies disclosed herein may be subjected to bending stresses over component dimensions of over 500 mm. High strength and increased stiffness / Young's modulus properties may be necessary for the application of materials for use in components disclosed herein in large-scale etching and / or deposition chambers. The bending strength of 98% dense aluminum oxide is reported to be about 375 MPa, and the stiffness (elastic modulus / Young's modulus) is reported to be about 350 GPa (Coorstek Advanced Alumina data sheet, available online). The at least one second layer 102 disclosed herein can provide mechanical strength and stiffness / Young's modulus that is approximately equal to or exceeds that of alumina, while providing the required CTE to match the at least one first layer 100 and the at least one third layer 103. The use of at least one second layer 102 as disclosed herein can significantly increase the bending strength and stiffness of a single multi-layer component fabricated from the multi-layer sintered ceramic body, enabling the creation of large (>100 to about 625 mm or larger dimensions) components that have both the high strength, stiffness, and resistance to halogen-based corrosion and erosion required for use as components in semiconductor plasma processing chambers.

[0112] The at least one first layer 100 provides a chemically inert plasma-facing surface 106 that is resistant to the corrosive effects of halogen process gases and the erosive effects of plasma ion bombardment (often inert gases such as argon can be used, along with other process gases known in the art), while the at least one second layer 102 provides the mechanical strength to the multi-layer corrosion-resistant sintered body disclosed herein. The at least one second layer 102 may be sintered to a very high density, and in embodiments, may be sintered to a sufficiently dense body that provides the mechanical strength necessary to fabricate a multi-layer sintered body of large dimensions, for example, diameters of 100 to about 625 mm, preferably 200 to about 625 mm, preferably 250 to about 625 mm, preferably 300 to about 625 mm, more preferably 350 to about 625 mm, more preferably 400 to about 625 mm, more preferably 450 to about 625 mm, more preferably 500 to about 625 mm. Table 3 lists the properties of the at least one second layer 102, which includes 16 volume percent partially stabilized zirconia and the balance alumina.

[0113] [Table 3]

[0114] 6, a multi-layer sintered ceramic body 98 is disclosed that includes at least one third layer 103. The at least one third layer 103 includes a polycrystalline phase that includes at least one of YAG, alumina, and zirconia. The zirconia may include at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia.

[0115] In an embodiment, the at least one third layer 103 comprises an area amount of YAG of more than 50% to 90%, preferably more than 50% to 80%, preferably more than 50% to 60%, more preferably about 51% to 55% of the area of ​​the exemplary polished surface of the at least one third layer. The area measurements were completed using backscatter detection images from the SEM imported into ImageJ software, and then the respective phases of YAG and alumina / zirconia were measured in terms of their percentage of surface area over the exemplary image area. The at least one third layer 103 of the multilayer sintered ceramic body may comprise a monolithic body, and thus comprises at least YAG, zirconia and alumina crystalline phases throughout, made according to the process disclosed herein. In other words, the structure measured on the surface represents the structure within the volume of the bulk at least one third layer. Thus, at least one third layer of a multi-layer sintered ceramic body can include the same relative amounts of YAG, zirconia and alumina crystalline phases on the surface and throughout the volume of the body.

[0116] The multiphase structure of the at least one third layer 103 is shown in 1000x SEM micrographs in Figures 26a) and 26b). Figure 26a) shows the microstructure of the at least one third layer 103 including large (largest dimension about 80 μm to about 200 μm) regions of YAG phase (white / light gray regions) and alumina phase (black regions throughout) with zirconia phase dispersed therein (smaller dimension, about 10 μm diameter white regions within the alumina phase). The microstructure of Figure 26a) can be achieved by dry mixing alumina, yttria, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia powders for about 16 hours without the use of grinding / mixing media to form a third powder mixture according to embodiments disclosed herein. The absence of grinding media and dry mixing conditions can contribute to the microstructure as shown in Figure 26a).

[0117] FIG. 26b) shows the microstructure of at least one third layer 103 at 1000× and 5000× (inset) including a finely dispersed (largest dimension about 5 μm to about 20 μm) YAG phase (white / light gray area) and an alumina phase (black area) with a zirconia phase dispersed therein (smaller dimension, about 3 μm diameter white area within the alumina phase). The microstructure of FIG. 26b) can be achieved by forming a 40 wt. % ethanol slurry including alumina, yttria, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia powders to form a third powder mixture according to embodiments disclosed herein. Alumina media was added at about 100% loading based on powder weight, and the powder was tumble milled for 20 hours. As shown in FIG. 26b), the high media loading and extended milling time can contribute to a finely dispersed, highly uniform microstructure.

[0118] The at least one third layer 103 also provides improved machinability and CTE match (within ranges disclosed herein) to the at least one first layer 100 and the at least one second layer 102. According to Fig. 22a), the light grey / white regions (containing YAG) and the alumina / zirconia regions (shown as dark grey or black with white regions within) each form areas measuring about 100 μm or greater, as shown in the SEM showing the multiphase third layer 103. Multiple SEM images were analyzed using ImageJ to determine the area percentage containing each phase of the multiphase layer 103. Using the SEM image of FIG. 26a) (and other images taken at the same magnification of 500x), the multi-layer sintered body comprises at least one third layer 103 including a YAG phase in an amount of about 51 to about 63%, preferably about 51 to about 60%, preferably about 55 to about 60%, and preferably about 60% by area of ​​the alumina-rich phase (including YAG) and the balance including alumina and zirconia, where the zirconia includes at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia. The multi-phase structure having regions including YAG and regions including alumina and zirconia may provide improved fracture toughness and resistance to crack propagation by deflection of the crack along the interface between the regions, thereby increasing the crack length. Additionally, the at least one third layer 103 may reduce the size and frequency of defects that may be formed during machining, thereby maintaining mechanical strength and toughness by absorbing energy generated during machining within the multi-phase at least one third layer 103.

[0119] In an embodiment, the at least one third phase comprises a zirconia toughened alumina (ZTA) phase comprising at least one of unstabilized zirconia, partially stabilized zirconia, or stabilized zirconia in an amount of about 16 volume percent, with the balance being alumina.

[0120] In some embodiments (as shown in FIG. 26 ), at least one third layer 103 comprises a YAG phase (white / light gray areas) in an amount greater than 50% to about 55% by area (and therefore volume), an alumina phase (black / gray), and a zirconia phase (white areas within the black / gray) dispersed within the alumina phase, with the zirconia comprising about 16% by volume of 3 mol % yttria partially stabilized zirconia in an amount less than about 45% to 50%.

[0121] The at least one third layer 103 also provides improved uniformity during sintering by combining yttria, zirconia, and alumina powders to form a third powder mixture having sintering properties similar to those of the at least one first powder mixture. The third powder mixture can provide more uniform heat transfer, which in turn can provide more uniform sintering properties (such as sintering temperature and densification rate of each layer) throughout the powder mixture during sintering according to the methods disclosed herein.

[0122] A second interface 105 between the at least one third layer 103 and the at least one second layer 102 is shown in the schematic diagrams of FIG. 22a) and FIG. 22b). As shown, the second interface 105 (described in more detail herein) can increase the toughness between the at least one third layer 103 and the at least one second layer 102. This improved toughness can be achieved by several factors, such as the multiphase nature of the second interface 105, which can increase the area between the phases to deflect crack propagation, as well as the interlocking effect brought about by the multiphase morphology and nonlinearity of the second interface 105. The intermixing between the powder mixtures forming the at least one third layer 103 and the at least one second layer 102 provides a second interface 105 that, in some embodiments, may not have a clearly delineated boundary between the third layer 103 and the second layer 102. The second interface 105 may, in some embodiments, include a diffuse boundary, and thus properties such as composition, strength, fracture toughness, etc. may have a gradient across the second interface 105. In other embodiments, the second interface 105 provides a distinct non-linear boundary between at least one second layer 102 and at least one third layer 103. The method of combining various powders disclosed herein for at least one third powder mixture may produce at least one second interface 105 as shown in FIG. 22 b). In embodiments, at least one second and third layer may be in contact to form the second interface 105, and thus the second and third layers are adjacent. In other embodiments, circuitry, heating elements, RF coils / antennas, etc. may be disposed between the second and third layers as required by the particular component application, and regardless of these features, the first and second layers may be adjacent or substantially adjacent.

[0123] In a preferred embodiment, compositions are selected for the at least one third layer 103, the at least one first layer 100, and the at least one second layer 102, such that the absolute value of the difference in the coefficients of thermal expansion (CTE) of the at least one first, second, and third layer is greater than or equal to ASTM A 102.25% CTE over a temperature range of 25 to 1700° C., or greater than or equal to ASTM A 102.25% CTE over a temperature range of 200 to 1400° C. When measured in accordance with E228-17, it is 0 to 0.75×10-6 / °C, preferably 0 to 0.7×10-6 / °C, preferably 0 to 0.6×10-6 / °C, preferably 0 to 0.5×10-6 / °C, preferably 0 to 0.45×10-6 / °C, preferably 0 to 0.4×10-6 / °C, preferably 0 to 0.35×10-6 / °C, preferably 0 to 0.3×10-6 / °C, preferably 0 to 0.25×10-6 / °C, preferably 0 to 0.2×10-6 / °C, preferably 0 to 0.15×10-6 / °C, preferably 0 to 0.1×10-6 / °C, preferably 0 to 0.08×10-6 / °C, preferably 0 to 0.04×10-6 / °C, preferably 0 to 0.02×10-6 / °C. A CTE match between at least one of the first layer 100, the second layer 102, and the third layer 103 can be provided over a temperature range from ambient to about 1700° C. in accordance with the temperature range of the methods disclosed herein. Selection of these materials to provide this CTE difference can reduce interfacial stresses on the nonlinear interface 104 and the second interface 105, thereby improving adhesion between the layers of the multilayer sintered ceramic body and components formed therefrom.

[0124] According to one embodiment, disclosed herein is a single multi-layer sintered ceramic body comprising at least one first layer 100 comprising polycrystalline YAG, at least one second layer 102 comprising alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia, and at least one third layer 103 comprising at least one multiphase selected from the group consisting of YAG, alumina, and zirconia, wherein the zirconia comprises at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first, second, and third layer is greater than or equal to ASTM A111115 over a temperature range of 25-1700° C. or over a temperature range of 200-1400° C. E228-17, the temperature is 0 to 0.75×10-6 / °C, preferably 0 to 0.7×10-6 / °C, preferably 0 to 0.6×10-6 / °C, preferably 0 to 0.5×10-6 / °C, preferably 0 to 0.45×10-6 / °C, preferably 0 to 0.4×10-6 / °C, preferably 0 to 0.35×10-6 / °C, preferably 0 to 0.3×10-6 / °C, preferably 0 to 0.3×10-6 / °C, 0.25×10-6 / °C, preferably 0~0.2×10-6 / °C, preferably 0~0.15×10-6 / °C, preferably 0~0.1×10-6 / °C, preferably 0~0.08×10-6 / °C, preferably 0~0.04×10-6 / °C, preferably 0~0.02×10-6 / °C, and at least one of the first, second and third layers forms a single multilayer sintered ceramic body. These ranges of absolute values ​​of the CTE difference between the at least one first layer comprising polycrystalline YAG, the second layer, and the third layer correspond to percentage CTE differences between any of the at least one first, second, and third layers of about 10% or less (as measured relative to the at least one first layer 100 comprising polycrystalline YAG) of about 9% or less, preferably 8% or less, preferably 6% or less, preferably 4% or less, preferably 3% or less, preferably 2.5% or less, preferably 2% or less, preferably 1.5% or less, preferably 1% or less, preferably 0.5% or less, preferably 0.25% or less.

[0125] The at least one first, second and third layers are matched in CTE within the disclosed ranges over a temperature range from ambient temperature (or at least 200°C as shown in the figures) to about 1700°C (or at least 1400°C as shown in the figures) to form a single multi-layer sintered ceramic body. In an embodiment, the at least one first layer 100 may further comprise at least one crystalline phase selected from the group consisting of YAP (yttrium aluminum perovskite), YAM (yttrium aluminum monoclinic), yttria, alumina and combinations thereof, each of the at least one first layer 100 being present in an amount of less than 5% by volume, preferably less than 3% by volume, and more preferably less than 1% by volume, as determined by x-ray diffraction, SEM imaging and ImageJ analysis. Each of the YAG, YAP and YAM crystalline phases is preferably polycrystalline. 9a), b) and c) show CTE measurements over a temperature range of ambient temperature (or at least 200°C as shown) to about 1700°C (or at least 1400°C as shown) of exemplary materials for forming at least one first and second layer of a single multi-layer sintered ceramic body according to an embodiment. All CTE measurements disclosed herein were made according to ASTM E228-17 over a temperature range of 25-1700°C or over a temperature range of 200-1400°C. CTE measurements were made on exemplary bulk materials. FIG. 9a shows a first layer 100 (solid line) of polycrystalline YAG and a second layer (ZTA, dashed line) 102 comprising at least one of stabilized zirconia and partially stabilized zirconia at about 10 volume % and the balance (90 volume %) alumina relative to the total volume of the at least one second layer 102. Figure 9b) shows a first layer 100 of polycrystalline YAG (solid line) and a second layer (ZTA, dashed line) 102 comprising about 20 volume % zirconia and balance (80 volume %) alumina based on the total volume of the at least one second layer. Figure 9c) shows at least one first layer 100 comprising polycrystalline YAG and at least one second layer 102 comprising about 16 volume % zirconia (and balance alumina) based on the total volume of the at least one second layer.

[0126] In one embodiment, the composition range of the at least one second layer 102 (about 5% to about 30% by volume zirconia and balance alumina) may be suitable for CTE matching and percentage ranges to the at least one first layer 100 comprising polycrystalline YAG. Thus, disclosed herein is a multilayer sintered ceramic body 98 comprising at least one second layer 102 comprising alumina and at least one of stabilized zirconia and partially stabilized zirconia in an amount of about 5% to about 30%, preferably about 10% to about 30%, preferably about 5% to about 20%, preferably about 10% to about 20% by volume relative to the volume of the at least one second layer, and at least one first layer 100 comprising polycrystalline YAG. In a preferred embodiment, to more closely match the CTE to the polycrystalline YAG at least one first layer 100, the at least one second layer 102 may include at least one of partially stabilized zirconia and stabilized zirconia and (balance alumina) in an amount of about 13% to about 19%, preferably about 14% to about 18%, preferably about 15% to about 17%, more preferably about 16% by volume, respectively, relative to the volume of the at least one second layer 102. These compositional ranges of the at least one second layer 102 are approximately 0.4×10 % or less of the alumina composition relative to the YAG at least one first layer 100, measured according to ASTM E228-17, over a temperature range of ambient temperature (or at least 200° C. as shown) to about 1700° C. (or at least 1400° C. as shown). -6 / ℃ or less, preferably 0.3×10 -6 / ℃ or less, preferably 0.25×10 -6 / °C or less, preferably about 0.2×10 -6 / ℃ or less, preferably 0.15×10 -6 / ℃ or less, preferably 0.1×10 -6 / °C or less, preferably 0.08×10-6 / °C or less, preferably 0.06×10-6 / °C or less, preferably 0.04×10-6 / °C or less, preferably 0.02×10-6 / °C or less, preferably 0.01×10-6 / °C or less. As a percentage relative to the at least one first layer, the percentage difference in CTE (between any of the at least one first, second and third layers according to one embodiment) may be about 5% or less, preferably 4% or less, preferably 3% or less, preferably 2.5% or less, preferably 2% or less, preferably 1.5% or less, preferably 1% or less, preferably 0.5% or less, preferably 0.25% or less, preferably 0.1% or less of the at least one first, second and third layer (as measured relative to the at least one first layer 100). The zirconia of the at least one second layer may include at least one of partially stabilized zirconia and stabilized according to the methods and stabilizing compounds disclosed herein. A single multi-layered sintered body was formed having a maximum dimension of 100 to about 625 mm and including at least one first layer 100 including polycrystalline YAG and at least one second layer 102 including about 16 volume percent partially stabilized zirconia.

[0127] To provide corrosion and erosion resistance suitable for use as a component in a plasma processing chamber, a polycrystalline single multilayer ceramic body having at least one first layer 100 containing highly phase-pure polycrystalline YAG (>90% by volume) is desirable. However, the formation of substantially phase-pure YAG requires careful compositional and processing control to maintain stoichiometry and thus form a sintered ceramic body containing phase-pure YAG (of composition 37.5+ / -0.1 mole % yttrium oxide and 62.5+ / -0.1 mole % aluminum oxide). In many cases, other crystalline phases may be present, such as alumina, yttria, YAP, YAlO3; yttrium aluminum perovskite phase), and YAM (Y4Al2O9; yttrium aluminum monoclinic phase), and combinations thereof. For reference, FIG. 10 shows a binary phase diagram of yttrium oxide / aluminum oxide. The horizontal axis corresponds to the mixture ratio (mol %) of yttria and alumina, and the vertical axis is temperature (Celsius). The left side of the horizontal axis corresponds to 100% alumina and the right side corresponds to 100% yttria. The phase diagram in Figure 10 shows the regions in which the YAG, YAP, and YAM yttrium aluminum oxide phases form, as well as the molar composition and temperature conditions required to produce these forms.

[0128] Crystal phase and image-based porosity measurements of at least one first layer 100 comprising YAG of a multilayer sintered ceramic body according to one embodiment disclosed herein were performed using a combination of X-ray diffraction (XRD), SEM imaging, and the use of image processing software (ImageJ). XRD was performed using a PANanitical Aeris model XRD capable of crystalline phase identification down to about + / - 5% by volume. FIG. 13 shows X-ray diffraction results confirming the formation of polycrystalline YAG of high phase purity comprising at least one first layer 100. No other phases were identified within the detection limits of XRD. YAG exists as a linear compound according to known phase diagrams, and thus the formation of phase pure YAG poses challenges and requires careful compositional and process control. Such phase pure YAG is disclosed in International Patent Application No. PCT / US20 / 60918, filed November 17, 2020, which is incorporated herein by reference. The at least one first layer 100 of YAG according to an embodiment may, in some embodiments, include excess alumina and / or excess yttria, may be substantially free of dopants, and / or may be substantially free of sintering aids disclosed herein. In other embodiments, the first layer including YAG may include sintering aids and / or dopants in amounts disclosed herein. In embodiments, the first layer 100 of polycrystalline YAG may be substantially free of dopants or free of dopants and may include sintering aids in amounts disclosed herein. XRD of the at least one first layer 100 of the multi-layer sintered ceramic body disclosed herein may measure a phase purity of about 95% by volume or less. Thus, the at least one first layer 100 of a single multi-layer sintered ceramic body includes at least about 95% by volume of YAG phase in the embodiment shown in the xrd results of FIG. 13.

[0129] To determine the phase purity with greater precision, for example, up to about 99.8% by volume, SEM images were taken using a backscattering detection (BSD) method known to those skilled in the art. With BSD, the YAG phase appears gray, the aluminum oxide phase appears black, the yttrium oxide phase appears white, and porosity, if present, also appears black. For the polycrystalline YAG sintered ceramic body according to the embodiments disclosed herein, images were taken at 5000x using the BSD method to identify the YAG, alumina and yttria phases, as well as any porosity present, as shown in FIG. 11 a).

[0130] To distinguish between black regions containing alumina and black regions containing porosity, the BSD image was processed with black and white thresholds using ImageJ processing software to highlight black regions in the BSD image that may contain either porosity or alumina, as shown in the same region in FIG. 11 b). ImageJ is a Java-based, public domain image processing and analysis program developed at the National Institutes of Health (NIH) for image processing of scientific multidimensional images. The BSD detector used for the measurements disclosed herein has the additional capability of measuring topographical features, thereby highlighting any deviations in the surface topography, such as surface porosity. Using the topography mode of the BSD detector, a topography image was taken at 5000x over the surface of the same region of the polycrystalline YAG sintered ceramic body according to Example 7, as shown in FIG. 11 a), and the topography image is shown in FIG. 12 a). The region containing surface porosity was highlighted after thresholding the topography image in ImageJ, as shown in FIG. 12 b). The area containing surface porosity in the topographical image of FIG. 12b) was then subtracted from the area containing alumina and / or porosity in the BSD image of FIG. 12a) to obtain the area % and therefore volume % containing alumina phase in the polycrystalline YAG sintered ceramic body according to the embodiments disclosed herein. At least one first layer 100 of the multilayer sintered ceramic body 98 disclosed herein may have porosity and / or aluminum oxide phase both on the surface and throughout the body. Thus, in an embodiment, the multilayer sintered ceramic body may include a monolithic body containing YAG made by the process disclosed herein, which further includes an aluminum oxide phase and porosity distributed throughout the body. In other words, the structure measured on the surface (e.g., plasma-facing surface 106) represents the structure within the volume of the bulk multilayer sintered ceramic body containing YAG and, in embodiments, further including aluminum oxide. The combination of these analytical tools of multiple SEM imaging modes and ImageJ analysis may provide a determination of phase purity with a confidence of about + / - 0.1% by volume.Using the disclosed method, the polycrystalline YAG sintered ceramic body according to Example 7 was determined to contain about 0.1 to about 0.2 volume percent alumina phase, about 0.1 to about 0.2 volume percent porosity, and about 99.6 to about 99.8 volume percent YAG phase. Taking into account measurement variability, the polycrystalline YAG sintered ceramic body may contain an amount of YAG phase of 99.4 to 99.8 volume percent, porosity of 0.1 to 0.3 volume percent, and aluminum oxide of 0.1 to about 0.3 volume percent.

[0131] Thus, a multilayer sintered ceramic body having at least one first layer 100 each comprising YAG phase in an amount of 90-99.9 volume %, preferably 90-99.8 volume %, preferably 90-99.7 volume %, preferably 90-99.6 volume %, preferably 93-99.8 volume %, preferably 93-99.7 volume %, preferably 93-99.6 volume % of the at least one first layer 100 may be formed using the materials and methods disclosed herein.

[0132] To evaluate the grain size of the at least one first layer 100 comprising polycrystalline YAG, linear intercept grain size measurements were performed according to the Heyn Linear Intercept Procedure described in ASTM Standard E112-2010, "Standard Test Method for Determining Average Grain Size." Grain size measurements (as described in Table 4) were performed on the exemplary plasma-facing surface 106, measuring an average grain size of 1.1-6.3 μm over 25 repeats. Maximum and minimum grain sizes of 2-7.7 μm were also measured on the exemplary plasma-facing surface 106 of the at least one first layer 100 comprising YAG. A single multi-layer sintered ceramic body can have a plasma-facing surface 106 having a maximum grain size of about 8 μm or less, preferably a maximum grain size of 6 μm or less. In an embodiment, the single multi-layer sintered ceramic body may have a plasma-facing surface 106 having an average grain size of 0.4 to 6.5 μm, preferably 0.4 to 5 μm, preferably 0.4 to 3 μm, preferably 0.8 to 6.5 μm, preferably 0.8 to 5 μm, preferably 0.8 to 3 μm, preferably 1 to 7 μm, preferably 1 to 6.5 μm.

[0133] [Table 4]

[0134] To meet the corrosion and erosion resistance requirements for use as a component in a semiconductor processing chamber, a multi-layer sintered ceramic body including at least one first layer 100 with low porosity across the plasma-facing surface 106 and / or within the layer 100 is preferred. Porosity can act as an initiation site for corrosion and erosion, and therefore it is preferred that there is minimal or no porosity, pores or voids within the at least one first layer 100 of the multi-layer sintered body and / or on the plasma-facing surface 106 of the first layer 100. The at least one first layer disclosed herein may have very small pores both on the surface and throughout. Preferably, the at least one first layer 100 made according to the process disclosed herein, including at least one crystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconia, is thus a monolithic layer with pores uniformly distributed throughout. In other words, the pores or gaps or porosity measured on the plasma-facing surface 106 may represent the pores or gaps or porosity within the bulk of the at least one first layer 100 .

[0135] The level of porosity was measured across the sample surface by using SEM images obtained from a Phenom XL scanning electron microscope at 5000x magnification. Images were imported into ImageJ software for analysis. ImageJ, developed at the National Institutes of Health (NIH), is a Java-based, public domain image processing and analysis program for image processing of scientific multidimensional images.

[0136] Using the ImageJ software method disclosed herein, the pore size and total area including porosity were measured across seven SEM images. 2 Images were taken at 5000x, each with a total area of ​​approximately 53.7 μm×53.7 μm, corresponding to a single image measurement area of ​​10 μm×100 μm.

[0137] FIG. 14 shows the porosity results measured on an exemplary plasma-facing surface 106 of at least one first layer 100 comprising YAG, with total pore area (μm 2 ) where the horizontal axis represents the pore size in microns. The measurements were taken over seven images taken at 5000x magnification, with each image measuring approximately 2885 μm 2 The total area including porosity in any one of the seven images ranged from about 0.015 to about 0.3 μm 2 , preferably about 0.015 to about 0.2 μm 2 , preferably about 0.015 to about 0.15 μm 2 The maximum pore size on the plasma-facing surface 106 of the at least one first layer 100 containing 0.7 μm YAG was measured, and the maximum area containing porosity was measured to be approximately 0.3 μm. 2 It was found that: Across the seven images analyzed within the plasma-facing surface 106 of the polycrystalline YAG of at least one first layer 100, no pores with a pore size greater than 0.7 μm were measured.

[0138] Figure 15 shows the mm 2 Unit area: μm 2 The cumulative fractional area with unit porosity (cumulative pore area) is shown, and the cumulative pore area (μm 2 ) for a given pore size for the seven images (from the plasma-facing surface 106) referenced in FIG. 2 / mm 2 Porosity was measured within each image (μm 2 ) using SEM images and ImageJ image processing methods disclosed herein. 2 units), total measured image area (mm 2 ) to calculate the cumulative pore area. At least one first layer 100 comprising YAG as disclosed herein has a cumulative pore area of ​​about 2 to about 800 μm as measured using SEM and image processing methods as disclosed herein. 2 / mm 2 , preferably about 2 to about 600 μm 2 / mm 2 , preferably about 2 to about 400 μm 2 / mm 2, preferably about 2 to about 300 μm 2 / mm 2 The cumulative pore area of ​​the multi-layer sintered ceramic body includes 100 μm of porosity. Over the seven images analyzed on the YAG plasma-facing surface 106 of at least one first layer 100 of the multi-layer sintered ceramic body, no pores with a pore size greater than 0.6 μm were measured. Thus, over the seven images, each of approximately 54 μm by 54 μm in area, the multi-layer sintered ceramic body disclosed herein has at least one first layer 100 having a plasma-facing surface 106 that includes a very low (<0.1 area %) porosity corresponding to a pore size of less than 1 μm, thus providing a corrosion- and erosion-resistant plasma-facing surface 106 of the multi-layer sintered ceramic body for use in a plasma processing chamber.

[0139] FIG. 16a) shows a 5000x SEM image showing a dense sintered microstructure after a thermal etching process of the plasma-facing surface 106 of at least one first layer 100 comprising a polycrystalline YAG phase. Very fine scale porosity with almost no pores is shown on the plasma-facing surface 106 of at least one first layer 100 of YAG. An almost fully dense microstructure is shown with a minimum porosity and a pore size of about 1 μm or less. A multilayer sintered ceramic body according to one embodiment comprises at least one first layer 100 comprising polycrystalline YAG having a plasma-facing surface 106 comprising pores, the pores having a pore size on the order of 5 μm or less, a submicron scale pore size of about 0.1 to about 5 μm, preferably about 0.1 to about 4 μm, preferably about 0.1 to about 3 μm, preferably about 0.1 to about 2 μm, preferably about 0.1 to about 1 μm. In this embodiment, at least one first layer 100 including YAG of a multilayer sintered ceramic body 98 formed from the materials and processes may include pores having maximum sizes of 0.1-5 μm, preferably 0.1-4 μm, preferably 0.1-3 μm, preferably 0.1-2 μm, and 0.1-1 μm as measured using the SEM and image processing methods disclosed herein. Approximately 22 pores were counted across a 54 μm by 54 μm plasma-facing surface 106.

[0140] FIG. 16b) shows the sum of the total surface area including pores or porosity (% of surface area) for each of the seven SEM images measured for FIG. 15 on the vertical axis, while the horizontal axis represents the corresponding pore size for a given % pore area in microns. Within a given image, the total area including porosity and the total image measured area were used to calculate the % pore area. As shown in FIG. 16, the measurements across the seven SEM images correspond to at least one first layer 100 having a plasma-facing surface 106 including YAG, the YAG being between 0.0005-2%, preferably between 0.0005-1%, preferably between 0.0005-0.5%, preferably between 0.0005-0.0 ... 5-0.03%, preferably 0.0005-0.005%, preferably 0.0005-0.003%, preferably 0.0005-0.001%, preferably 0.005-2%, preferably 0.05-2%, preferably 0.5-2%, preferably 0.005-2%, preferably 0.005-1%, preferably 0.05-2%, preferably 0.05-1%, preferably 0.5-2%. Thus, across an image each having an area of ​​about 54 μm×54 μm, the multilayer sintered ceramic body disclosed herein includes a plasma-facing surface 106 that includes a very low (<1% by total area) percentage of porosity, thus providing a corrosion- and erosion-resistant surface of the multilayer sintered ceramic body 98 for use in a plasma processing chamber.

[0141] The small pore / void maximum size and minimum porosity percent area of ​​at least one first layer 100 of the multi-layer sintered body may allow for reduced particle generation and corrosion and erosion required for use in semiconductor reactors. This minimum porosity corresponds to a high density, which also provides resistance to corrosion and erosion that allows for their use as components in semiconductor etching and deposition applications.

[0142] Density measurements of multi-layer bodies have proven difficult due to differences in density of the layers. Density measurements were performed on multi-layer sintered ceramic bodies (disclosed in Example 4) by sectioning a sample cut from the full thickness of the multi-layer sintered body into its first and second layers and performing density measurements of the individual layers. Measurements were performed according to the Archimedes immersion method of ASTM B962-17, and a density of 4.55 to 4.57 g / cc, preferably about 4.56 g / cc, was measured for at least one first layer 100 of polycrystalline YAG. The reported density values ​​are averages over five measurements, and the standard deviation in the measurements (using known standards) was determined to be about 0.002. A commercially available single crystal sample of bulk YAG was measured for density using the method disclosed herein. An Archimedes density of 4.56 g / cc was obtained over five measurements, and this value is the theoretical density of YAG used herein. Thus, the at least one first layer 100 comprising YAG of a single multi-layer sintered ceramic body according to one embodiment has a density of 98.5-100%, preferably 99-100%, preferably 99.5-100%, preferably 99.7-100%, preferably about 100% of the theoretical density of YAG. The density of the at least one second layer 102 comprising about 16 volume percent of at least one of stabilized zirconia and partially stabilized zirconia (and balance alumina) was measured according to the Archimedes immersion method of ASTM B962-17, and a density of about 4.32 g / cc was calculated. Using volumetric mixture rules known in the art to calculate the theoretical density of the at least one second layer comprising alumina and at least one of about 16 volume percent stabilized zirconia and partially stabilized zirconia, a density of 4.31-4.33 g / cc, preferably about 4.32 g / cc, was measured and taken as the theoretical density of the at least one second layer 102. Thus, the at least one second layer 102 of the multi-layer sintered ceramic body (comprising about 16 volume percent zirconia and balance alumina) has a theoretical density percent of 98-100%, preferably 99-100%, preferably 99.5-100%, preferably about 100% of theoretical density.The single multi-layer sintered ceramic body disclosed according to this embodiment comprises at least one first and second layer, each having a % theoretical density (also denoted as relative density, RD) that is greater than 98% of the theoretical density of the single multi-layer sintered ceramic body, preferably 98-100%, preferably 99-100%, preferably 99.5-100%, preferably about 100%.

[0143] The relative density (RD) of a given material is defined as the ratio of the measured density of a sample to the reported theoretical density of the same material, as shown in the following formula: Volumetric porosity (Vp) is calculated from the density measurements as follows:

[0144]

number

[0145] The very high density of the at least one first layer comprising polycrystalline YAG (see, for example, Example 4) allows the at least one plasma-facing surface 106 to be polished to a very low surface roughness Sa and low peak-to-valley Sz. Polishing was performed using methods known to those skilled in the art, and the plasma-facing surface 106 of the at least one first layer comprising polycrystalline YAG 100 was measured to have an average surface roughness Sa of 8 nm and an average peak-to-valley Sz of 0.14 μm using the measurement method according to ISO standard 25178-2-2012 disclosed herein. The measurements were averaged over 10 repetitions. The plasma-facing surface 106 of the at least one first layer comprising polycrystalline YAG 100 was measured to have a maximum surface roughness Sa of 10 nm and a maximum peak-to-valley Sz of 0.21 μm. The plasma-facing surface 106 of the at least one first layer 100 comprising polycrystalline YAG was measured to have a minimum surface roughness Sa of 5 nm, and a minimum peak-to-valley Sz of 0.057 μm. The disclosed surface properties of the dense at least one first layer comprising YAG may provide improved resistance to corrosion and erosion, thereby providing reduced particle generation during use as a component in a semiconductor plasma processing chamber.

[0146] Laminates common in the art, including, for example, tape cast and spray dried layers, typically have laminates or layers exposed to plasma treatments that have a lower density than those disclosed herein, and therefore may not be polished to the very low surface roughness as disclosed herein, and therefore may not provide sufficient resistance to the corrosive and erosive effects of the harsh plasmas used during semiconductor processing, resulting in the release of particles into the plasma chamber during use.

[0147] The high density of the at least one first layer of high density polycrystalline YAG may enable high hardness values ​​of the plasma-facing surface 106 of the at least one first layer, which may provide resistance to the erosive effects of ion bombardment used during typical plasma processes. Erosion or spalling may result from ion bombardment of the component or layer surface due to the use of an inert plasma gas such as Ar. These materials with high hardness values ​​may be preferred for use as materials for components due to their enhanced hardness values ​​providing greater resistance to ion bombardment and resulting erosion. Thus, Vickers hardness measurements were performed on the exemplary plasma-facing surface 106 of the at least one first layer 100 comprising polycrystalline YAG according to ASTM standard C1327 "Standard Test Method for Vickers Indentation Hardness of Advanced Ceramics". The test equipment used for all hardness measurements was a Wilson Micro Hardness Tester Model VH1202. Hardness values ​​of at least 1200HV, preferably at least 1400HV, preferably at least 1800HV, preferably at least 2000HV, 1300-1600HV, 1300-1500HV, 1300-1450HV, 1300-1400HV, 1400-1600HV, 1450-1600HV, 1450-1550HV, were measured for the plasma-facing surface 106 of at least one first layer 100 of a multilayer sintered ceramic body 98 disclosed herein. Measurements were made using the Vickers hardness method known in the art and converted to SI units of GPa. Hardness values ​​of 12.75-15.69 GPa, 12.75-14.71 GPa, 12.75-14.22 GPa, 12.75-13.73 GPa, 13.73-15.69 GPa, 14.22-15.69 GPa, and preferably 14.22-15.20 GPa have been measured. These high hardness values ​​can contribute to improved resistance to ion bombardment during semiconductor etching processes and reduced erosion during use, providing extended component life when the multilayer sintered ceramic body is machined into a multilayer sintered ceramic component having fine-scale features.Table 5 lists the hardness values ​​of the multi-layer sintered ceramic bodies disclosed herein. The average is reported over eight test replicates using a 2 kgf load cell / applied load for Samples A, C, and B, and a 0.025 kgf load for Sample D.

[0148] [Table 5]

[0149] In one embodiment, the sintered ceramic bodies disclosed herein have an average hardness of about 13.0-16.0 GPa calculated from eight test replicates using an applied load of 0.2 kgf as measured according to ASTM standard C1327. In another embodiment, the sintered ceramic bodies disclosed herein have an average hardness of about 13.5-15 GPa calculated from eight test replicates using an applied load of 0.2 kgf as measured according to ASTM standard C1327. In other embodiments, the sintered ceramic bodies may have an average hardness of about 13.8-15.8 GPa calculated from eight test replicates using an applied load of 0.025 kgf.

[0150] The surface roughness of the at least one first layer plasma-facing surface 106 can affect performance in a semiconductor processing chamber. Surface roughness measurements were performed using a Keyence 3D laser scanning confocal digital microscope model VK-X250X under Class 1 cleanroom environmental conditions. The microscope is placed on a TMC tableTop CSP benchtop passive vibration isolation table with a natural frequency of 2.8 Hz. This non-contact system uses a laser beam light and an optical sensor to analyze the surface via the intensity of the reflected light. Surface roughness characteristics Sa and Sz are parameters known in the underlying technical field and are described, for example, in ISO standard 25178-2-2012. Section 4.17 of the ISO standard describes surface roughness Sa, Section 4.1.6 describes Sz, and Section 4.3.2 describes Sdr. ISO 25178 Surface Texture (Areal Roughness Measurement) is a collection of international standards related to the analysis of surface roughness, with which this microscope complies. Sa is the average roughness value calculated over a user-defined area (arithmetic mean height of the scale-limited surface) of the surface of the multilayer sintered ceramic body. Sz represents the maximum peak-to-valley distance (maximum height of the scale-limited surface, peak-to-valley) over a user-defined area of ​​the surface of the multilayer sintered ceramic body. Sdr is a calculated numerical value defined as the "Developed Interfacial Area Ratio" and is a proportional representation of the increase in actual surface area relative to a perfectly flat surface. A flat surface is assigned an Sdr of 0, and the value increases with the slope of the surface. A larger numerical value corresponds to a larger increase in surface area. This allows for a numerical comparison of the extent of surface area increase of the samples. It represents the additional surface area resulting from texture or surface features compared to flat areas.

[0151] A laser scan of the surface of the sample was performed at 50x magnification using a confocal microscope to capture detailed images of the sample. The parameters Sa (arithmetic mean height), Sz (maximum height), Ra (line roughness) and Sdr (developed interfacial area) were measured in selected areas of the polished surface (plasma-facing surface 106) of at least one layer 100 of the multilayer sintered ceramic body. The roughness was obtained in the profiles of seven sectioned blocks. The lambda chi (λ), which represents the measurement sampling length, was adjusted to restrict the line readings to measurements from five central blocks out of seven, according to ISO standard 4288: Geometrical Product Specifications (GPS)--Surface texture:Profile method--Rules and procedures for the assessment of surface texture. A surface area was selected within the polished surface of the sample for the measurements. The area was selected to be most representative of a typical sample surface and was used to calculate Sa, Sz and Sdr.

[0152] In one embodiment in which the plasma-facing surface 106 of at least one first layer comprises YAG, surface roughness measurements are made in accordance with ISO standard 25178-2-2012 and are within the range of 0.0005-2 μm, preferably 0.0005-1.5 μm, preferably 0.0005-1 μm, preferably 0.0005-0.75 μm, preferably 0.0005-0.5 μm, preferably 0.0005-0.25 μm, preferably 0.0005-0. Sa values ​​of 125 μm, preferably 0.0005-0.075 μm, preferably 0.0005-0.050 μm, preferably 0.0005-0.025 μm, preferably 0.0005-0.020 μm, preferably 0.0005-0.015 μm, preferably 0.0005-0.010 μm, preferably 0.001-0.030 μm, preferably 0.001-0.020 μm, preferably 0.001-0.010 μm have been measured. Table 6 below lists Sa, Sz, and Sdr values ​​for at least one first layer 100 including a plasma-facing surface 106 comprising YAG according to embodiments disclosed herein.

[0153] [Table 6]

[0154] Thus, at least one first layer 100 comprising YAG of a multilayer sintered ceramic body according to one disclosed embodiment (and listed in Table 6) has a thickness of 0.0005-2 μm, preferably 0.0005-1.5 μm, preferably 0.0005-1 μm, preferably 0.0005-0.75 μm, preferably 0.0005-0.5 μm, preferably 0.0005-0.25 μm, preferably 0.0005-0.1 μm, as measured according to ISO standard 25178-2-2012. The plasma-facing surface 106 may have a surface roughness Sa of 25 μm, preferably 0.0005 to 0.075 μm, preferably 0.0005 to 0.050 μm, preferably 0.0005 to 0.025 μm, preferably 0.0005 to 0.020 μm, preferably 0.0005 to 0.015 μm, preferably 0.0005 to 0.010 μm, preferably 0.001 to 0.030 μm, preferably 0.001 to 0.020 μm, preferably 0.001 to 0.010 μm.

[0155] According to Table 6, the at least one first layer 100 comprising YAG of a multilayer sintered ceramic body according to one embodiment disclosed herein may have a plasma-facing surface 106 having a peak-to-valley Sz of 0.3-5 μm, preferably 0.3-4 μm, preferably 0.3-3 μm, preferably 0.3-2 μm, preferably 0.3-1 μm, preferably 0.65-5 μm, preferably 1-5 μm, preferably 2-5 μm, preferably 0.35-3 μm, preferably 0.5-1 μm, as measured according to ISO Standard 25178-2-2012.

[0156] According to Table 6, the at least one first layer 100 including YAG of the multilayer sintered ceramic body according to one embodiment disclosed herein has a thermal conductivity of 5×10 -5 ~550×10 -5 , preferably 30 x 10 -5 ~400×10 -5, preferably 30 x 10 -5 ~200×10 -5 , preferably 40 x 10 -5 ~100×10 -5 The plasma-facing surface 106 may have a developed interfacial area Sdr of

[0157] To evaluate performance in halogen-based plasma applications, etching was performed on sintered ceramic bodies prepared according to one embodiment comprising at least one first layer 100 comprising YAG, as described below.

[0158] To evaluate the etching performance, polished ceramic samples with a plasma-facing surface containing a first layer of YAG with dimensions of 6 mm × 6 mm × 2 mm were mounted on a c-plane sapphire wafer using a silicone-based heat sink compound. Areas of each section were blocked from exposure to the etching process by bonding a 5 mm × 5 mm square piece of sapphire ceramic to the sample surface.

[0159] The dry etching process was performed using industry standard equipment, a Plasma-Therm Versaline DESC PDC Deep Silicon Etch. The etch was completed using a two-step process for a total duration of 6 hours. The etch method was performed using a pressure of 10 millitorr, a bias of 600 volts, and an ICP power of 2000 watts. The etch method was performed using a first etch step with a CF4 flow rate of 90 standard cubic centimeters per minute (sccm), an oxygen flow rate of 30 standard cubic centimeters per minute (sccm), and an argon flow rate of 20 standard cubic centimeters per minute (sccm), and a second etch step with an oxygen flow rate of 100 standard cubic centimeters per minute (sccm) and an argon flow rate of 20 standard cubic centimeters per minute (sccm), with the first and second etch steps repeated for 300 seconds each for a total duration of 6 hours. The etch conditions used herein to evaluate sample performance were selected to subject the disclosed materials to extreme etch conditions in order to differentiate performance. Once the etching procedure was completed, the surface roughness parameters Sa, Sz, and Sdr were measured using the methods disclosed herein. Table 7 lists the results after etching (using a two-step process as disclosed herein) for various samples having a plasma-facing surface 106 of at least one first layer 100 comprising YAG.

[0160] [Table 7]

[0161] Exemplary plasma-facing surfaces 106 of at least one first layer 100 comprising YAG were fabricated using excess alumina (samples 311 and 322), zirconia doping (sample 298), stoichiometric YAG (samples 454 and 223), and reduced relative density (RD), sample 454-1. As set forth in Table 7, process conditions (process) are described as the temperature T (° C.), pressure P (MPa), and time t (min) used to fabricate each of the respective samples according to the methods disclosed herein. Where applicable, annealing was performed at 1400° C. in air for 8 hours.

[0162] In one embodiment, the present disclosure relates to a multilayer sintered ceramic body and / or components made therefrom having at least one first layer 100 comprising YAG, which provides, prior to an etching or deposition process, an arithmetic mean height Sa, surface roughness in unetched areas of less than 15 nm, more preferably less than 13 nm, more preferably less than 10 nm, more preferably less than 8 nm, more preferably less than 5 nm, according to clause 4.1.7 of ISO standard 25178-2-2012, and has a plasma-facing surface 106 not exceeding a particular value.

[0163] In one embodiment, the present disclosure relates to a multilayer sintered ceramic body and / or components made therefrom having at least one first layer 100 comprising polycrystalline YAG having a plasma-facing surface 106, which provides a maximum height Sz of less than 5.0 μm, more preferably less than 4.0 μm, most preferably less than 3.5 μm, more preferably less than 2.5 μm, more preferably less than 2 μm, more preferably less than 1.5 μm, prior to an etching or deposition process, according to ISO standard 25178-2-2012, and has a surface not exceeding a specified value.

[0164] In one embodiment, the present disclosure provides a multi-layer sintered ceramic body and / or components made therefrom having at least one first layer 100 comprising polycrystalline YAG having a plasma-facing surface 106, the first layer 100 being etched to a thickness of 1500×10 in accordance with Section 4.1.7 of ISO standard 25178-2-2012 prior to an etching or deposition process. -5 Less than 1200×10 -5 Less than 1000×10 -5 less than 800×10 -5 Less than 600×10 -5 less than 400×10 -5 The present invention relates to a multi-layer sintered ceramic body and / or a component made therefrom, having a surface that provides a developed interfacial area Sdr of less than a specified value, and a surface roughness that does not exceed a specified value.

[0165] In one embodiment, the present disclosure provides a multi-layer sintered ceramic body and / or components made therefrom having at least one first layer comprising polycrystalline YAG having a plasma-facing surface 106, the multi-layer sintered ceramic body having a thickness of 0.0005-2 μm, preferably 0.0005-1.5 μm, preferably 0.0005-1 μm, preferably 0.0005-0.75 μm, preferably 0.0005-0.5 μm, preferably 0.0005-0.25 μm, preferably 0.0005-0.12 μm, in accordance with Section 4.1.7 of ISO Standard 25178-2-2012, prior to the etching or deposition process disclosed herein. The present invention relates to a multilayer sintered ceramic body and / or a component made therefrom, which provides an arithmetic mean height, surface roughness of 0.5 μm, preferably 0.0005-0.075 μm, preferably 0.0005-0.050 μm, preferably 0.0005-0.025 μm, preferably 0.0005-0.020 μm, preferably 0.0005-0.015 μm, preferably 0.0005-0.010 μm, preferably 0.001-0.030 μm, preferably 0.001-0.020 μm, preferably 0.001-0.010 μm, preferably 0.008 μm and has a surface not exceeding a particular value.

[0166] In one embodiment, the present disclosure relates to a multilayer sintered ceramic body and / or component made therefrom having at least one first layer comprising polycrystalline YAG having a plasma-facing surface 106, which after an etching or deposition process disclosed herein provides a maximum height Sz, surface roughness according to ISO standard 25178-2-2012, of less than 3.8 μm, more preferably less than 2.8 μm, most preferably less than 2.5 μm, more preferably 0.1-2.5 μm, more preferably 0.1-1.5 μm, more preferably 0.1-1.0 μm, more preferably 0.1-0.5 μm, more preferably about 0.1-0.3 μm, and has a surface that does not exceed a specified value.

[0167] In one embodiment, the present disclosure provides a multi-layer sintered ceramic body and / or components made therefrom having at least one first layer comprising polycrystalline YAG having a plasma-facing surface 106, the multi-layer sintered ceramic body having a plasma-facing surface 106 and a plasma-facing surface 108 having a thermal conductivity of 3000×10 sintered ceramic particles in accordance with Section 4.1.7 of ISO Standard 25178-2-2012 after an etching or deposition process disclosed herein. -5 Less than 2500×10 -5 Less than 2000×10 -5 Less than 1500×10 -5 Less than 1000×10 -5 The present invention relates to a multi-layer sintered ceramic body and / or components made therefrom, which provides a developed interfacial area Sdr, surface roughness of less than 100 nm, more preferably less than 800×10-5, and has a surface that does not exceed a certain value. By using the multi-layer sintered ceramic body according to an embodiment disclosed herein, a significant corrosion and erosion resistant material is provided that allows for continuous long-term use as a component in etching and deposition processes. The corrosion and erosion resistant material minimizes particle generation due to the improved surface properties disclosed herein, providing improved performance during use and reduced contamination of semiconductor substrates during processing.

[0168] The starting powders and powder mixtures used to make the at least one first layer 100 disclosed herein and having very high purity can provide corrosion and erosion resistance that allows for use as components in semiconductor etching and deposition applications. This high purity provides a chemically inert plasma-facing surface 106 (the term inert as used herein is intended to mean chemically inert), which can prevent the plasma-facing surface 106 of the at least one first layer 100 from being roughened by halogen-based gas species that would otherwise chemically attack and etch materials made from powders and powder mixtures of lower purity, or be eroded by ion bombardment. Impurities and contaminants in the at least one first layer 100 can serve as initiation sites for corrosion and erosion, and therefore high purity (and corresponding low impurity content, expressed in ppm of contaminants) is preferred in the at least one first layer 100 of the multilayer corrosion-resistant sintered ceramic body, especially on the plasma-facing surface 106. Table 9 lists the impurities of an exemplary powder mixture according to one embodiment that is sintered to form at least one first layer 100 comprising substantially phase-pure polycrystalline YAG.

[0169] According to the disclosure herein, a multi-layer sintered ceramic body having at least one first layer plasma-facing surface 106 containing an amount of yttrium aluminum garnet (YAG) phase greater than 90% by volume can be formed by in situ reaction sintering during the sintering process due to the combined properties of particle size distribution, purity and / or surface area of ​​the powder mixture disclosed herein. In an embodiment, the powder mixture contains crystalline powders of yttria and alumina. In another embodiment, in addition to the crystalline powders of yttria and alumina, the powder mixture can be sintered and contains less than about 10% by volume of YAG, preferably less than 8% by volume of YAG, preferably less than 5% by volume of YAG. In another embodiment, disclosed herein is a powder mixture that is free or substantially free of YAG phase (including crystalline powders of yttria and alumina). In another embodiment ... 2In other embodiments, the powder mixture may be sintered in a volume of about 2 m to form at least one first layer of a multi-layer sintered ceramic body comprising YAG by the in situ reactive phase sintering process disclosed herein. 2 It may be preferable to have no YAG phases with a specific surface area of ​​1000 nm / g or more. All purity measurements disclosed herein were measured above the reporting limit of the particular element and were performed using an Agilent 7900ICP-MS model G8403 ICP-MS. The liquid sample is introduced into the ICP-MS as a fine aerosol, which is ionized in a plasma discharge and then separated using a quadrupole mass analyzer known to those skilled in the art. The detection limit using the ICP-MS method disclosed herein to identify the presence of lighter elements is higher than the reporting limit of the heavier elements. In other words, heavier elements, such as Sc and above, are detected with a higher precision, such as as low as 0.06 ppm, than lighter elements, such as Li to Al (which are detected with a precision of, for example, 0.7 ppm). Thus, the impurity content of these powders containing lighter elements such as Li through Al can be determined to about 0.7 ppm or better, and the impurity content of heavier elements from Sc (scandium) through U (uranium) can be determined to about 0.06 ppm or better. Using the ICPMS method disclosed herein, silica can be detected in amounts as low as about 14 ppm, while K (potassium) and Ca (calcium) can be identified in amounts of 1.4 ppm or better. Iron can be detected with an accuracy of as low as 0.14 ppm or better. The total impurity content disclosed herein does not include silica.

[0170] The plasma-facing surface 106 of the at least one first layer 100 comprising polycrystalline YAG may have a total impurity content, measured using ICPMS techniques, of less than 100 ppm, preferably less than 75 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably less than 10 ppm, preferably less than 8 ppm, preferably less than 5 ppm, preferably between 5 and 30 ppm, preferably between 5 and 20 ppm, based on the total mass of the at least one first layer comprising polycrystalline YAG. The total impurity content disclosed herein does not include Si in the form of silica.

[0171] The detection limit using the ICP-MS method disclosed herein to identify the presence of lighter elements is higher than the reporting limit of heavier elements. In other words, heavier elements, such as Sc and above, are detected with a higher precision, such as a lower precision of 0.06 ppm, than lighter elements, such as Li to Al, which are detected with a precision of 0.7 ppm. Thus, the impurity content of these powders containing lighter elements, such as Li to Al, can be determined to about 0.7 ppm or higher, and the impurity content of heavier elements, such as Sc (scandium) to U (uranium), can be determined to about 0.06 ppm or higher. Using the ICPMS method disclosed herein, silica can be detected in amounts as low as about 14 ppm, while K (potassium) and Ca (calcium) can be identified in amounts of 1.4 ppm or higher. Iron can be detected with a precision as low as 0.14 ppm.

[0172] Sintering aids such as SiO2, MgO, CaO, Li2O and LiF are known to promote densification, and LiF in particular is known to be used to promote grain growth and thereby increase the grain size of YAG and spinel. However, these sintering aids may reduce corrosion resistance, strength and performance in etching and deposition applications. Thus, in embodiments, at least one first layer 100 of the multilayer sintered ceramic body disclosed herein may be formed from at least one powder mixture having a calcia, magnesia, lithia and / or lithium fluoride content of about 2 ppm or less, respectively, based on the total mass of the powder mixture. The high purity powder mixture, which may be calcined and then sintered using the methods disclosed herein, is thereby transferred to the multilayer sintered ceramic body. In embodiments disclosed herein, for example, a multi-layer sintered ceramic body may have at least one first layer 100 comprising at least one crystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconia, and each of the at least one first layer 100 comprises silica in an amount of 14-100 ppm, preferably 14-75 ppm, preferably 14-50 ppm, preferably 14-25 ppm, preferably 14-20 ppm, preferably about 14 ppm, each based on the weight of the at least one first layer 100. In other embodiments, each of the at least one first layer 100 may include at least one of magnesia, lithia / lithium fluoride, and / or calcia in an amount of about 2-100 ppm, preferably about 2-75 ppm, preferably about 2-50 ppm, preferably about 2-25 ppm, preferably about 2-20 ppm, preferably about 2-10 ppm, each based on the mass of the at least one first layer 100. To enhance strength and provide chemical inertness in the at least one first layer 100 including at least one crystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and zirconia and alumina, each of the at least one first layer 100 preferably does not include more than about 2 ppm of Li or LiF, each based on the mass of the at least one first layer 100.Thus, in a further embodiment, each of the at least one first layer 100 comprising at least one crystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and zirconia and alumina may comprise lithium fluoride, calcia and / or magnasia in an amount of about 2-100 ppm, preferably 2-75 ppm, preferably 2-50 ppm, preferably 2-25 ppm, preferably 2-20 ppm, each relative to the total mass of the at least one first layer 100.

[0173] In a preferred embodiment, at least one first layer comprising polycrystalline YAG may each have a purity of 99.99% or greater, preferably 99.995% or greater, for a material having 100% purity as measured using the ICPMS techniques disclosed herein.

[0174] In an embodiment, each of the at least one first layer 100 comprising at least one polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconia may comprise Si in the form of silica in an amount of 14-100 ppm, preferably 14-75 ppm, preferably 14-50 ppm, preferably 14-25 ppm, preferably 14-20 ppm, preferably about 14 ppm, each relative to the total mass of the at least one first layer.

[0175] In the embodiments of the multilayer sintered ceramic body disclosed herein, each of the at least one first layer 100 comprising at least one polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconia can be prepared using, for example, rare earth oxides selected from the group consisting of Sc, La, Er, Ce, Cr, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Tm, Yb, and Lu, and optional dopants of oxides and combinations thereof, in an amount of >0.002 wt.%, preferably >0.0035 wt.%, preferably >0.005 wt.%, preferably >0.0075 wt.%, which can be added to the starting powder or powder mixture in steps a, b, or c.

[0176] In an embodiment of the multilayer sintered ceramic body disclosed herein, at least one first layer 100 of said ceramic sintered body can be prepared using rare earth oxides selected from the group consisting of Sc, La, Er, Ce, Cr, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Tm, Yb, and Lu, as well as optional dopants of oxides and combinations thereof, in an amount of <0.05 wt.%, preferably <0.03 wt.%, preferably <0.01 wt.%, preferably 0.002-0.02 wt.%, which can be added to the starting powder or powder mixture in steps a, b, or c.

[0177] In the embodiments of the multilayer sintered ceramic body disclosed herein, the at least one first layer 100 comprising at least one polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconia may be made without the aforementioned dopants. In particular, for semiconductor chamber applications requiring chemical inertness and resistance to corrosion and erosion combined with high strength, it may be preferable that each of the at least one first layer 100 comprising at least one polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconia of the multilayer sintered ceramic body is free or substantially free of dopants. Thus, in certain embodiments, a multilayer sintered ceramic body having at least one first layer 100 comprising at least one polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconia is substantially free of the aforementioned dopants or is free of at least one or all of the aforementioned dopants.

[0178] According to some embodiments, excess yttria and / or alumina in the polycrystalline YAG layer 100 is not considered a dopant or sintering aid to the extent that it may remain in the at least one first layer. The high purity and corresponding low impurities of the plasma-facing surface 106 of the disclosed at least one first layer may enable reduced particle generation and corrosion and erosion required for use in semiconductor reactors. For example, a purity of 99.99% or higher, preferably 99.995% or higher, preferably 99.999% or higher, preferably 99.9995% or higher, preferably about 99.9999% may be measured for the at least one first layer 100 including polycrystalline YAG.

[0179] The dielectric loss / tangent delta of the at least one first layer 100 and at least one second layer 102 of polycrystalline YAG are listed below in Table 8. The high purity of each layer comprising the multi-layer sintered ceramic body is 5.5×10 at 1 MHz for the at least one first layer comprising YAG. -3 Below, 1×10 at 1GHz -4 and for at least one second layer comprising alumina and about 16 volume percent partially stabilized zirconia, providing a low loss tangent of less than 0.0007. Measurements were performed on exemplary solid bodies of each material.

[0180] [Table 8]

[0181] However, these corrosion and erosion resistant materials pose the challenge of sintering to the high densities required for semiconductor etch and deposition chamber applications, and thus pressure assisted sintering techniques, and in preferred embodiments pressure and current assisted sintering techniques, are typically required.

[0182] According to another embodiment, disclosed herein is a single multi-layer sintered ceramic body comprising at least one first layer 100 comprising magnesium aluminate spinel, at least one second layer 102 comprising alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia, and at least one third layer 103 comprising a multiphase layer comprising at least YAG, alumina, and zirconia, wherein the zirconia comprises at least one of unstabilized zirconia, stabilized zirconia, and partially stabilized zirconia, wherein an absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first, second, and third layer is greater than or equal to ASTM A 1024 over a temperature range of 25-1700° C. or over a temperature range of 200-1400° C. When measured in accordance with E228-17, it is 0 to 0.75×10-6 / °C, preferably 0 to 0.7×10-6 / °C, preferably 0 to 0.6×10-6 / °C, preferably 0 to 0.5×10-6 / °C, preferably 0 to 0.45×10-6 / °C, preferably 0 to 0.4×10-6 / °C, preferably 0 to 0.35×10-6 / °C, preferably 0 to 0.3×10-6 / °C, preferably 0 to 0.25×10-6 / °C, preferably 0 to 0.2×10-6 / °C, preferably 0 to 0.15×10-6 / °C, preferably 0 to 0.1×10-6 / °C, preferably 0 to 0.08×10-6 / °C, preferably 0 to 0.04×10-6 / °C, preferably 0 to 0.02×10-6 / °C. These ranges of absolute values ​​of the difference in CTE between the at least one first layer comprising magnesium aluminate spinel, the second layer, and the third layer correspond to percentage CTE differences between any of the at least one first, second, and third layers of 9% or less (as measured relative to the at least one first layer 100 comprising magnesium aluminate spinel), preferably 7% or less, preferably 5% or less, preferably 3% or less, preferably 2% or less, preferably 1.5% or less, preferably 1% or less, preferably 0.5% or less, preferably 0.1% or less.The at least one first, second and third layers are matched in CTE within the disclosed ranges over a temperature range from ambient temperature (or at least 200°C as shown in the figures) to about 1700°C (or at least 1400°C as shown in the figures) to form a single multi-layer sintered ceramic body.

[0183] 17a), b), and c) show CTE measurements over a temperature range of ambient temperature (or at least 200° C. as shown) to about 1700° C. (or at least 1400° C. as shown) of exemplary materials for forming at least one first and second layer of a single multi-layer sintered ceramic body according to one embodiment. All CTE measurements disclosed herein were made in accordance with ASTM E228-17. CTE measurements were made on exemplary bulk materials. FIG. 17a) shows a first layer 100 of magnesium aluminate spinel and a second layer 102 including alumina and zirconia, where the zirconia includes at least one of stabilized zirconia and partially stabilized zirconia in an amount of about 25% by volume. FIG. 17b) shows a first layer 100 of spinel and a second layer 102 including alumina and zirconia, where the zirconia includes at least one of stabilized zirconia and partially stabilized zirconia in an amount of about 16% by volume of zirconia and the balance being alumina. FIG. 17c) shows the CTE measurement of at least one first layer 100 of magnesium aluminate spinel and at least one second layer 102 including alumina and zirconia, the zirconia including at least one of stabilized zirconia and partially stabilized zirconia in an amount of about 20% by volume of zirconia and balance alumina, over a temperature range of 200° C. to 1400° C. The composition of the at least one second layer 102 and at least one third layer 103 of ZTA may be varied to CTE match the at least one first layer 100 including spinel. The composition range of the at least one second layer 102 including zirconia and alumina (16% by volume to 25% by volume of zirconia and balance alumina) may be suitable to CTE match the at least one first layer 100 including spinel. Thus, disclosed herein is a multi-layer sintered ceramic body comprising at least one second layer comprising about 16 to about 25 volume percent zirconia (and balance alumina), at least one first layer 100 comprising magnesium aluminate spinel, and at least one third layer having a CTE match to the at least one first and second layer.To more closely match the CTE of the first layer 100, second layer 102, and third layer 103 of spinel according to one embodiment, the second layers 102 each include about 15% to about 25% by volume, preferably about 18% to about 20% by volume, and more preferably about 20% by volume, zirconia (and balance alumina). These compositional ranges for the at least one second layer 102 are about 0.45×10-10, as measured according to ASTM E228-17, over a temperature range from ambient temperature (or at least 200° C. as shown) to about 1700° C. (or at least 1400° C. as shown), for the at least one first layer 100 of spinel. -6 / ℃ or less, preferably 0.4×10 -6 / ℃ or less, preferably 0.3×10 -6 / °C or less, preferably about 0.25×10 -6 / ℃ or less, preferably 0.2×10 -6 / ℃ or less, preferably 0.15×10 -6 / ℃ or less, preferably 0.1×10 -6CTE can be provided in an amount of below / ℃, preferably below 0.08×10-6 / ℃, preferably below 0.06×10-6 / ℃, preferably below 0.04×10-6 / ℃, preferably below 0.02×10-6 / ℃, preferably below 0.01×10-6 / ℃. As a percentage relative to at least one first layer, the difference in CTE by percentage (between any of at least one first, second, and third layers according to one embodiment) can be 6% or less, about 5% or less, preferably 4% or less, preferably 3% or less, preferably 2% or less, preferably 1.5% or less, preferably 1% or less, preferably 0.5% or less, preferably 0.25% or less (measured relative to at least one first layer 100 containing spinel). Zirconia can be at least one of stabilized and partially stabilized zirconia according to the methods and stabilizing compounds disclosed herein. The variation in CTE between at least one second layer 102 (containing zirconia and alumina), at least one first layer (containing magnesium aluminate spinel), and at least one third layer (containing a combination of the first and second layers) is within the range disclosed to enable the successful manufacture of a single multi-layer sintered ceramic body disclosed herein.

[0184] Figure 18 shows the X-ray diffraction results of a fired powder mixture (fired at 850 °C for 4 hours) of magnesia and alumina (with minor spinel phase formation) batch processed to form at least one first layer 100 containing the magnesium aluminate spinel phase MgAl2O4 (after sintering) according to one embodiment of a single multi-layer sintered ceramic body disclosed herein. The spinel phase is formed by a reactive sintering process in-situ from a powder mixture containing the starting powders of magnesia and alumina. In some embodiments, at least one first layer 100 containing spinel is substantially free or free of dopants, substantially free or free of sintering aids, and substantially free or free of LiF. In other embodiments, the first layer of spinel may contain a sintering aid in the amount disclosed herein (excluding magnesia which is the main component of spinel).

[0185] 19 shows a 1000X SEM image of a dense sintered microstructure of at least one first layer 100 comprising magnesium aluminate spinel according to one embodiment disclosed herein. The at least one first layer 100 comprising spinel is free or substantially free of dopants, sintering aids and LiF as disclosed herein. A nearly fully dense microstructure with minimal porosity is shown.

[0186] According to this embodiment in which the at least one first layer comprises spinel, a Sa of about 5 to about 20 nm can be measured across the surface using the surface roughness measurement methods disclosed herein.

[0187] According to another embodiment, disclosed herein is a single multi-layer sintered ceramic body, comprising at least one first layer comprising at least one polycrystalline ceramic material comprising yttria and zirconia, wherein the zirconia is present in an amount of at least 10 mol % to at most 25 mol %, at least one second layer 102 comprising alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia, and at least one third layer 103 comprising a multiphase layer of at least YAG, alumina, and zirconia, wherein an absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first, second, and third layer is greater than or equal to 100% by mass in accordance with ASTM A1224 over a temperature range of 25-1700° C., or greater than or equal to 100% by mass in accordance with ASTM A1224 over a temperature range of 200-1400° C. E228-17, the temperature is 0 to 0.75×10-6 / °C, preferably 0 to 0.7×10-6 / °C, preferably 0 to 0.6×10-6 / °C, preferably 0 to 0.5×10-6 / °C, preferably 0 to 0.45×10-6 / °C, preferably 0 to 0.4×10-6 / °C, preferably 0 to 0.35×10-6 / °C, preferably 0 to 0.3×10-6 / °C, preferably 0 to 0.3×10-6 / °C, 0.25×10-6 / ℃, preferably 0 to 0.2×10-6 / ℃, preferably 0 to 0.15×10-6 / ℃, preferably 0 to 0.1×10-6 / ℃, preferably 0 to 0.08×10-6 / ℃, preferably 0 to 0.06×10-6 / ℃, preferably 0 to 0.04×10-6 / ℃, preferably 0 to 0.02×10-6 / ℃, preferably 0 to 0.01×10-6 / ℃. These ranges of absolute values ​​of the difference in CTE between the at least one first layer comprising yttria and zirconia (zirconia present in an amount of 10 mol % or more and 25 mol % or less) and the second and third layers correspond to percentage CTE differences between any of the at least one first, second and third layers of 8% or less (measured relative to the at least one first layer 100), preferably 6.5% or less, preferably 5% or less, preferably 4% or less, preferably 3% or less, preferably 2% or less, preferably 1% or less, preferably 0.5% or less, preferably 0.1% or less.The at least one first, second and third layers are matched in CTE within the disclosed ranges over a temperature range from ambient temperature (or at least 200°C as shown in the figures) to about 1700°C (or at least 1400°C as shown in the figures) to form a single multi-layer sintered ceramic body.

[0188] 20a), b), and c) show CTE measurements over a temperature range of ambient temperature (or at least 200° C. as shown) to about 1700° C. (or at least 1400° C. as shown) of exemplary materials for forming at least one first and second layer of a single multi-layer sintered ceramic body according to one embodiment. All CTE measurements disclosed herein were made in accordance with ASTM E228-17. CTE measurements were made on exemplary bulk materials. FIG. 20a) shows at least one first layer 100 comprising about 20 mole % zirconia and balance yttria, and at least one second layer 102 having 16 volume % zirconia and balance alumina. Figure 20b) shows at least one first layer 100 comprising about 20 mole % zirconia and balance yttria, and at least one second layer 102 having about 20 volume % at least one of partially stabilized zirconia and stabilized zirconia and balance alumina. Figure 20c) shows at least one first layer 100 comprising about 25 mole % zirconia and balance yttria, and at least one second layer 102 comprising about 25 volume % zirconia (by volume of the at least one second layer) and balance alumina. Variations of this embodiment may include at least one first layer 100 comprising at least one crystalline phase of a ceramic material including yttria and zirconia, where the zirconia is present in an amount of at least 10 mol% ZrO2 and at most 25 mol% ZrO2, preferably at least 12 mol% to at most 23 mol% ZrO2, preferably at least 15 mol% to at most 25 mol% ZrO2, preferably at least 18 mol% to at most 25 mol% ZrO2, preferably at least 10 mol% to at most 23 mol% ZrO2, preferably at least 10 mol% to at most 20 mol% ZrO2, preferably at least 15 mol% to at most 23 mol% ZrO2, with the balance comprising Y2O3. These compositions for the at least one first layer 100 may be combined with compositions of the at least one second layer 102 and at least one third layer 103 disclosed herein, with the at least one second and third layers having compositions (of zirconia and alumina) suitable for CTE matching with the at least one first layer 100 comprising at least one crystalline phase of yttria and zirconia.In an embodiment, at least one first layer 100 is a C-type solid solution, or a combination of fluorite and C-type solid solutions, or Zr3Y4O. 12The at least one crystalline phase of yttria and zirconia may be selected from the group consisting of a combination of compound phases including yttria and C-type solid solutions. C-type solid solutions refer to rare earth yttria-type solid solutions. These crystalline phases are consistent with the disclosed composition ranges as reported in "Phase Relations in the Yttria-Rich Portion of the Yttria-Zirconia System" (J. Mater. Sci 12 (1977) 311-316, HG Scott). In one embodiment, the CTE of the at least one first layer 100 (containing 10-25 mole % zirconia and balance yttria) may be CTE matched by at least one second layer 102 containing about 16 volume % to about 25 volume % zirconia and balance alumina (relative to the volume of the at least one second layer). In this embodiment, the CTE of at least one first layer 100 (including 10-25 mole % zirconia and balance yttria) can be CTE matched to at least one second layer 102 including about 16 to about 25 volume % at least one of partially stabilized zirconia and stabilized zirconia and balance alumina. Thus, disclosed herein is a multilayer sintered ceramic body 98 comprising at least one second layer 102 including about 16 to about 25 volume % at least one of partially stabilized zirconia and stabilized zirconia (and balance alumina) and at least one first layer 100 including 10-25 mole % zirconia and balance yttria. In a preferred embodiment, in order to more closely match the CTE of the at least one first layer 100 (containing 10-25 mol % zirconia and balance yttria) and the at least one second layer 102 (containing alumina and at least one of partially stabilized zirconia and stabilized zirconia), the at least one second layer each contains a volumetric amount of zirconia of at least one of partially stabilized zirconia and stabilized zirconia (and balance alumina) of about 16-25%, preferably about 20-25%, preferably about 22-25%, more preferably about 20%, relative to the volume of the at least one second layer 102.These compositional ranges for the at least one second layer 102 are approximately 0.55×10, as measured according to ASTM E228-17, for the at least one first layer 100 (containing 10-25 mole % zirconia and balance yttria) over a temperature range of ambient temperature (or at least 200° C. as shown in the figures) to approximately 1700° C. (or at least 1400° C. as shown in the figures). -6 / ℃ or less, preferably 0.5×10 -6 / ℃ or less, preferably 0.4×10 -6 / °C or less, preferably about 0.3 × 10 -6 / ℃ or less, preferably 0.2×10 -6 / ℃ or less, preferably 0.15×10 -6 / ° C. The zirconia of the at least one second layer 102 can be at least one of stabilized zirconia and partially stabilized zirconia according to the methods and stabilization compounds disclosed herein.

[0189] In an embodiment, the at least one first layer 100 comprising at least one crystalline phase of yttria and zirconia, where zirconia is present in an amount of 10 mol % or more ZrO2 and 25 mol % or less ZrO2, is substantially free or free of dopants and / or substantially free or free of sintering aids. In other embodiments, the at least one first layer 100 comprising at least one crystalline phase of yttria and zirconia in the disclosed amounts may comprise sintering aids and / or dopants in the amounts disclosed herein. The starting powder of zirconia comprising at least one first phase 100 comprising at least one crystalline phase of yttria and zirconia in the disclosed amounts may comprise at least one selected from the group consisting of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia.

[0190] FIG. 21 a) shows an SEM image illustrating a nonlinear interface 104 of a single multi-layer sintered ceramic body 98 according to one embodiment, where at least one first layer 100 includes at least one crystalline phase of a ceramic material including yttria and zirconia, where zirconia is present in an amount of about 20 mole %, with the remainder being yttria. In certain embodiments, the zirconia of the at least one first layer may be partially stabilized and may include about 3 mole % yttria as a stabilizing compound. In other embodiments, the zirconia of the at least one first layer may include at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia. In an embodiment, the at least one first layer 100 may include a reaction layer 108 adjacent to the at least one second layer 102, where the at least one second layer 102 and the reaction layer 108 form a nonlinear interface 104 between the layers. As can be seen in the SEM results of FIG. 21, the reaction layer 108 is very dense and has minimal porosity. The reaction layer 108 may have a thickness of 10-30 μm, preferably 15-30 μm, preferably 20-30 μm, preferably 25-30 μm, preferably about 20 μm, as measured from SEM images. The reaction layer 108 may improve the adhesive strength of the nonlinear interface 104. In an embodiment, the reaction layer 108 may include at least one crystalline phase selected from the group consisting of YAG, YAP, YAM, a cubic phase (comprising a solid solution of at least two of yttria, alumina, and zirconia), and a cubic fluorite crystalline phase (comprising a solid solution of at least two of yttria, alumina, and zirconia), and combinations thereof. FIG. 21b) shows a dense sintered microstructure of the plasma-facing surface 106 of at least one first layer 100 comprising about 20 mole % zirconia and balance yttria. A nearly fully dense microstructure with minimal porosity is shown.

[0191] According to one embodiment in which the at least one first layer comprises a solid solution of 80 mole % yttria and 20 mole % zirconia, an average Ra over five measurements of 10 to 25 nm was measured.

[0192] Multi-layer sintered bodies, as known to those skilled in the art, are often formed from pre-cast layers or tapes that are stacked and co-sintered, or stacked or deposited on a sintering substrate and sintered. However, these multi-layer stacks often delaminate at the interfaces between the layers due to poor interfacial bonding between the layers, resulting in spalling and particle ejection during use in semiconductor reactors. Typically, these stacks have interfaces that are linear and therefore do not provide the benefits of interlocking, increased adhesion / bonding strength of the non-linear interface 104, and improved toughness of the multi-phase second interface 105 that are characteristic of the single multi-layer sintered ceramic body disclosed herein.

[0193] Disclosed herein is a multilayer sintered ceramic body including at least one first layer 100 and at least one second layer 102, which are continuous and bounded by a nonlinear interface 104, as shown in the schematic diagrams of FIG. 22a) and b). Also shown in FIG. 22a) and b) is a nonlinear interface 105 between adjacent layers 102 and 103. As shown, the nonlinear interface 104 (as described in more detail herein) can provide improved adhesion between the at least one first layer 100 and the at least one second layer 102. This improved adhesion can be achieved by several factors, including an increase in the interfacial length and associated increase in the interfacial area, the tortuosity (T), the arithmetic mean of the interface (the distance of the interface from the mean interface line), the nonlinearity, and the interlocking effect provided by the morphology of the interface 104.

[0194] The interface of the layers typically has a tortuous and non-linear interface such that the interface layer usually meanders between at least one first layer and the second layer, and between at least one second layer and the third layer. The tortuous degree using the calculations disclosed herein can be 1.2 to 2.2, particularly 1.4 to 2.0. The measurement for determining the tortuous degree is described below and is based on the increase in interface length relative to the linear distance of the interface layer. Thus, disclosed herein is a multilayer sintered ceramic body defined by at least one second layer and at least one first layer, having an interface between at least one second layer and at least one third layer, wherein the interface length is increased by 20 to 70%, preferably 20 to 60%, preferably 20 to 40%, preferably 30 to 80%, preferably 40 to 80%, preferably 50 to 70%.

[0195] Correspondingly, the at least one second layer and the at least one first layer, and the at least one third layer and the at least one second layer, may contact each other at an interface having an interfacial area commensurate with the maximum dimension of the multilayer sintered ceramic body along the interface layer.

[0196] In the case of a single multi-layer sintered body having a maximum dimension of 100 to about 625 mm, taking into account the above-mentioned bending degree of at least 1.2, at least one second layer and at least one first layer have a bending length of at least 113 cm. 2 , preferably at least 452 cm 2 , preferably at least 1,018 cm 2 , preferably at least 1,810 cm 2 They contact each other at a nonlinear interface with an area of

[0197] In the case of a single multi-layer sintered body having a maximum dimension of 100 to about 625 mm, taking into account the above-mentioned bending degree of at least 1.4, at least one second layer and at least one first layer have a bending length of at least 153 cm. 2 , preferably at least 616 cm 2 , preferably at least 1,386 cm 2 , preferably at least 2,464 cm 2They contact each other at a nonlinear interface with an area of

[0198] In the case of a single multi-layer sintered body having a maximum dimension of 100 to about 625 mm, taking into account the above-mentioned bending degree of up to 2.2, at least one second layer and at least one first layer have a maximum bending length of 15,085 cm 2 , preferably up to 14,850 cm 2 , preferably up to 14,128 cm 2 , preferably up to 9,802 cm 2 , preferably up to 6,083 cm 2 , preferably up to 3,421 cm 2 , preferably up to 1,520 cm 2 They contact each other at a nonlinear interface with an area of

[0199] In the case of a single multi-layer sintered body having a maximum dimension of 100 to about 625 mm, taking into account the above-mentioned bending degree of up to 2.0, at least one second layer and at least one first layer have a maximum bending length of 12,468 cm 2 , preferably up to 12,272 cm 2 , preferably up to 11,676 cm 2 , preferably up to 7,852 cm 2 , preferably up to 5,028 cm 2 , preferably up to 2,828 cm 2 , preferably up to 1,256 cm 2 They contact each other at a nonlinear interface with an area of

[0200] In the case of a single multi-layer sintered body having a maximum dimension of 100 to about 625 mm, taking into account the above-mentioned bending degree of at least 1.2, at least one second layer and at least one first layer have a maximum dimension of 113 to about 4,488 cm 2 , preferably 113 to about 4,418 cm 2 , preferably 113 to 4,204 cm 2 , preferably 113 to 2,827 cm 2 , preferably 113 to 1,918 cm 2 , preferably 113 to 1,018 cm 2 , preferably 113 to 452 cm 2, preferably 452 to about 4,488 cm 2 , preferably 452 to about 4,418 cm 2 , preferably 452 to 4,203 cm 2 , preferably 452 to 2,827 cm 2 , preferably 452 to 1,810 cm 2 , preferably 1,018 to about 4,418 cm 2 , preferably 1,810 to 4,376 cm 2 They contact each other at a nonlinear interface with an area of

[0201] In the case of a single multi-layer sintered body having a maximum dimension of 100 to about 625 mm, taking into account the above-mentioned bending degree of at least 1.4, at least one second layer and at least one first layer have a maximum dimension of 153 to about 6,110 cm 2 , preferably 153 to about 6,013 cm 2 , preferably 153 to 5,722 cm 2 , preferably 153 to 3,847 cm 2 , preferably 153 to 2,464 cm 2 , preferably 153 to 1,386 cm 2 , preferably 153 to 616 cm 2 , preferably 616 to about 6,110 cm 2 , preferably 616 to about 6,013 cm 2 , preferably 616 to 5,722 cm 2 , preferably 616 to 3,847 cm 2 , preferably 616 to 2,464 cm 2 , preferably 1,386 to about 6,013 cm 2 , preferably 2,464 to 5,957 cm 2 They contact each other at a nonlinear interface with an area of

[0202] In the case of a single multi-layer sintered body having a maximum dimension of 100 to about 625 mm, taking into account the above-mentioned bending degree of up to 2.2, at least one second layer and at least one first layer have a bending length of 378 to about 15,085 cm 2 , preferably 378 to about 14,850 cm 2 , preferably 378 to 14,128 cm 2, preferably 378 to 9,502 cm 2 , preferably 378 to 6,083 cm 2 , preferably 378 to 3,421 cm 2 , preferably 378 to 1,520 cm 2 , preferably 1,520 to about 15,085 cm 2 , preferably 1,520 to about 14,850 cm 2 , preferably 1,520 to 14,128 cm 2 , preferably 1,520 to 9,502 cm 2 , preferably 1,1520 to 6,083 cm 2 , preferably 3,421 to about 14,850 cm 2 , preferably 6,083 to 14,710 cm 2 They contact each other at a nonlinear interface with an area of

[0203] In the case of a single multi-layer sintered body having a maximum dimension of 100 to about 625 mm, taking into account the above-mentioned bending degree of up to 2.0, at least one second layer and at least one first layer have a bending length of 312 to about 12,468 cm 2 , preferably 312 to about 12,272 cm 2 , preferably 312 to 11,676 cm 2 , preferably 312 to 7,852 cm 2 , preferably 312 to 5,028 cm 2 , preferably 312 to 2,828 cm 2 , preferably 312 to 1,256 cm 2 , preferably 1,256 to about 12,468 cm 2 , preferably 1,256 to about 12,272 cm 2 , preferably 1,256 to 11,676 cm 2 , preferably 1,256 to 7,652 cm 2 , preferably 1,256 to 5,028 cm 2 , preferably 2,828 to about 12,272 cm 2 , preferably 5,028 to 7,294 cm 2 They contact each other at a nonlinear interface with an area of

[0204] 24a) and 24b) show SEM images characterizing the interface 104 between at least one first layer 100 and at least one second layer 102, and as shown in the exemplary image in 24b), the linear distance between the ends (L) is about 54 μm, and the interface length or curvature (C) measured along the interface 104 is about 90 μm. The tortuosity according to 24b) using the calculations disclosed herein is about 1.7. Measurements were made across nine SEM images using ImageJ software analysis as disclosed herein. An average interface length of about 90 μm was measured, indicating an increase of about 66% in interface length (C) relative to linear distance (L). Accordingly, disclosed herein is a multi-layer sintered ceramic body having an interface 104 defined by at least one second layer and at least one first layer, where the interface length is increased by 20-70%, preferably 20-60%, preferably 20-40%, preferably 30-80%, preferably 40-80%, preferably 50-70%. Correspondingly, the at least one second layer 102 and the at least one first layer 100 may contact each other at an interface that has an interface area commensurate with the maximum dimension of the multi-layer sintered ceramic body. In some embodiments, for a single multi-layer sintered body having a maximum dimension of 100 to about 625 mm, the at least one second layer 102 and the at least one first layer 100 may contact each other at an interface that has an interface area commensurate with the maximum dimension of the multi-layer sintered ceramic body. 2 , preferably about 3,068 cm 2 Below 2,919cm, preferably 2 Preferably, 78 to about 3,117 cm 2 , preferably 78 to about 3,068 cm 2 , preferably 78 to 2,919 cm 2 , preferably 78 to 1,963 cm 2 , preferably 78 to 1,257 cm 2 , preferably 78 to 707 cm 2 , preferably 78 to 314 cm 2 , preferably 314 to about 3,117 cm 2 , preferably 314 to about 3,068 cm 2 , preferably 314 to 2,919 cm 2 , preferably 314 to 1,963 cm2 , preferably 314 to 1,257 cm 2 , preferably 707 to about 3,068 cm 2 , preferably 1257 to 3,039 cm 2 The first and second layers contact each other at a nonlinear interface 104 having an area of ​​100 mm to 150 mm. In embodiments, the first and second layers are in direct contact to form the nonlinear interface 104, and thus it is preferred that at least one of the first and second layers are adjacent layers. In other embodiments, circuitry, heating elements, RF coils / antennas, etc. may be disposed between the first and second layers as required by the particular component application, and regardless of these features, at least a portion of the first and second layers may be adjacent or substantially adjacent. This increased interfacial length and interfacial area enhances adhesion at the nonlinear interface 104 between the at least one first layer 100 and the at least one second layer 102.

[0205] Referring again to FIG. 24b), the width of the illustrated interface layer is typically 1-200 μm, in particular 5-100 μm, more particularly 10-50 μm, and even more particularly 20-30 μm.

[0206] The volume of the first layer across the width of said interface layer has pores with a maximum size of less than 5 μm, in particular less than 3 μm, in particular less than 1 μm.

[0207] The volume of the first layer across the width of said interface layer in particular has only pores having a maximum size of less than 5 μm, in particular less than 3 μm, in particular less than 1 μm.

[0208] At least the volume of the first layer within the width disclosed herein has a structure in which less than 0.2% of the volume is occupied by the above-mentioned pores, more preferably less than 0.15%, and most preferably less than 0.1%.

[0209] The volume of the second layer across the width of said interface layer has pores with a maximum size of less than 5 μm, in particular less than 3 μm, in particular less than 1 μm.

[0210] The volume of the second layer across the width of said interface layer in particular has only pores having a maximum size of less than 5 μm, in particular less than 3 μm, in particular less than 1 μm.

[0211] The volume of at least the second layer within the width disclosed herein has a structure in which less than 0.2% of the volume is occupied by the above-mentioned pores, more preferably less than 0.15%, and most preferably less than 0.1%.

[0212] FIG. 23a) shows a SEM micrograph at 500x of a multi-layer sintered ceramic body, where the non-linear interface 104 defined by at least one second layer 102 and at least one first layer 100 is an irregular non-linear boundary, which in embodiments may include a retrograde angle. In some embodiments, as shown in FIG. 23a), the interface may include at least one dovetail structure and / or at least a portion of a dovetail structure. In other embodiments, at least a portion of the interface may include a trapezoidal shape. The tortuosity (T) disclosed herein is mathematically defined as the ratio of the length C of the curve (interface) to the linear distance L between its ends, T=C / L. The image in FIG. 23a) was measured to have a tortuosity of 2.7. The nonlinear interface 104 disclosed herein may have a tortuosity T of greater than 1.02 to about 1.5, preferably greater than 1.02 to about 2.0, preferably greater than 1.02 to about 2.5, preferably greater than 1.02 to about 3.0, preferably greater than 1.1 to about 3.0, preferably 1.3 to about 3, preferably 1.5 to about 2.7, as measured using SEM and image processing methods (measurement within ImageJ software) disclosed herein.

[0213] Straight interfaces (typical of laminates and structures using pre-sintered bodies to which layers are applied) have a degree of tortuosity of about 1 to 1.02. The increased tortuosity of the interfaces 104 of the multi-layer bodies disclosed herein provides an interlocking effect between the layers, thereby increasing the bond strength such that an inseparable single multi-layer sintered ceramic body is formed.

[0214] FIG. 23b) shows the average interface line (IL) of the nonlinear interface 104 calculated from SEM and image processing methods. The exemplary SEM image of FIG. 23b) showing the nonlinear interface 104 was imported into ImageJ software and the x / y coordinates corresponding to the points along the interface were used to obtain a linear equation for the average interface line (IL) as shown in FIG. 23b), and the nonlinear interface 104 was characterized by the distance of the nonlinear interface 104 from the average interface line (IL). The distance (D) of the interface 104 from the average interface line (IL) varies in an amount of 10-100 μm, preferably 20-100 μm, preferably 30-100 μm, preferably 40-100 μm, 50-100 μm, preferably 25-85 μm, as measured using SEM and image processing. The increase in the distance (D) from the average interface line (IL) may contribute to the improved adhesion and interlocking effect of the multilayer sintered ceramic body disclosed herein.

[0215] These reverse or retrograde angles, properties, and structures can provide an anchoring effect, thereby increasing the interfacial and tensile strength and bonding across the interface 104 defined by the at least one second layer 102 and the at least one first layer 100.

[0216] In comparison, FIG. 5 shows the interface of a prior art sample where layer or substrate B is first sintered to form a solid, and then layer D is deposited on top of substrate B, and the two are bonded over time, temperature, and pressure. A substantially linear interface with no retrograde or interface angle and minimal or no increase in interface length is evident. Tortuosity measurements were calculated as disclosed herein (using images such as those shown in FIG. 5), whereby the length (C) of the curve (interface) and the linear distance L between its ends were measured from SEM images imported into ImageJ image processing software as disclosed herein. The tortuosity (T) of the prior art laminate was calculated to be less than about 1.02. Thus, the interface of the multilayer embodiment known in the art does not provide the beneficial features of the improved interlayer adhesion and interlocking effect of the subject single multilayer sintered ceramic body disclosed herein. The bright areas shown in FIG. 5 (center-right area of ​​the image) correspond to the metal layers.

[0217] As shown in the prior art laminate of FIG. 5, there is significant grain size variation between layers B and D. Layer B has large grains on the order of 20-30 μm, which may indicate an extensive thermal history, such as multiple sintering processes. Layer D has grains on the order of 2-5 μm, indicating much less grain growth typically caused by thermal history and sintering. This grain size difference may indicate a lamination or deposition process where layer D is deposited or stacked on top of layer B and subsequently sintered to form the laminate or stack.

[0218] The high density required for layer B (to impart mechanical strength, high Young's modulus, and other properties) requires long sintering times and high temperatures, thus resulting in excessive grain growth. Layer D is then bonded to substrate B at a lower temperature and for a shorter duration, so that layer D does not have to experience the excessive grain growth of substrate B. This results in a layered structure with a significant difference in grain size. The grain sizes were measured (using the Heyn Line Intercept method known to those skilled in the art) and grain sizes of about 12 μm and 4 μm were measured for substrate B and layer D, respectively. This grain size difference can lead to variations in properties (such as mechanical strength, Young's modulus, dielectric loss, and other properties) between the two bodies, which can result in fractures and / or cracks.

[0219] In contrast, grain size measurements were performed on a multi-layer sintered ceramic body of one embodiment including at least one first layer including YAG and at least one second layer including alumina, where the alumina comprises at least one of stabilized zirconia and partially stabilized zirconia present in an amount of about 16 volume percent. The grain sizes of the at least one YAG first layer and the at least one second layer were measured to be about 0.78 μm and 0.74 μm, respectively. These differences may be within the measurement accuracy, and thus the multi-layer sintered ceramic body disclosed herein may include at least one first and second layer including grains, the grains having the same size or substantially the same size between the at least one first layer 100 and the second layer 102.

[0220] The number of grains in contact across the interface may also play a role in the adhesion and strength properties of the nonlinear interface 104. The number of grains was counted across the interface length to obtain the number of grains per micron. FIG. 25a) shows the number of grains per interface length (in microns) of the interface defined by at least one first layer 100 and at least one second layer 102 over 10 images, with fewer grains per micron being preferred. In an embodiment, for a multilayer sintered ceramic body including YAG as at least one first layer 100 and a second layer of about 16 volume % zirconia in an alumina matrix, the average number of grains per micron, preferably about 0.5, includes 0.2-0.8 grains / μm, preferably 0.3-0.6 grains / μm, preferably 0.4-0.55 grains / μm. FIG. 25b) shows the ratio of interface length (C, also defined as curve / interface length) to linear measurement L (linear distance between the endpoints of C, defined herein as tortuosity T) over the disclosed image area of ​​about 54 μm over 10 SEM images. The non-linear interface 104 may have a tortuosity (T) of greater than 1.02-3, preferably 1.1-3, preferably 1.2-3, preferably 1.3-3, preferably 1.3-2.7, preferably an average tortuosity of about 1.7 measured using SEM and image processing methods. A higher ratio of interface length C to linear interface length L (or tortuosity T) is preferred to increase the adhesive strength between at least one first layer 100 and second layer 102.

[0221] As described, the nonlinear interface 104 may provide improved adhesion strength between the at least one first layer 100 and the at least one second layer 102. This improved adhesion strength may be achieved by an interlocking effect as measured by an increased interface length, an increased distance from the interface line, and a degree of tortuosity T between the at least one first layer 100 and the at least one second layer 102.

[0222] Referring now to Figures 26a) and b), SEM micrographs of the microstructure of the at least one third layer 103 are shown. In an embodiment, the at least one third layer 103 includes multiple phases of ceramic material including YAG, alumina, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia. The multiphase structure of the at least one third layer 103 may provide a strengthening effect due to the interface between at least two phases, which may promote preferential crack propagation along an increased distance of the interface. Large areas including YAG and ZTA (zirconia-toughened alumina) are shown in Figures 26a) and b), each comprising about 50% by area as measured using SEM images and ImageJ software.

[0223] A CTE match within the disclosed range between the at least one first, second and third layer is preferably provided over a temperature range from ambient temperature (or at least 200° C. as shown in the figure) to about 1700° C. (or at least 1400° C. as shown in the figure) in accordance with the temperature range of the method disclosed herein. Selection of materials for each of the at least one first, second and third layers that provide the disclosed CTE difference can reduce interfacial stresses on the nonlinear interface 104 and second interface 105, thereby improving adhesion and strength between the at least one first layer 100 and the at least one second layer 102 and the at least one third layer 103.

[0224] To form plasma processing chamber components from the disclosed multi-layer sintered ceramic bodies, the multi-layer sintered ceramic bodies may be machined, drilled, surface-ground, lapped, polished, and other processes as necessary to form them into multi-layer sintered parts with the required through holes, surface finish, and dimensional tolerances, depending on the component design, as shown diagrammatically in FIG. 27. FIG. 27 illustrates an exemplary embodiment of a multi-layer sintered ceramic body and a multi-layer sintered ceramic component manufactured therefrom. Through holes 112 may be created through at least one first layer 100, at least one second layer 102, and at least one third layer 103 by any number of machining, grinding, and / or drilling processes as known to those skilled in the art. Multi-layer sintered ceramic parts formed from the sintered bodies disclosed herein may have any number of through holes 112. As shown in Fig. 27a), b) and c), the through hole 112 can have a sidewall 110, the sidewall 110 comprising at least a portion of a crystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconia, the zirconia being present in an amount of 10 mol% to 25 mol%. In some embodiments, the thickness of the at least one second layer 102 is maximized and the thickness of the at least one first layer 100 and / or the at least one third layer 103 is minimized, each in the range of about 0.5-3 mm, preferably 0.5-1.5 mm. Maximizing the thickness of the at least one second layer 102 provides corrosion resistance and machinability in combination with the preferred properties of high mechanical strength, high thermal conductivity, high dielectric constant and low dielectric loss. The at least one second layer 102 fabricated within the disclosed composition ranges can provide the aforementioned preferred properties required for high frequency chamber applications. The combination of high strength, corrosion resistance, low dielectric loss and thermal conductivity of the multi-layer sintered ceramic body disclosed herein makes the multi-layer sintered ceramic body 98 particularly well suited as a material for the manufacture of dielectric or RF windows and many other components for use in semiconductor plasma processing chambers.These include windows, lids, dielectric windows, RF windows, rings, focus rings, process rings, deposition rings, nozzles, injectors, gas injectors, showerheads, gas distribution plates, diffusers, ion suppressor elements, chucks, electrostatic wafer chucks (ESCs), and pucks.

[0225] However, these necessary grinding and polishing processes always create defects such as cracks and / or microcracks (cracks that are not easily visible to the eye) or subsurface defects in the sintered ceramic components. It is preferable that the creation of surface and / or subsurface defects during machining is minimized in order to minimize particle emission from the plasma-facing surface 106 of the at least one first layer 100 into the chamber as shown in FIG. 6. These surface and / or subsurface defects may cause microcracks on the plasma-facing surface 106 of the first layer 100 at a scale that is not easily visibly evident, which may then lead to the subsequent emission of particles from the plasma-facing surface 106 of the at least one first layer 100 into the plasma processing chamber. Additionally, the presence of larger scale defects in the second layer 102 may result in the fracture of the sintered body at a strength lower than the typical strength of the material, according to the interrelationship between the type of material itself (in this case a brittle non-metallic ceramic), the flaw or defect size (resulting from machining), and the applied stress (residual from processing and / or due to CTE differences between the layers and / or arising during use as a sintered ceramic component). This relationship between material, flaw size and stress follows the fracture mechanics reported by the AAGriffith in "The phenomena of rupture and flow in solids" Phil. Trans. Roy. Soc. London, Volume 221, Issue 582-593, 01 January 1921.

[0226] Residual stresses remaining in the sintered body can result from differences in CTE between layers that may appear during the heating, sintering, annealing, and cooling steps to form the multi-layer sintered ceramic body herein. Thus, it is preferable to minimize these internal stresses caused by differences in the CTE of the subject materials by providing those materials as layers that are CTE-matched (within the ranges disclosed) over the temperature range from ambient temperature to the sintering and annealing temperatures disclosed herein, from ambient temperature (or at least 200° C. as shown in the figures) to about 1700° C. (or at least about 1400° C. as shown in the figures).

[0227] The difference in CTE between any of the at least one first layer 100, the at least one second layer 102, and / or the at least one third layer 103 of the multilayer sintered ceramic body is 0.75×10 -6 If the CTE difference is greater than 1 / °C, then during the machining or drilling process, greater stress resulting from the CTE mismatch may be exerted on the at least one first layer, which may result in surface or subsurface damage in the form of microcracks in the at least one first layer 100. This damage to the at least one first layer may result in increased spalling and / or erosion of the layer, which may then result in the emission of particles from the plasma-facing surface 106 into the plasma processing chamber during use. As a result, to form a multi-layer sintered ceramic body having high strength, sufficient handleability, and minimal surface damage to the at least one first layer due to machining, the CTE difference between the at least one first layer 100, the at least one second layer 102, and the at least one third layer 103 of the multi-layer sintered ceramic body is preferably within the disclosed ranges, and preferably the CTEs are matched as closely as possible, including a value of 0, where substantially no difference in CTE was measured, over a temperature range from ambient temperature (or about 200°C as shown in the figure) to about 1700°C, according to the disclosed method. As used herein, the term "CTE match" refers to a CTE value (absolute value) of 0 to 0.75×10 over the temperature range from ambient temperature to the sintering temperature of about 1700° C. or less. -6It refers to a combination of at least one first layer 100, at least one third layer 103, and at least one second layer 102, differing only in the following:

[0228] Accordingly, in an embodiment, the absolute value of the coefficient of thermal expansion (CTE) of the first, second and third layers is less than about 0-0.75×10 / °C, preferably 0-0.7×10 / °C, as measured according to ASTM E228-17, over a temperature range of 25-1700°C, or over a temperature range of 200-1400°C. -6 / °C, preferably 0 to 0.6 × 10 -6 / °C, preferably 0 to 0.5 × 10 -6 / °C, preferably 0 to 0.45 × 10 -6 / °C, preferably 0 to 0.4 × 10 -6 / °C, preferably 0 to 0.35 × 10 -6 / °C, preferably 0 to 0.3 × 10 -6 / °C, preferably 0 to 0.25 × 10 -6 / °C, preferably 0 to 0.2 × 10 -6 / °C, preferably 0 to 0.15 × 10 -6 / °C, preferably 0 to 0.1 × 10 -6 / °C, preferably 0 to 0.08 × 10 -6 / °C, preferably 0 to 0.06×10 -6 / °C, preferably 0 to 0.04 × 10 -6 / °C, preferably 0 to 0.02 × 10 -6 / °C, preferably 0 to 0.01 × 10 -6 It is preferred that the materials selected for the first, second and third layers differ by an amount of .mu.m / .degree.C.

[0229] In embodiments where the CTE of each of the first, second and third layers does not cross over one another over the disclosed temperature range (i.e., the absolute value of the difference in CTE is not 0 over the temperature range), the absolute value of the coefficient of thermal expansion (CTE) of the first, second and third layers is less than about 0.003×10 over a temperature range of 25 to 1700° C., or over a temperature range of 200 to 1400° C., as measured according to ASTM E228-17. -6 / ℃~0.75×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.7×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.6×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.5×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.45×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.4×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.35×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.3×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.25×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.2×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.15×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.1×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.08×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.06×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.04×10 -6 / °C, preferably 0.003 x 10 -6 / ℃~0.02×10 -6 , preferably 0.003 x 10 -6 / ℃~0.01×10 -6 / °C.

[0230] The disclosed ranges of absolute values ​​of the difference in the coefficients of thermal expansion between at least one of the first, second and third layers are preferably maintained over a temperature range according to the methods disclosed herein. The desired ranges of absolute values ​​of the difference in the coefficients of thermal expansion between the first, second and third layers are preferably maintained over a temperature range from ambient temperature (or at least 200°C as shown in the figures) to about 1700°C (or at least about 1400°C as shown in the figures), preferably over a temperature range of 200°C-1400°C, preferably over a sintering temperature range of 1000°C-1700°C and / or an annealing temperature range of 900°C-1800°C.

[0231] Use of the CTE-matched multilayer sintered ceramic bodies disclosed herein can reduce stress on the at least one first layer 100 (and thereby the potential for particle generation in a plasma processing chamber) and improve machinability (by reducing subsurface and / or surface damage) by providing at least one third layer 103 with a symmetrically balanced matching CTE on either side of the at least one second layer 102. Additionally, the composition of the at least one second layer 102 may be selected to be CTE-matched to the at least one first layer 100 and / or the at least one third layer 103 within the disclosed ranges.

[0232] This reduced stress between and within the layers can reduce the effects of surface and subsurface damage during machining, thereby reducing particle generation from the plasma-facing surface 106 of the at least one first layer 100, while improving the overall strength and machinability of the multilayer sintered ceramic bodies (and components produced therefrom) disclosed herein.

[0233] When the absolute value of the CTE between any of the layers varies within these ranges, multi-layer sintered ceramic bodies, especially those of large (>100 mm) dimensions, having high strength with improved machinability, reduced surface and subsurface defects can be formed using the pressure-assisted methods disclosed herein.

[0234] Equipment / Spark Plasma Sintering Tools The apparatus for preparing the multilayer sintered ceramic body disclosed herein preferably comprises a die including a sidewall, the sidewall including an inner wall and an outer wall, the inner wall having a diameter defining an interior volume capable of receiving at least one ceramic powder (or at least one powder mixture, as the case may be); and an upper punch and a lower punch operatively connected to the die, each of the upper punch and the lower punch having an outer wall defining a diameter smaller than the diameter of the inner wall of the die, whereby when at least one of the upper punch and the lower punch is moved within the interior volume of the die, a gap is generated between each of the upper punch and the lower punch and the inner wall of the die, the gap being between 10 μm and 100 μm wide, and the at least one powder mixture is moved within the interior volume of the die, the gap being between 10 μm and 100 μm wide, the gap being between 10 μm and 100 μm wide, as measured in accordance with ASTM C1274. 2 and an upper punch and a lower punch having a specific surface area (SSA) of 100 / g.

[0235] As shown in FIG. 28, the pressure-assisted sintering process disclosed herein (and in a preferred embodiment, pressure and current assisted sintering processes such as SPS) provides for the preparation of a single multi-layer sintered ceramic body 98 from at least three layers of a powder mixture arranged in a tool set (powder compact) without the use of dopants and / or sintering aids. The single multi-layer sintered body 98 is formed (after in-situ sintering) from layers of powder mixture (shown in FIG. 28 as 100a corresponding to at least one first layer 100, 102a corresponding to at least one second layer 102, and 103a corresponding to at least one third layer 103 (thus forming a powder compact)), which are then formed into at least one first layer 100, second layer 102, and third layer 103 of the sintered body, respectively (without the formation of a film, tape, or green body as is common in the art). In some embodiments, the order of arrangement of the at least one first and third powder mixture may be reversed. In embodiments, at least one of the powder mixtures may be sintered, while in other embodiments, all of the powder mixtures may be sintered. In contrast to Figures 1 and 2, the pressure-assisted method produces a single, dense, multi-layer sintered ceramic body without the need to adapt the sintering rate of the pressureless method as known to those skilled in the art. The absolute value of the CTE difference between at least one first layer 100, second layer 102, and third layer 103 of the multi-layer sintered body is preferably within the ranges disclosed herein to avoid cracks and fractures resulting from CTE mismatches outside the disclosed ranges (which may be experienced during sintering and other thermal excursions such as annealing), as shown in Figure 4.

[0236] Figure 29 shows an SPS tool 1 with a simplified die / punch arrangement used to sinter ceramic powders and / or powder mixtures. Typically, the die / punch arrangement is within a vacuum chamber (not shown) as will be appreciated by those skilled in the art. With reference to Figure 29, the spark plasma sintering tool 1 comprises a die system 2 having a sidewall including an inner wall 8 having a diameter defining an interior volume capable of receiving a ceramic powder or powder mixture 5.

[0237] With further reference to FIG. 29 , the spark plasma sintering tool 1 comprises an upper punch 4 and a lower punch 4′ operably coupled to a die system 2, each of the upper punch 4 and the lower punch 4′ having an outer wall 11 defining a diameter smaller than the diameter of the inner wall 8 of the die system 2, thereby forming a gap 3 between each of the upper punch 4 and the lower punch 4′ and the inner wall 8 of the die system 2 when at least one of the upper punch 4 and the lower punch 4′ moves within the interior volume of the die system 2.

[0238] The die system 2 and the upper and lower punches 4 and 4' may comprise at least one graphite material. In certain embodiments, the graphite materials disclosed herein may comprise at least one isotropic graphite material. In other embodiments, the graphite materials disclosed herein may comprise at least one reinforced graphite material, such as, for example, a carbon-carbon composite, and a graphite material comprising fibers, particles, or sheets or meshes, or laminates of other conductive materials, such as carbon, in a matrix of an isotropic graphite material. In other embodiments, the die and the upper and lower punches comprise a combination of these isotropic and reinforced graphite materials.

[0239] For example, the graphite material used in some or all of the tool components, such as the die 6 and punches 4 and 4', may comprise a porous graphite material that exhibits a porosity of about 5% to about 20%, about 5% to about 17%, about 5% to about 13%, about 5% to about 10%, about 5% to about 8%, about 8% to about 20%, about 12% to about 20%, about 15% to about 20%, about 11% to about 20%, about 5% to 15%, 6% to about 13%, and preferably about 7% to about 12%.

[0240] Preferably, the graphite material has an average pore size (pore diameter) of 0.4 to 5.0 μm, preferably 1.0 to 4.0 μm, and contains pores with a surface pore size of at most 30 μm, preferably at most 20 μm, preferably at most 10 μm. More preferably, pores with a surface pore size of 10 to 30 μm may be present.

[0241] The graphite material used in the tools disclosed herein may have an average grain size of <0.05mm, preferably <0.04mm, preferably <0.03mm, preferably <0.028mm, preferably <0.025mm, preferably <0.02mm, preferably <0.018mm, preferably <0.015mm, preferably <0.010mm.

[0242] The graphite material used in the tools disclosed herein may have an average grain size of >0.001mm, preferably >0.003mm, preferably >0.006mm, preferably >0.008mm, preferably >0.010mm, preferably >0.012mm, preferably >0.014mm, preferably >0.020mm, preferably >0.025mm, preferably >0.030mm.

[0243] The graphite material used in the tools disclosed herein has a hardness of ≧1.45 g / cm 3 , preferably ≧1.50 g / cm 3 , preferably ≧1.55 g / cm 3 , preferably ≧1.60 g / cm 3 , preferably ≧1.65 g / cm 3 , preferably ≧1.70 g / cm 3 , preferably ≧1.75 g / cm 3 The density of the sintered body may be 0.01 to 0.01.

[0244] The graphite material used in the tools disclosed herein has a hardness of <2.0 g / cm 3 , preferably 1.90 g / cm 3 , preferably <1.85g / cm 3 , preferably <1.80 g / cm 3 The density of the sintered body may be 0.01 to 0.01.

[0245] In an embodiment, the graphite material has a molecular weight of ≧3.3×10 -6 / ℃, ≥3.5×10 -6 / ℃, ≥3.7×10 -6 / ℃, ≥ 4.0×10 -6 / ℃, ≥4.2×10 -6 / ℃, ≥4.4×10-6 / ℃, ≥4.6×10 -6 / ℃, ≥4.8×10 -6 / °C over the temperature range of about 400 to about 1400°C.

[0246] In an embodiment, the graphite material has a melting point of <7.2×10 -6 / °C, preferably <7.0 x 10 -6 / °C, preferably <6.0 x 10 -6 / °C, preferably <5.0 x 10 -6 / °C, preferably <4.8 x 10 -6 / °C, preferably <4.6 x 10 -6 The material may have a coefficient of thermal expansion (CTE) of 100 / °C over a temperature range of about 400 to 1400°C.

[0247] Table 9 lists the properties of exemplary graphite materials disclosed herein.

[0248] [Table 9]

[0249] As illustrated in the embodiment of Figures 25a)-25c), the die system 2 includes a die 6 and, optionally, but preferably, at least one conductive foil 7 located on an inner wall of the die. There is no limit to the number of conductive foils on the inner wall of the die, and 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 conductive foils may be provided as circumferential liners between the die 6 and each of the upper and lower punches 4, 4', such that the inner wall 8 of the die system 2 (including at least one conductive foil, if present) and the outer wall 11 of each of the upper and lower punches define the gap 3. The at least one conductive foil 7 includes graphite, niobium, nickel, molybdenum, platinum, and other ductile, conductive materials and combinations thereof that are stable within the temperature range according to the methods disclosed herein.

[0250] In certain embodiments, the conductive foil may comprise a flexible and compressible graphite foil as disclosed herein, having the following properties: a carbon content of more than 99 wt%, preferably more than 99.2 wt%, more preferably more than 99.4 wt%, more preferably more than 99.6 wt%, more preferably more than 99.8 wt%, more preferably more than 99.9 wt%, more preferably more than 99.9 wt%, more preferably more than 99.99 wt%, more preferably more than 99.999 wt%; impurities less than 500 ppm, preferably less than 400 ppm, more preferably less than 300 ppm, more preferably less than 200 ppm, more preferably less than 100 ppm, more preferably less than 50 ppm, more preferably less than 10 ppm, more preferably less than 5 ppm, more preferably less than 3 ppm; a tensile strength of the graphite foil in the range of 4.0-6.0 MPa, preferably 4.2-5.8 MPa, more preferably 4.4 or 5.6 MPa; and / or Bulk density of the graphite foil preferably within the range of 1.0-1.2 g / cc, preferably 1.02-1.18 g / cc, more preferably 1.04-1.16 g / cc, more preferably 1.06-1.16 g / cc.

[0251] In embodiments, the at least one foil typically comprises graphite. In certain embodiments, the at least one foil as part of the die system may include a circumferential liner between a surface of the die and each of the upper and lower punches.

[0252] The graphite foil can improve temperature distribution throughout the powder during sintering. Table 10 lists properties of exemplary graphite foils according to embodiments disclosed herein.

[0253] [Table 10]

[0254] Referring now to Fig. 30a), Fig. 25b and Fig. 30c, an SPS tool set with an embodiment of a graphite foil arrangement is shown. At least one ceramic powder (or powder mixture) 5 is placed between at least one of the upper punch 4 and the lower punch 4', and a gap 3 is shown between the outer wall 11 of each of the upper and lower punches and the inner wall 8 of the die system 2. Fig. 30a), Fig. 30b and Fig. 30c respectively show 1-3 layers of conductive foil 7 and a die 6 as part of the die system 2. Thus, the gap extends from the inner wall 8 of the die system 2 to the outer wall 11 of each of the upper and lower punches. The gap spacing is arranged to allow degassing of the powder before and / or during heating and sintering, while also maintaining ohmic contact between the punch and die to improve temperature distribution throughout the ceramic powder or powder mixture during heating and sintering.

[0255] The graphite foil 7 may have a thickness of, for example, 0.025 to 0.260 mm, preferably 0.025 to 0.200 mm, preferably 0.025 to 0.175 mm, preferably 0.025 to 0.150 mm, preferably 0.025 to 0.125 mm, preferably 0.035 to 0.200 mm, preferably 0.045 to 0.200 mm, preferably 0.055 to 0.200 mm.

[0256] The spacing of the gap 3 is measured from the inwardly facing surface of the foil 7 closest to the upper punch 4 and the lower punch 4' to the outer wall of the outer wall 11 of each of the upper and lower punches. A preferred range for the spacing of the gap 3 is preferably 10-100 μm, preferably 10-70 μm, preferably 10-60 μm, preferably 10-50 μm, preferably 30-70 μm, preferably 20-60 μm, preferably 30-60 μm.

[0257] Furthermore, the width of the gap 3 between the inner wall 8 of the die system 2 and the outer wall 11 of each of the upper and lower punches 4 and 4' can be determined by the skilled person so that, on the one hand, the degassing of the powder during the preheating, heating and sintering process is sufficiently easy, and, on the other hand, sufficient electrical contact is obtained for Joule or resistive heating to perform sintering. If the gap 3 is spaced less than 10 μm apart, the forces required to move at least one of the upper and lower punches in the internal volume of the die system and thus assemble the tool set may cause damage to the tool set. Furthermore, a gap 3 less than 10 μm may not allow gases, organics, moisture, etc. adsorbed in the powder 5 to escape, thereby extending the process time during production and reducing the density of the resulting sintered ceramic body by leaving residual porosity. If the width of the gap 3 is more than 70 μm when sintering the ceramic powder or powder mixture, local overheating may occur and thermal gradients may occur in the tool set during sintering. As a result, for forming multi-layer sintered ceramic bodies (such as those disclosed herein) of large dimensions (up to about 625 mm in maximum dimension), a gap of 10-100 μm is preferred. Thus, in some embodiments, the spacing of the gap 3 between the inner wall 8 of the die system 2 and the outer wall 11 of each of the upper and lower punches when sintering the ceramic powder or powder mixture is preferably 10-100 μm, preferably 10-70 μm, preferably 10-60 μm, preferably 10-50 μm, preferably 10-40 μm, preferably 20-70 μm, preferably 30-70 μm, preferably 40-70 μm, preferably 50-70 μm, preferably 30-60 μm.

[0258] These thermal gradients can result in low overall bulk density or high density deviations, as well as sintered ceramic bodies that are fragile and prone to breakage. As a result, the spacing of the gap 3 between the inner wall 8 of the die system 2 and the outer wall 11 of each of the upper and lower punches when sintering a ceramic powder or powder mixture as disclosed herein is 10-100 μm, preferably 10-70 μm, preferably 10-60 μm, preferably 10-40 μm, preferably 20-70 μm, preferably 40-70 μm, preferably 50-70 μm, preferably 30-70 μm, preferably 40-60 μm. Without intending to be bound by any particular theory, it is believed that the spacing of the gap between the inner wall 8 of the die system 2 and the outer wall 11 of each of the upper and lower punches during sintering functions to facilitate degassing of organics, moisture, adsorbed molecules, etc. of the powder during the sintering process. This results in sintered ceramic bodies, such as the multi-layer bodies disclosed herein, having high density, low volume porosity, and large size with improved mechanical properties, such that the ceramic bodies can be easily handled and machined into the desired configuration of the chamber components without breakage. Multi-layer sintered ceramic bodies made as disclosed herein can have dimensions from 100 mm to about 625 mm for the largest dimension of the multi-layer sintered ceramic body 98.

[0259] In practice, the upper and lower punches 4 and 4' are not always perfectly aligned about the central axis. Fig. 31a) and Fig. 31b) are plan views of the tool set 1, showing the arrangement of the upper and lower punches 4 and 4', the gap 3, the number of conductive foils 7, and the die system 2 about the central axis 9. In the embodiment shown in Fig. 31a)A, the gap can be axisymmetric about the central axis 9. In another embodiment shown in Fig. 31b), the gap can be asymmetric about the central axis 9. The gap 3 can extend between 10 μm and 100 μm in both the axisymmetric and asymmetric embodiments as shown, when the ceramic powder or powder mixture is sintered to form a multilayer sintered ceramic body as disclosed herein.

[0260] The asymmetric performance of the gap can be measured by performing an absolute radial deviation analysis of the CTE over a range of temperatures. For example, FIG. 32 shows the radial deviation from the average CTE at 1200° C. for two isotropic graphite materials (A and B) used as punches and dies in the device disclosed herein. FIG. 32 shows that for materials that can successfully maintain the desired gap over a large temperature range, the radial deviation can vary by no more than >0.3×10-6 ppm / ° C. in the xy plane, for example, from room temperature to 2000° C. Material B shows an unacceptable CTE spread in the xy plane, while material A shows an acceptable CTE spread throughout the entire temperature range.

[0261] The advantages of the particular toolset design used in accordance with one embodiment may result in the overall technical effect of obtaining large multi-layer sintered ceramic bodies of very high purity with high and uniform density and low volumetric porosity, thereby reducing the tendency for fracture in the sintering process according to the present disclosure, particularly the SPS process. Accordingly, all features disclosed with respect to the toolset also apply to the production of multi-layer sintered ceramic bodies with dimensions of more than 100 mm up to about 625 mm.

[0262] The use of the toolset disclosed herein allows to achieve a more homogeneous temperature distribution in the ceramic powder or powder mixture 5 to be sintered, making it possible to produce sintered ceramic bodies, especially those with large dimensions (including about 625 mm or more), e.g., greater than 100 mm and / or 200 mm in their largest dimension, with a very high (>98% of the theoretical density of a given material) and uniform density (<4% variation over the largest dimension), thereby reducing the tendency to fracture. The term "homogeneous" means that the material or system as a whole has substantially the same properties and is uniform without irregularities. Thus, "homogeneous temperature distribution" means that the temperature distribution is spatially uniform and does not have significant gradients, i.e., there is a substantially uniform temperature regardless of the position in the horizontal xy plane along the ceramic powder or powder mixture 5.

[0263] The disclosed toolsets may further include spacer elements, shims, liners, and other toolset components, typically fabricated from at least one of the graphite materials having the properties disclosed herein.

[0264] 33, embodiments of the technology disclosed herein may be useful as components for use in a plasma processing system 9500, also referred to as an "etch processing system," that may be configured for use in a semiconductor etch process. The etch processing system 9500 may include a remote plasma region. The remote plasma region may include a remote RF source / matching network 9502, also referred to as a remote plasma source ("RPS").

[0265] The etch processing system 9500 can include a vacuum chamber 9550 with a corrosion resistant chamber liner (not shown), a vacuum source, and a chuck or electrostatic chuck ("ESC") 9509 on which a wafer 50, also referred to as a substrate, is supported. A cover ring or electrode cover 9514, an upper shield ring 9512, and a shield ring 9513 surround the wafer 50 and puck 9509. A top plate / window / lid 9507 forms a top wall of the vacuum chamber 9550. A showerhead 9517 forms the top wall of the vacuum chamber 9650 or is mounted below the top wall. The top plate / window / lid 9507 (which may include an RF window or dielectric window, gas distribution system 9506, showerhead 9517, cover ring or electrode cover 9514, top shield ring 9512, shield ring 9513, chamber liner (not shown), and chuck or electrostatic chuck (ESC) 9508 and puck 9509 may be fabricated from at least some of the embodiments of the multilayer sintered ceramic body disclosed herein.

[0266] A portion of the surface of the showerhead 9517 may be covered by a shield ring 9712. A portion of the surface of the showerhead 9517, particularly the radial side of the surface of the showerhead 9517, may be covered by an upper shield ring 9710. The shield ring 9712, cover ring 9517, and upper shield ring 9710 may be made at least in part from an embodiment of a multilayer sintered ceramic body disclosed herein.

[0267] The remote plasma source 9502 is located outside a window 9507 of a chamber 9550 that contains a wafer 50 to be processed. The remote plasma region can be in fluid communication with the vacuum chamber 9550 via a gas delivery system 9506. A reactive plasma can be generated in the chamber 9550 by supplying process gases to the chamber 9550 and high frequency power to the plasma source 9502. The reactive plasma thus generated is used to perform a predetermined plasma process on the wafer 50. Planar antennas having a predetermined pattern are commonly used as high frequency antennas in the etching processing system 9500.

[0268] As shown in FIG. 34 , embodiments of the technology disclosed herein may be useful as components in a plasma processing system 9600, also referred to as a “deposition processing system,” that may be configured for use in a semiconductor deposition process. The deposition processing system 9600 includes a vacuum chamber 9650, a vacuum source, and a chuck 9609 on which a wafer 50, also shown as a semiconductor substrate, is supported. The processing system may further include a nozzle or injector 9614 in fluid communication with a gas delivery system 9616 for supplying process gases to the interior of the vacuum chamber 9650. A top wall 9700 of the chamber 9650 may include a central opening configured to receive a central gas injector (also referred to as a nozzle) 9614. In certain embodiments, the top wall 9700 of the chamber may include an RF window or a dielectric window configured with a central opening to accommodate the injector 9614. The RF energy source energizes the process gases into a plasma state to process the substrate 50. An embodiment of the top wall including the RF or dielectric window 9700, the gas delivery system 9616, and the central gas injector 9614 may be made in whole or in part from an embodiment of a multilayer sintered ceramic body as disclosed herein.

[0269] The deposition processing system 9600 may further include an electrostatic chuck 9608 designed to hold a wafer 50. The chuck 9608 may include a puck 9609 to support the wafer 50. A portion of the support surface of the puck 9609 may be covered by a deposition ring 9615. Other names for the deposition ring 9615, such as a deposition shield or a deposition ring assembly, are intended to be synonymous and may be used interchangeably herein. The deposition ring 9615 may be made in whole or in part from an embodiment of a multilayer sintered ceramic body as disclosed herein.

[0270] The puck 9609 may be formed in whole or in part from an embodiment of a multi-layer sintered ceramic body as disclosed herein and may have a chucking electrode disposed within the puck proximate a support surface of the puck 9609 for electrostatically holding the wafer 50 when placed on the puck 9609. The chuck 9608 may include a base 9611 having a ring shape extending to support the puck 9609, and a shaft 9610 disposed between the base and the puck and supporting the puck above the base such that a gap is formed between the puck 9609 and the base 9610, the shaft 9610 supporting the puck proximate a periphery of the puck 9609. The chuck 9608, puck 9609, and deposition ring 9615 may be fabricated in whole or in part from a single embodiment of a multi-layer sintered ceramic body as disclosed herein.

[0271] Preparation method The preparation of multi-layer sintered ceramic bodies may be accomplished by the use of pressure-assisted sintering, such as, for example, Spark Plasma Sintering (SPS) or Direct Current Sintering (DCS), also known as Field-Assisted Sintering Technology (FAST). These DC sintering and related techniques use direct current to heat an electrically conductive die arrangement or tool set and thereby the material to be sintered. This heating regime allows very high heating and cooling rates to be applied, enhancing densification mechanisms over diffusion mechanisms that promote grain growth, facilitating the preparation of ceramic sintered bodies with very fine grain sizes, and transferring the inherent properties of the original powder to their nearly or fully dense products. The DC pressure-assisted method disclosed herein utilizes continuous DC current, preferably not pulsed, to heat the tool set disclosed herein.

[0272] Preparation of the multi-layer sintered ceramic bodies disclosed herein may also be accomplished through the use of pressure assisted sintering methods, such as uniaxial hot pressing, in which a die arrangement or tool set is heated by an externally applied heat source, such as induction heating.

[0273] Multilayer sintered ceramic bodies are generally manufactured using the following process steps: a) combining at least two powders selected from the group consisting of yttria, alumina, and magnesia with at least one selected from the group consisting of stabilized zirconia, partially stabilized zirconia, stabilized zirconia, and combinations thereof to produce a first powder mixture; b) combining an alumina powder with at least one of a partially stabilized zirconia powder and a stabilized zirconia powder to produce a second powder mixture; and c) combining an yttria powder, an alumina powder, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia. d) sintering at least one of the first, second, and third powder mixtures by applying heat to raise the temperature of at least one of the powder mixtures to a sintering temperature and maintaining the sintering temperature to form at least one first, second, and third sintered powder mixture; and e) separately disposing at least one of the first, second, and third powder mixtures within an internal volume defined by a toolset of a sintering apparatus to sinter at least one of the first powder mixture and at least one of the zirconia powder. forming a layer of the first powder mixture, at least one layer of the second powder mixture, and at least one layer of the third powder mixture and creating a vacuum condition within the volume, wherein the toolset comprises a die including a sidewall including an inner wall and an outer wall, and upper and lower punches operatively coupled to the die, the inner wall having a diameter defining an interior volume capable of receiving at least one powder, each of the upper and lower punches having an outer wall defining a diameter smaller than a diameter of the inner wall of the die, such that at least one of the upper and lower punches is positioned within the interior volume of the die. f) applying pressure to the layers of the first, second and third fired powder mixture while heating to a sintering temperature to sinter the layers to form a multi-layer sintered ceramic body, wherein at least one layer of the first powder mixture forms at least one first layer, at least one layer of the second powder mixture forms at least one second layer, and at least one layer of the third powder mixture forms at least one third layer. and g) reducing the temperature of the multi-layer sintered ceramic body, wherein the at least one first layer comprises at least one polycrystalline phase of a ceramic material selected from the group consisting of (i) YAG, (ii) magnesium aluminate spinel, and (iii) yttria and zirconia, the zirconia being present in an amount of 10 mol% or more ZrO2 and 25 mol% or less ZrO2, preferably 12 mol% to 25 mol% ZrO2, preferably 15 mol% to 25 mol% ZrO2, preferably 18 mol% to 25 mol% ZrO2, preferably 10 mol% to 23 mol% ZrO2, preferably 10 mol% to 20 mol% ZrO2, preferably 15 mol% to 25 mol% ZrO2. % or less of ZrO2 (the balance comprising Y2O3); the at least one second layer comprises alumina and zirconia, the zirconia comprising at least one of stabilized zirconia and partially stabilized zirconia; the at least one third layer comprises at least one selected from the group consisting of yttria, alumina, and zirconia, the zirconia comprising at least one of unstabilized zirconia, stabilized zirconia, and partially stabilized zirconia; the at least one second layer is disposed between the at least one first layer and the at least one third layer; an absolute value of a difference in coefficient of thermal expansion (CTE) between any of the at least one first, second, and third layers is 0 to 0.75 x 10-6 / °C as measured in accordance with ASTM E228-17; and the at least one first, second, and third layers form a single sintered ceramic body. In a preferred embodiment, the powders selected from the group consisting of yttria, alumina, magnesia, and at least one selected from the group consisting of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia from steps a), b) and c) each have a molecular weight of about 18 m, as measured according to ASTM C1274. 2 / g or less, preferably about 1 to about 18 m 2 / g. Preferably, the first, second and third powder mixtures have a total impurity content of 200 ppm or less, measured relative to the mass of the first, second and third powder mixtures.

[0274] The at least one second powder mixture comprises alumina and zirconia, the zirconia comprising at least one of stabilized zirconia and partially stabilized zirconia. The at least one second powder mixture comprises alumina in an amount of 60% to 92.5% by weight, preferably 75% to 85% by weight, preferably about 77% by weight, based on the weight of the at least one second powder mixture. The at least one second powder mixture comprises zirconia (including a stabilizer for forming at least one of stabilized zirconia and partially stabilized zirconia) in an amount of 7.5% to 40% by weight, preferably 15% to 25% by weight, preferably about 23% by weight, based on the weight of the at least one second powder mixture. After sintering, these composition ranges of the at least one second powder mixture correspond to at least one second layer 102 comprising zirconia (after sintering) in an amount of 5-30 vol%, preferably 10-30 vol%, preferably 15-30 vol%, preferably 20-30 vol%, preferably 12-25 vol%, preferably 15-25 vol%, preferably 17-25 vol%, preferably 10-22 vol%, preferably 10-20 vol%, preferably 10-17 vol%, preferably 15-21 vol%, preferably 16-20 vol%, preferably about 16 vol%, based on the volume of the at least one second layer 102 (the remainder comprising alumina). These volume amounts of zirconia may be measured using a combination of SEM imaging and ImageJ analysis software according to the methods disclosed herein.

[0275] The at least one third powder mixture comprises at least one selected from the group consisting of yttria, alumina and zirconia, the zirconia comprising at least one of stabilized zirconia, partially stabilized zirconia and stabilized zirconia. The at least one third powder mixture comprises yttria in an amount of 1-57 wt%, preferably 3-57 wt%, preferably 5-57 wt%, preferably 1-40 wt%, preferably 1-30 wt%, preferably 3-30 wt%, preferably 5-30 wt%, preferably 5-15 wt%, preferably about 6 wt%, based on the weight of the at least one third powder mixture. The at least one third powder mixture comprises alumina in an amount of 43 wt%-92.5 wt%, preferably 65 wt%-75 wt%, preferably about 73 wt%, based on the weight of the at least one third powder mixture. The at least one third powder mixture comprises zirconia (including stabilizer, if applicable, to form stabilized and / or non-stabilized) in an amount of about 0.4%-40% by weight, preferably 4%-40% by weight, preferably 15%-40% by weight, preferably 15%-25% by weight, preferably about 21% by weight, based on the weight of the at least one third powder mixture. After sintering, these composition ranges of the at least one third powder mixture may correspond to exemplary SEM images of at least one third layer 103 comprising a multiphase structure of YAG, zirconia and alumina, as shown in Figure 26a) and Figure 26b). In a preferred embodiment, the at least one third powder mixture comprises zirconia in an amount for the at least one third layer (after sintering) comprising ZrO2 in an amount of about 5 to about 30 vol%, preferably 5 to 25 vol%, preferably 5 to 20 vol%, preferably 5 to 16 vol%, preferably 10 to 30 vol%, preferably 15 to 30 vol%, preferably 20 to 30 vol%, preferably 15 to 20 vol%, based on the volume of each at least one third layer 103 (the balance comprising Y2O3 and Al2O3).

[0276] The following additional steps are optional: h) annealing the multi-layer sintered ceramic body by applying heat to increase the temperature of the multi-layer sintered ceramic body until an annealing temperature is reached; i) reducing the temperature of the annealed multi-layer sintered ceramic body; and j) machining the multi-layer sintered ceramic body or the annealed multi-layer sintered ceramic body to produce multi-layer sintered ceramic bodies in the shape of windows, lids, dielectric windows, RF windows, rings, focus rings, process rings, deposition rings, nozzles, injectors, gas injectors, showerheads, gas distribution plates, diffusers, ion suppressor elements, chucks, electrostatic wafer chucks (ESCs), and pucks.

[0277] In some embodiments, an optional annealing step may be performed by applying heat to raise the temperature of the multi-layer sintered ceramic body to an annealing temperature, performing the annealing, reducing the temperature of the sintered and annealed multi-layer sintered ceramic body to ambient temperature by removing the heat source applied to the body, and transferring the multi-layer sintered ceramic body.

[0278] The above-mentioned properties of the corrosion resistant multi-layer sintered ceramic body according to one embodiment are achieved, in part, by tailoring the purity and specific surface area (SSA) of the first, second and third powder mixtures, the pressure on the first, second and third powder mixtures, the temperature of the first, second and third powder mixtures, the duration of sintering of the first, second and third powder mixtures, the temperature of the multi-layer sintered ceramic body during the optional annealing step, and the duration of the optional annealing step.

[0279] A method for preparing a multi-layer sintered ceramic body is disclosed, the method comprising the steps of: a) combining at least two powders selected from the group consisting of yttria, alumina, and magnesia with at least one selected from the group consisting of stabilized zirconia, partially stabilized zirconia, stabilized zirconia, and combinations thereof to produce a first powder mixture; b) combining an alumina powder with at least one of a partially stabilized zirconia powder and a stabilized zirconia powder to produce a second powder mixture; c) combining an yttria powder, an alumina powder, and at least one of a non-stabilized zirconia, partially stabilized zirconia, and stabilized zirconia powder to produce a third powder mixture; and d) applying heat to at least one of the first, second, and third powder mixtures to raise the temperature of the powder mixture to a sintering temperature and maintaining the sintering temperature to sinter at least one of the first, second, and third powder mixtures. e) separately disposing the first, second, and third powder mixtures within an interior volume defined by a toolset of a sintering apparatus to form at least one layer of the first powder mixture, at least one layer of the second powder mixture, and at least one layer of the third powder mixture and create a vacuum condition within the volume, the toolset comprising a die including a sidewall including an inner wall and an outer wall, and an upper punch and a lower punch operatively coupled to the die, the inner wall having a diameter defining an interior volume capable of receiving at least one powder, each of the upper punch and the lower punch having an outer wall defining a diameter smaller than a diameter of the inner wall of the die, thereby defining a gap between each of the upper punch and the lower punch and the inner wall of the die when at least one of the upper punch and the lower punch moves within the interior volume of the die, the gap being between 10 μm and 100 μm in width.f) applying pressure to at least one of the layers of the first, second and third fired powder mixture while heating to a sintering temperature to sinter to form a multi-layer sintered ceramic body, wherein after sintering at least one layer of the first powder mixture forms at least one first layer, at least one layer of the second powder mixture forms at least one second layer, and at least one layer of the third powder mixture forms at least one third layer; and g) reducing the temperature of the multi-layer sintered ceramic body, wherein at least one first layer is selected from the group consisting of: (i) YAG; (ii) Magnesium aluminate; and (iii) at least one crystalline phase of a ceramic material selected from the group consisting of yttria and zirconia, the zirconia comprising an amount of at least 10 mol% ZrO2 and at most 25 mol% ZrO2, preferably at least 12 mol% and at most 25 mol% ZrO2, preferably at least 15 mol% and at most 25 mol% ZrO2, preferably at least 18 mol% and at most 25 mol% ZrO2, preferably at least 10 mol% and at most 23 mol% ZrO2, preferably at least 10 mol% and at most 20 mol% ZrO2, preferably at least 15 mol% and at most 23 mol% ZrO2. The at least one second layer comprises alumina and zirconia, the zirconia comprising at least one of unstabilized, stabilized zirconia and partially stabilized zirconia, the at least one second layer being disposed between the at least one first layer and the at least one third layer, the absolute value of the difference in coefficient of thermal expansion (CTE) between any of the at least one first, second and third layers being 0 to 0.75×10-6 / °C as measured according to ASTM E228-17, and the at least one first, second and third layers forming a single sintered ceramic body. In a preferred embodiment, the powders selected from the group consisting of yttria, alumina, magnesia, and at least one selected from the group consisting of unstabilized zirconia, partially stabilized zirconia and stabilized zirconia each have a thickness of about 18 m as measured according to ASTM C1274. 2 / g or less, preferably about 1 to about 18 m 2In a further preferred embodiment, the at least one first, second and third powder mixture (or optionally the calcined powder mixture) each has a specific surface area of ​​about 18 m / g, as measured according to ASTM C1274. 2 / g or less, preferably 1 to 18m 2 / g. Preferably, the first, second and third powder mixtures have a total impurity content of 200 ppm or less, measured relative to the mass of the first, second and third powder mixtures.

[0280] The following additional steps are optional: h) annealing the multi-layer sintered ceramic body by applying heat to increase the temperature of the multi-layer sintered ceramic body until an annealing temperature is reached; i) reducing the temperature of the annealed multi-layer sintered ceramic body; and j) machining the multi-layer sintered ceramic body or the annealed multi-layer sintered ceramic body to produce multi-layer sintered ceramic bodies in the shape of windows, lids, dielectric windows, RF windows, rings, focus rings, process rings, deposition rings, nozzles, injectors, gas injectors, showerheads, gas distribution plates, diffusers, ion suppressor elements, chucks, electrostatic wafer chucks (ESCs), and pucks for use in plasma processing chambers.

[0281] Step a) of the method disclosed herein comprises combining at least two powders selected from the group consisting of yttria, alumina, magnesia, and zirconia (zirconia is selected from at least one of non-stabilized zirconia, partially stabilized zirconia, and stabilized zirconia) to make a first powder mixture. The starting powder materials comprising the first powder mixture are combined and mixed in a proportion such that the at least one first powder mixture forms, after sintering, at least one first layer comprising at least one crystalline phase of a ceramic material comprising YAG, magnesium aluminate spinel, or comprising yttria and zirconia, wherein the zirconia is present in an amount of 10 mol% or more ZrO2 and 25 mol% or less ZrO2, with the balance comprising Y2O3. The powders selected to form the at least one first powder mixture are preferably commercially available powders of high purity (>99.99%). However, other oxide powders, such as those produced from chemical synthesis processes and related methods, may also be used.

[0282] The particle size of the starting powders, powder mixtures and calcined powder mixtures can be measured using a Horiba Model LA-960 laser scattering particle size distribution analyzer, which can measure particle sizes from 10 nm to 5 mm. The specific surface area (SSA) of the starting powders, powder mixtures and calcined powder mixtures ranges from 0.01 to 2000 m for most samples. 2Purity can be measured using a Horiba BET Surface Area Analyzer model SA-9601, which can measure with an accuracy of 10% or better over a specific surface area of ​​100 / g. The purity of the starting powder, powder mixture, and calcined powder mixture can be measured using ICP-MS measurements using an Agilent 7900 ICP-MS model G8403, which can analyze lighter elements (such as Sc and lower atomic numbers) to about 1.4 ppm and heavier elements (such as atomic numbers higher than Sc) to about 0.14 ppm. Purity is reported herein as a percentage of 100% purity, which represents a material that does not include impurities, dopants, sintering aids, etc., and contains only the intended components. Impurity content is reported herein in ppm relative to the total mass of the material being evaluated. Silica is not disclosed in the purity and impurity reports and can be measured in an amount of about 14 ppm using the ICP-MS method disclosed herein.

[0283] As known in the art, the d50 particle size is defined as the median particle size and represents the value above which half of the particle size distribution lies and below which half lies. Similarly, 90% of the distribution lies below the d90 and 10% of the distribution lies below the d10.

[0284] The starting powders of yttria, zirconia, magnesia and alumina are preferably crystalline, thereby having long-range crystallographic order. Any one or all of the starting powders of yttria, zirconia, magnesia and alumina may be sieved, tumbled, blended, ground, etc., according to methods known to those skilled in the art. In some embodiments, the starting powders of yttria, magnesia, zirconia and / or alumina may be calcined, if desired, according to methods known to those skilled in the art. 2Starting powders, powder blends and sintered powder blends with high specific surface areas (SSA), such as nano powders exceeding 180 nm / g, present challenges in handling when loading the powders into the tool set, achieving uniform particle dispersion and mixing during the powder combination / mixing process, and forming a first layer containing a YAG phase during the in-situ reactive sintering method for forming YAG as disclosed in International Application No. PCT / US20 / 60918, which is incorporated herein by reference. Starting powders according to the methods disclosed herein include yttria, magnesia, zirconia and alumina, and are preferably 180 nm or less. 2 / g or less. Thus, the powder mixtures disclosed herein are free or substantially free of nanopowder and have a specific surface area of ​​about 18 m 2 It is preferred that the specific surface area (SSA) is 0.1 to 1.0 μm / g or less.

[0285] Approximately 0.75m 2 Starting powders, powder mixtures and / or calcined powder mixtures having a specific surface area less than 100 nm / g may suffer from agglomeration and may require higher mixing energy and longer mixing times to combine to form the powder mixtures disclosed herein. Additionally, powders having a surface area in this range can reduce the driving force required to sinter to high density as disclosed herein and produce sintered ceramic bodies with lower density and higher porosity. Preferred for use in the disclosed methods are powders having a specific surface area of ​​1 to 18 m2 as measured according to ASTM C1274. 2 / g, preferably 2 to 15m 2 / g, preferably 3 to 12 m 2 / g of SSA.

[0286] The d10 particle size of the yttrium oxide powder used as starting material according to one embodiment of the present invention is preferably 1-6 μm, preferably 1-5 μm, preferably 1-4 μm, preferably 2-6 μm, preferably 3-6 μm, preferably 4-6 μm, preferably 2-4 μm.

[0287] The d50 particle size of the yttrium oxide powder used as a starting material according to one embodiment of the present invention is preferably 3-9 μm, preferably 3-8.5 μm, preferably 3-8 μm, preferably 3-7 μm, preferably 4-9 μm, preferably 5-9 μm, preferably 6-9 μm, preferably 4-8 μm. The yttria powder disclosed herein may have an average particle size of about 5-9 μm.

[0288] The d90 particle size of the yttrium oxide powder used as starting material according to one embodiment of the present invention is preferably 6-16 μm, preferably 6-15 μm, preferably 6-14 μm, preferably 6.5-16 μm, preferably 7-16 μm, preferably 7.5-16 μm, preferably 7.5-14 μm.

[0289] Yttrium oxide powder is typically 2-10m 2 / g, preferably 2 to 8 m 2 / g, preferably 2 to 6m 2 / g, preferably 3 to 10m 2 / g, preferably 4 to 10m 2 / g, preferably 6 to 10m 2 / g, preferably 2 to 4 m 2 / g specific surface area (SSA).

[0290] The purity of the yttrium oxide starting material is preferably greater than 99.99%, preferably greater than 99.995%, more preferably greater than 99.999%, more preferably greater than 99.9995%, more preferably greater than about 99.9999%, which corresponds to an impurity level of 100 ppm or less, preferably 50 ppm or less, preferably 25 ppm or less, preferably 10 ppm or less, more preferably about 1 ppm, preferably 1-100 ppm, preferably 1-50 ppm, preferably 1-25 ppm, preferably 1-10 ppm, preferably 1-5 ppm.

[0291] The average or d50 particle size of the magnesium oxide powder used as a starting material according to one embodiment of the present invention is typically 1.5-5.5 μm, 2-5.5 μm, 2.5-5.5 μm, 3-5.5 μm, 1.5-5 μm, 1.5-4.5 μm, more preferably 2-4.5 μm.

[0292] The d90 particle size of the magnesium oxide powder used as starting material according to one embodiment of the present invention is 4-9 μm, preferably 5-9 μm, preferably 6-9 μm, preferably 4-8 μm, preferably 4-7 μm, more preferably 5-7.5 μm.

[0293] Magnesium oxide powder is typically 0.5 to 10 m 2 / g, preferably 0.5 to 8m 2 / g, preferably 0.5 to 6m 2 / g, preferably 1 to 10m 2 / g, preferably 2 to 10m 2 / g, preferably 3 to 10m 2 / g, preferably 2 to 6m 2 The magnesium oxide starting material has a specific surface area (SSA) of 100 ppm or less, preferably .... Correspondingly, the magnesia powder has a specific surface area (SSA) of 10 ppm

[0294] The zirconia powder according to step a) may be selected from the group consisting of unstabilized zirconia, partially stabilized zirconia and stabilized zirconia. The reaction between the zirconia powder and the yttria powder to form at least one crystalline phase allows any zirconia powder to be used without the need for stabilization of the tetragonal / monoclinic phase transformation that occurs in phase-pure zirconia. Thus, the zirconia powder for forming the at least one first layer may comprise any one or combination of unstabilized zirconia, partially stabilized zirconia and stabilized zirconia. Further powder properties of zirconia and alumina (from the second powder mixture) are disclosed in step b) of the method below.

[0295] Combining at least two of alumina, magnesia, yttria, and at least one of non-stabilized zirconia powder, partially stabilized zirconia powder, and stabilized zirconia powder to produce at least first and second powder mixtures (according to either or both of steps a) and b) may be performed using the following powder preparation techniques: wet or dry ball (axial) milling, wet or dry tumbling (end-over-end or vertical) mixing, jet milling, and combinations thereof. The use of these powder combination methods provides a high energy process that breaks down particulates and agglomerates.

[0296] Using dry conditions, the starting powders may be ball milled or end-over-end / tumbling mixed using high purity (>99.9%) alumina media to maintain the purity of the starting powders during mixing. In other embodiments, hard media such as zirconia media may be used to break down hard agglomerates. High purity alumina media was tested using the ICPMS method disclosed herein and found to have a purity of about 99.9-99.99%. The use of zirconia media may result in trace amounts of zirconia, such as less than 100 ppm, in the multi-layer sintered ceramic body. Media used to perform dry ball milling may have dimensions ranging from, for example, 5 mm to 15 mm in diameter and are added at a loading of about 50 to about 100% by powder weight. Media used to perform dry tumbling mixing may include, but is not limited to, at least one media element of large dimensions (about 20-40 mm in diameter). Dry ball milling and / or dry tumbling mixing may be carried out for a period of 12 to 48 hours, preferably 16 to 48 hours, preferably 16 to 24 hours, preferably 18 to 22 hours. Dry ball milling or tumbling mill processes (axial rotation) may use RPM (revolutions per minute) of 50 to 250 RPM, preferably 75 to 200 RPM, preferably 75 to 150 RPM, preferably 100 to 125 RPM, each with a vessel having a diameter of about 200 mm. The RPM may vary depending on the size of the vessel selected for use, for example, one with a diameter larger than 200 mm may have a correspondingly lower RPM, as known to those skilled in the art. Dry end-over-end / tumbling mixing may be carried out at an RPM of 10 to 30 rpm, preferably about 20. After dry ball milling and / or dry end-over-end / tumbling milling / mixing, the powder mixture may be sieved and blended as necessary using any number of meshes that may have openings, for example, between 45 and 400 μm, without any limitation as to repetition or sequence as known to those skilled in the art.

[0297] Wet ball milling or wet end-over-end / tumbling mixing can be done by suspending the starting powders in various solvents such as ethanol, methanol, and other alcohols to form a slurry. The slurry in either process (ball milling or tumbling grinding / mixing) can be formed during milling or mixing with a powder loading of 25-75% by powder weight, preferably 40-75% by powder weight, preferably 50-75% by powder weight. Wet ball milling or wet end-over-end / tumbling mixing can result in improved dispersion of the powders due to increased mobility, resulting in fine scale uniform mixing prior to heat treatment or calcination. In embodiments, a dispersant may be added to the slurry as needed using any number of commercially available dispersants, such as polymethylmethacrylate (PMMA) and polyvinylpyrrolidone (PVP) and other dispersants known to those skilled in the art. The dispersant may be added as needed in an amount of 0.05-0.2% by powder weight, preferably 0.05-0.1% by powder weight. Media loading for either wet ball or wet tumbling / end-over-end mixing may vary from 30-100% loading by powder weight, preferably 30-75% loading by powder weight, preferably 30-60% loading by powder weight. Wet ball milling or tumbling mixing may be carried out for a duration of 8-48 hours, preferably 12-48 hours, preferably 16-48 hours, preferably 8-36 hours, preferably 8-24 hours, preferably 16-24 hours, preferably 12-24 hours. Ball milling may use RPM (revolutions per minute) of 50-250 RPM, preferably 75-200 RPM, preferably 75-150 RPM, preferably 100-125 RPM, each for a vessel having a diameter of about 200 mm. RPM may vary depending on the size of the vessel selected for use, for example, one with a diameter greater than 200 mm may have a correspondingly lower RPM, as known to those skilled in the art. Wet end-over-end / tumbling (or vertical) mixing may be performed at 10-30 rpm, preferably about 20 RPM.After wet ball milling and / or wet end-over-end / tumbling mixing, the powder mixture may be sieved and blended as necessary using any number of meshes that may have openings, for example, between 45 and 400 μm, without any limitation as to repetition or sequence, as known to those skilled in the art.

[0298] Jet milling processes known to those skilled in the art may be used to thoroughly mix the powders to form powders, powder mixtures, or calcined powder mixtures with narrow particle size distributions. Jet milling uses high velocity jets of either inert gas or air to collide particles of the starting powders and / or powder mixtures and / or calcined powder mixtures without the use of milling or mixing media, thus maintaining the initial purity of the powders being milled. The chamber can be designed to allow larger particles to be preferentially reduced in size, providing a narrow particle size distribution in the final powder, powder mixture, or calcined powder mixture. Once the powders reach a pre-determined particle size determined by the machine settings prior to processing, they exit the jet milling chamber to end the process. The starting powders, powder mixtures, and / or calcined powder mixtures disclosed herein may be subjected to jet milling at a pressure of about 100 psi, either separately as the disclosed powder grinding / mixing processes, or in any combination thereof, or all of them, as disclosed herein. After the jet milling, the powder or powder mixture may be blended and optionally sieved using any number of meshes, which may have openings of, for example, 45 to 400 μm, without any limitation as to repetition or sequence, as known to those skilled in the art.

[0299] Additional powder preparation procedures such as grinding, high shear mixing, planetary milling, and other known procedures may also be applied. The powder preparation techniques described above may be used alone or in any combination thereof, or for two or more powder mixtures that are subsequently sintered to form a single multi-layered sintered ceramic body.

[0300] If a wet mixing or milling process is used, the slurry can be dried by rotary evaporation, for example at a temperature of about 40° C. to 90° C. for 1 to 4 hours, depending on the volume of the slurry to be dried, as known to those skilled in the art. In other embodiments, the slurry can be dried using spray drying techniques known to those skilled in the art. After drying, the powder mixture may be sieved and blended as necessary, for example, using a mesh having openings of 45 to 400 μm, without any limitation with respect to repetition or sequence. The aforementioned powder preparation techniques may be used alone or in any combination thereof.

[0301] After drying, the powder mixture of step a) has a specific surface area of ​​2 to 18 m2, measured according to ASTM C1274. 2 / g, preferably 2 to 17m 2 / g, 2-14m 2 / g, preferably 2 to 12 m 2 / g, preferably 2 to 10m 2 / g, preferably 4 to 17m 2 / g, preferably 6 to 17m 2 / g, preferably 8 to 17m 2 / g, preferably 10 to 17m 2 / g, preferably 4 to 12 m 2 / g, preferably 4 to 10m 2 / g, preferably 5 to 8 m 2 / g.

[0302] The purity of the powder mixture can be maintained from the purity of the starting materials after mixing / milling by using high purity grinding media, such as aluminum oxide media of 99.99% purity or greater. In embodiments, the use of zirconium oxide grinding media may be preferred, and zirconium oxide can be introduced to the extent that it remains within at least one of the first and / or second layers of the multi-layer sintered ceramic body in an amount of 15-100 ppm, 15-75 ppm, preferably 15-60 ppm, preferably 20-30 ppm.

[0303] Step b) of the method disclosed herein includes combining an alumina powder with a zirconia powder (wherein the zirconia powder includes at least one of a partially stabilized zirconia powder and a stabilized zirconia powder) to create a second powder mixture. The starting powder materials including the second powder mixture are combined and mixed in a ratio such that the second powder mixture forms at least one second layer 102 after sintering, the at least one second layer 102 including at least one of partially stabilized zirconia and stabilized zirconia (and combinations thereof) in an amount of 5% by volume or more ZrO2 and 30% by volume or less ZrO2, with the balance including Al2O3. The starting powders selected to form the at least one second layer 102 are preferably commercially available powders of high purity. However, other oxide powders, such as those produced from chemical synthesis processes and related methods, may also be used. In some embodiments, depending on the required CTE matching properties, toughness and mechanical strength requirements of the plasma processing chamber components, the at least one second layer 102 comprises at least one of partially stabilized zirconia and stabilized zirconia (and combinations thereof) in an amount of 10 volume % or more ZrO2 and 25 volume % or less ZrO2 relative to the volume of the at least one second layer 102, with the balance comprising Al2O3.

[0304] The following characteristics regarding the zirconia and alumina powders also apply to step a), except that the zirconia of step a) may comprise any one or combination of unstabilized zirconia, partially stabilized zirconia and stabilized zirconia. The zirconia powder according to step b) is preferably stabilized, partially stabilized and combinations thereof.

[0305] The zirconium oxide powder may have a particle size distribution with a d10 of 0.08-0.20 μm, a d50 of 0.3-0.7 μm, and a d90 of 0.9-5 μm. The zirconium oxide powder used as starting material for the mixture according to one embodiment of the invention may have an average particle size of 0.3-1 μm.

[0306] Zirconia powders typically have a particle size of 1 to 16 m as measured according to ASTM C1274. 2 / g, preferably 2 to 14m 2 / g, preferably 4 to 12 m 2 / g, preferably 5 to 9m 2 / g.

[0307] The purity of the zirconia powder starting material is typically greater than 99.8%, preferably greater than 99.9%, preferably greater than 99.95%, preferably greater than 99.975%, preferably greater than 99.99%, preferably greater than 99.995%. This corresponds to a total impurity content of 2000 ppm or less, preferably 1000 ppm or less, preferably 500 ppm or less, preferably 250 ppm or less, preferably 100 ppm or less, preferably 50 ppm or less, preferably 25-150 ppm, as measured using the ICPMS method disclosed herein. The zirconia used in the embodiments disclosed herein contains a small amount of Hf, about 2-5 wt%, as is common in many commercially available zirconia powders. These purities of zirconia exclude Hf and any stabilizing compounds, as disclosed according to Table 1.

[0308] In an embodiment, the zirconia powder may include a stabilizing compound including at least one selected from the group consisting of yttria, lanthanum oxide (La2O3), ceria (CeO2), magnesia, samaria (Sm2O3), and calcia, and combinations thereof. To form partially stabilized zirconia (PSZ), these stabilizing compounds may each be present in an amount of 0.5 to 50 mol%, preferably 0.5 to 30 mol%, preferably 0.5 to 15 mol%, preferably 0.5 to 10 mol%, preferably 1 to 50 mol%, preferably 1 to 30 mol%, preferably 1 to 10 mol%, preferably 1 to 5 mol%, preferably about 3 mol%. To form stabilized zirconia (SZ), these stabilizing compounds may each be present in an amount of more than 6 to about 45 mol%, preferably more than 10 to about 45 mol%, preferably more than 25 to about 45 mol%, preferably more than 6 to 30 mol%, preferably more than 6 to about 15 mol%, preferably more than 8 to 15 mol%. Table 1 provides additional guidelines for stabilizing or partially stabilizing zirconia.

[0309] In a particular embodiment, at least one second layer 102 is yttria stabilized and formed from a powder mixture including alumina and zirconia, where the zirconia is selected from the group consisting of partially yttria stabilized zirconia (PYSZ) or fully yttria stabilized zirconia (YSZ). Partially yttria stabilized zirconia (PYSZ) may be formed from a powder mixture including about 1-10 mol% yttria, preferably 1-8 mol% yttria, preferably 1-5 mol% yttria, preferably 2-4 mol% yttria, preferably about 3 mol% yttria. Yttria stabilized zirconia (YSZ) can be formed from a powder mixture including about 8 to about 15 mol% yttria, preferably 10-15 mol% yttria, preferably 12-15 mol% yttria.

[0310] The alumina powder comprising the first and second powder mixtures has the powder characteristics disclosed below.

[0311] The d10 particle size of the aluminum oxide powder used as starting material according to the embodiments of the present disclosure is preferably 0.1-0.5 μm, preferably 0.1-0.4 μm, preferably 0.1-0.3 μm, preferably 0.2-0.5 μm, preferably 0.3-0.5 μm, preferably 0.4-0.5 μm, preferably 0.1-0.2 μm.

[0312] The d50 particle size of the aluminum oxide powder used as starting material according to embodiments of the present disclosure is preferably 2-8 μm, preferably 2-7 μm, preferably 2-6 μm, preferably 3-8 μm, preferably 4-8 μm, preferably 5-8 μm, preferably 2.5-5 μm.

[0313] The d90 particle size of the aluminum oxide powder used as a starting material according to an embodiment of the present disclosure is preferably 15-40 μm, preferably 15-30 μm, preferably 15-25 μm, preferably 20-40 μm, preferably 30-40 μm, preferably 20-30 μm.

[0314] Aluminum oxide powder is typically 4 to 18 m 2 / g, preferably 4 to 14m 2 / g, preferably 4 to 10m 2 / g, preferably 4 to 6m 2 / g, preferably 6 to 18m 2 / g, preferably 6 to 14m 2 / g, preferably 8 to 18m 2 / g, preferably 10 to 18 m 2 / g, preferably 8 to 10m 2 / g, preferably 6 to 10m 2 / g.

[0315] The purity of the aluminum oxide starting material is typically greater than 99.99%, preferably greater than 99.995%, preferably greater than 99.999%, preferably greater than 99.9995%, as measured using ICPMS techniques. Correspondingly, the impurity content of the alumina powder may be 100 ppm or less, preferably 50 ppm or less, preferably 25 ppm or less, preferably 10 ppm or less, more preferably 5 ppm or less.

[0316] The alumina powder and zirconia powder are mixed in a ratio such that the zirconia is present in an amount of 10 to 30 volume %, preferably 10 to 25 volume %, preferably 10 to 20 volume %, preferably 15 to 25 volume %, preferably 20 to 25 volume %, preferably 15 to 20 volume %, each of at least one second layer 102 (after sintering) of the multilayer sintered ceramic body.

[0317] Combining alumina with at least one of the partially stabilized zirconia powder and the stabilized zirconia powder to make the second powder mixture may be carried out according to the materials and methods disclosed in step a) of the method.

[0318] Step c) of the method disclosed herein includes combining alumina, yttria, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia to produce at least one third powder mixture. The at least one third powder mixture may include alumina in an amount of more than 43% and not more than 92.5%, yttria in an amount of 1% to 56%, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia in an amount of 0.4% to 40%, each by weight of the at least one third powder mixture. Preferably, the at least one third powder mixture has a viscosity of 1 to 18 m as measured according to ASTM C1274. 2 / g, preferably 1m 2 / g ~ approx. 14m 2 / g, preferably about 1m 2 / g~about 10m 2 / g, preferably about 1m 2 / g~about 8m 2 / g, preferably about 2m 2 / g ~ approx. 18m 2 / g, preferably about 2m 2 / g ~ approx. 14m 2 / g, preferably about 2m 2 / g~about 10m 2 / g, preferably about 3m 2 / g~approx. 9m 2 / g, preferably about 3m 2 / g~about 6m 2 The at least one third powder mixture may have a specific surface area (SSA) of about 100 / g. In a preferred embodiment, the at least one third powder mixture may include about 73% alumina, about 6% yttria, and about 21% at least one of stabilized zirconia, partially stabilized zirconia, and stabilized zirconia, each based on the weight of the at least one third powder mixture. In a further preferred embodiment, the at least one third powder mixture includes about 73% alumina, about 6% yttria, and about 21% 3 mol % yttria partially stabilized zirconia, each based on the weight of the at least one third powder mixture. The at least one third powder mixture forms at least one third layer 103 having multiple phases including YAG, alumina, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia, after sintering. In another embodiment, the at least one third powder mixture may be batch processed to form a YAG phase after sintering, and thus includes about 43% by weight alumina and 57% yttria, and the at least one third layer including YAG has a CTE match within the disclosed range to the at least one first layer including YAG.

[0319] Combining the yttria, alumina and zirconia powders to make the third powder mixture can be done according to the materials and methods disclosed in step a) The third powder mixture can be dry ball milled, roller blended, wet milled, wet tumble mixed, and other similar mixing methods known to those skilled in the art.

[0320] As disclosed above, combining at least two of alumina, yttria, magnesia, and at least one of non-stabilized zirconia powder, partially stabilized zirconia powder, and stabilized zirconia powder to produce at least the first, second, and third powder mixtures (according to either or both of steps a), b) and c) can be performed using powder preparation techniques such as wet or dry ball (axial) milling, wet or dry tumbling (end-over-end or vertical) mixing, jet milling, and combinations thereof. The use of these powder combining methods provides a high energy process that breaks down particulates and agglomerates.

[0321] Step d) of the method disclosed herein includes sintering at least one of the first, second and third powder mixtures by applying heat to raise the temperature of at least one of the powder mixtures to a sintering temperature and maintaining the sintering temperature to form at least one first, second and third sintered powder mixture. This step can be performed in such a way that moisture can be removed and the surface condition of the powder mixture is uniform before sintering. The sintering can be performed at a temperature of 600°C to 1200°C, preferably 600°C to 1100°C, preferably 600°C to 1000°C, preferably 600°C to 900°C, preferably 700°C to 1100°C, preferably 800°C to 1100°C, preferably 800°C to 1000°C, preferably 850°C to 950°C. Calcination may be performed in an oxygen-containing environment for a duration of 4-12 hours, preferably 4-10 hours, preferably 4-8 hours, preferably 6-12 hours, preferably 4-6 hours. After calcination, the powder mixture may be sieved and / or tumbled and / or blended according to known methods to form at least one first, second and third calcined powder mixture. The at least one first powder mixture is preferably calcined. Calcination may or may not result in a reduction in the specific surface area.

[0322] The first powder mixture may have a d10 particle size of 0.06-4 μm, preferably 0.08-4 μm, preferably 0.1-4 μm, preferably 0.2-4 μm, preferably 0.3-4 μm, preferably 0.4-4 μm, preferably 0.08-3 μm, preferably 0.08-2 μm, preferably 0.08-1 μm, preferably 0.5-3 μm, preferably 1-2 μm, preferably 1-3 μm.

[0323] The second powder mixture may have a d10 particle size of 0.075-0.4 μm, preferably 0.075-0.3 μm, preferably 0.075-0.2 μm, preferably 0.1-0.4 μm, preferably 0.1-0.3 μm, preferably 0.1-0.2 μm, preferably about 0.2 μm.

[0324] The first powder mixture may have a d50 particle size of 0.7-50 μm, preferably 1-40 μm, preferably 1-30 μm, preferably 1-20 μm, preferably 1-10 μm, preferably 1-5 μm, preferably 5-50 μm, preferably 10-50 μm, preferably 20-50 μm, preferably 30-50 μm, preferably 3-8 μm, preferably 5-10 μm, preferably 6-15 μm.

[0325] The second calcined powder mixture may have a d50 particle size of 1-100 μm, preferably 1-80 μm, preferably 1-60 μm, preferably 1-40 μm, preferably 10-100 μm, preferably 20-100 μm, preferably 30-100 μm, preferably 20-80 μm, preferably 20-60 μm, preferably 20-40 μm.

[0326] The first and second sintered powder mixtures may have a d90 particle size of 10-350 μm, preferably 10-300 μm, preferably 10-250 μm, preferably 10-200 μm, preferably 10-175 μm, preferably 10-150 μm, preferably 10-100 μm, preferably 10-75 μm, preferably 10-50 μm, preferably 10-40 μm, preferably 10-25 μm, preferably 20-350 μm, preferably 40-350 μm, preferably 60-350 μm, preferably 100-350 μm, preferably 150-350 μm, preferably 200-350 μm, preferably 12-330 μm, preferably 100-330 μm, preferably 100-250 μm.

[0327] The second calcined powder mixture may have a d90 particle size of 20-250 μm, preferably 20-220 μm, preferably 20-150 μm, preferably 20-100 μm, preferably 50-220 μm, preferably 70-220 μm, preferably about 100-220 μm.

[0328] In certain embodiments, the higher temperature firing conditions disclosed herein may result in the formation of crystalline phases and agglomeration of the fired powder mixture, thus resulting in greater variability in the overall particle size distribution, particularly larger d50 and d90 particle sizes. In other embodiments, the lower temperature firing conditions disclosed herein may not affect the particle size distribution of the fired powder mixture compared to the starting material, whereby the particle size distribution is in the same range as or similar to the starting powder material. Lot-to-lot variability and management of heat transfer during firing may also contribute to the variability in particle size distribution. Thus, a wide range of particle size distributions, particularly d50 and d90 particle sizes of the powder mixture, may result from the firing conditions disclosed herein.

[0329] The at least one first, second and third calcined powder mixtures each have a thickness of about 1 m as measured in accordance with ASTM C1274. 2 / s~about 18m 2 / g, preferably 1m 2 / g ~ approx. 14m 2 / g, preferably about 1m 2 / g~about 10m2 / g, preferably about 1m 2 / g~about 8m 2 / g, preferably about 2m 2 / g ~ approx. 18m 2 / g, preferably about 2m 2 / g ~ approx. 14m 2 / g, preferably 2 to 12 m 2 / g, preferably about 2m 2 / g~10m 2 / g, preferably about 3m 2 / g~approx. 9m 2 / g, preferably about 3m 2 / g~about 6m 2 / g specific surface area (SSA).

[0330] The first calcined powder mixture may have a total impurity content of 5 to 200 ppm, preferably 5 to 150 ppm, preferably less than 100 ppm, preferably less than 75 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably less than 10 ppm, preferably less than 8 ppm, preferably less than 5 ppm, preferably 5 to 50 ppm, preferably 5 to 30 ppm, preferably 3 to 20 ppm, based on the mass of the first calcined powder mixture.

[0331] Table 11 shows the ICPMS purity results of the exemplary first powder mixture before being formed into a polycrystalline YAG layer.

[0332] [Table 11] * N / A represents the elements present in the starting powders forming the powder mixture.

[0333] Table 12 shows the ICPMS purity results of the exemplary first powder mixture before being formed into a spinel layer.

[0334] [Table 12] *N / A represents the elements present in the starting powders forming the powder mixture.

[0335] Table 13 shows the ICPMS purity results of the exemplary first powder mixture before being formed into an yttria-zirconia layer.

[0336] [Table 13] * N / A represents elements present in the starting powders forming the powder mixture;

[0337] For each of Tables 10-14, N / D indicates that the element was detected below the reporting limit of ICPMS. Purity reported is the average across five powder mix lots.

[0338] The second powder mixture may have a total impurity content of 5 to 200 ppm, preferably 5 to 150 ppm, preferably less than 100 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably 10 to 100 ppm, preferably 10 to 80 ppm, preferably 10 to 60 ppm, preferably 10 to 40 ppm, preferably 20 to 80 ppm, preferably 30 to 60 ppm, based on the mass of the second powder mixture.

[0339] Table 14 shows the ICPMS purity results of the exemplary second powder mixture before being formed into at least one second layer 102.

[0340] [Table 14]

[0341] The results in Table 14 are averaged over five powder lots. As shown in Table 14, the second powder mixture may contain magnesia in an amount of about 5 ppm or less, preferably 3 ppm or less, measured relative to the mass of the at least one second powder mixture. The powder mixtures comprising alumina and at least one of stabilized zirconia and partially stabilized zirconia disclosed herein are free or substantially free of dopants and / or sintering aids disclosed herein. Hf, Y, and Zr are not considered impurities, dopants, or sintering aids and are not listed in Table 14.

[0342] The starting powders, including at least one first and second powder mixture, have different characteristics, such as particle size and purity. Thus, the characteristics of the powder mixture, such as purity, can be higher than the at least one starting powder alone by combining it with another starting powder, which can be of higher purity.

[0343] Tables 10-14 show very high purity (>99.99% for 100% pure powder) of at least one powder mixture batched to form (after sintering) at least one crystalline phase of YAG, magnesium aluminate spinel, yttria and zirconia (zirconia present in an amount of 10 to 25 mol %), and alumina and zirconia (zirconia including at least one of stabilized zirconia and partially stabilized zirconia). As listed in the tables, each of the powder mixtures may contain iron (Fe) in an amount less than 0.5 ppm, preferably less than 0.25 ppm, by weight of the respective powder mixture.

[0344] Step e) of the method disclosed herein includes separately placing the first, second and third sintered powder mixtures in a volume defined by a sintering machine tool set to form at least one layer of the first powder mixture, at least one layer of the second powder mixture and at least one layer of the third powder mixture, and creating a vacuum condition in the volume. The spark plasma sintering (SPS) machine tool set used in the process disclosed herein includes at least one graphite die, typically a cylindrical graphite die. In the graphite die, the first, second and third powder mixtures are separately placed between three graphite punches to form at least two separate layers.

[0345] In a preferred embodiment, the SPS apparatus comprises a die including a sidewall including an inner wall and an outer wall, the inner wall having a diameter defining an internal volume capable of receiving at least one ceramic powder or powder mixture, and an upper punch and a lower punch operatively coupled to the die, each of the upper punch and the lower punch having an outer wall defining a diameter smaller than the diameter of the inner wall of the die, thereby defining a gap between each of the upper punch and the lower punch and the inner wall of the die when at least one of the upper punch and the lower punch moves within the internal volume of the die, the gap being 10 μm to 100 μm wide. Preferably, the die and punch are made of graphite. Such SPS tools are disclosed in U.S. Provisional Patent Application No. 63 / 087,204, filed October 3, 2020, and U.S. Provisional Patent Application No. 63 / 124,547, filed December 11, 2020, both of which are incorporated herein by reference.

[0346] In an embodiment, three or more powder mixtures may be placed within the graphite die. A vacuum condition, as known to those skilled in the art, is established within the ceramic powder or powder mixtures placed within the internal volume. Exemplary vacuum conditions include 10 -2 ~10 -3The pressure may be as high as 1000 torr. A vacuum is applied primarily to remove the air to protect the graphite from burning and to remove most of the air from the powder. The order of placement of the powder mixtures may be reversed or repeated as necessary to achieve the desired structure of the multi-layer sintered ceramic body and components formed therefrom. In a preferred embodiment, the second powder mixture is placed between the first powder and the third powder, such that the second powder mixture is adjacent to each of the first and third powder mixtures when placed in the graphite die during sintering. The at least one first, second and third powder layer is then sintered to form the first, second and third layers, whereby the first and second layers are adjacent, thereby forming the non-linear interface 104 of the multi-layer sintered ceramic body, and the second and third layers are adjacent, thereby forming the second interface 105. Placing at least one of the first and second powder mixtures in the volume defined by the tool set typically results in intermixing of the first fired powder mixture with the second powder mixture, thereby creating the aforementioned tortuosity of the nonlinear interface 104 that is characteristic of the multilayer sintered body produced by the method disclosed herein. This nonlinear interface 104 can provide an interlocking effect and improved adhesion between at least one of the first and second layers. Intermixing also occurs between at least one of the second and third powder mixtures, thereby creating a second interface 105. This second interface 105 can provide an interlocking effect and improved toughness between at least one of the second and third layers. The nonlinear interface 104 and the second interface 105 are significantly different from those of laminates and sintered bodies formed from at least one laminate or pre-sintered body having a substantially linear (or one-dimensional) interface, and thus the multilayer sintered ceramic body disclosed herein is not a laminate or laminate. The at least first, second and third powder mixtures may be directly loaded into a sintering apparatus tool set and sintered without a pre-sintering step, such as the use of binders, dispersants, etc., which may contribute to contamination and reduced density.

[0347] The disclosed process utilizes commercially available starting powders having a micron-sized average (or d50) particle size distribution or those prepared from chemical synthesis techniques without the need to form or machine a green tape or body prior to sintering.

[0348] The high density and low porosity associated with the multilayer sintered ceramic body resulting from the disclosed process and powder materials is achieved without the use of binders or sintering aids in the initial powder. Other sintering techniques require the use of sintering aids to reduce sintering temperatures, which can adversely affect halogen-based plasma resistance and densification. Polymer binders are also often used to make the aforementioned green bodies, which can contribute to residual porosity and lower density upon binder burnout. Binders or sintering aids are not required in the fabrication of the multilayer sintered corrosion-resistant ceramic body disclosed herein or the multilayer components formed therefrom. The combination of CTE matching of the respective layers and pressure-assisted sintering is favorable for forming a multilayer sintered ceramic body having the properties as disclosed herein, including high density and high bond strength between layers.

[0349] Step f) of the method disclosed herein includes applying pressure to the layers of the first, second and third fired powder mixture while heating to a sintering temperature to form a multi-layer sintered ceramic body, where at least one layer of the first powder mixture forms at least one first layer, at least one layer of the second powder mixture forms at least one second layer and at least one layer of the third powder mixture forms at least one third layer, and f) reducing the temperature of the multi-layer sintered ceramic body.

[0350] After at least one of the first, second and third powder mixtures is placed in the inner volume of the die, pressure is applied axially to the powder mixture placed between the graphite punches, the pressure is increased until it reaches 5 MPa to 100 MPa, preferably 5 MPa to 60 MPa, preferably 5 MPa to less than 40 MPa, preferably 5 MPa to 20 MPa, preferably 5 MPa to 15 MPa, preferably 10 MPa to 60 MPa, preferably 10 MPa to 40 MPa, preferably 10 MPa to 30 MPa, preferably 10 MPa to 20 MPa, preferably 15 MPa to 60 MPa, preferably 15 MPa to 40 MPa, preferably 15 MPa to 30 MPa, preferably 20 MPa to 40 MPa, preferably 15 MPa to 20 MPa, preferably 13 MPa to 18 MPa.

[0351] By applying heat to the powder mixture prepared in the inner volume of the die, a sintering temperature of 1000-1700°C, preferably 1200-1700°C, preferably 1400-1700°C, preferably 1500-1700°C, preferably 1600-1700°C, preferably 1200-1600°C, preferably 1200-1400°C, preferably 1400-1600°C, preferably 1500-1650°C is facilitated. Sintering may typically be performed for a time period of 0.5-180 minutes, preferably 0.5-120 minutes, preferably 0.5-100 minutes, preferably 0.5-80 minutes, preferably 0.5-60 minutes, preferably 0.5-40 minutes, preferably 0.5-20 minutes, preferably 0.5-10 minutes, preferably 0.5-5 minutes, preferably 5-120 minutes, preferably 10-120 minutes, preferably 20-120 minutes, preferably 40-120 minutes, preferably 60-120 minutes, preferably 80-100 minutes, preferably 100-120 minutes, preferably 30-90 minutes. In certain embodiments, sintering may be performed without an isothermal time, and once the sintering temperature is reached, cooling is initiated at a rate disclosed herein. According to step g) of the process, the sintered ceramic body may be passively cooled by removal of the heat source. Natural or forced convection may be used until a temperature is reached that readily permits the optional annealing process.

[0352] In a preferred embodiment, the powder mixture is directly heated by the punch and die of the sintering apparatus. The die may be constructed of a conductive material such as graphite to facilitate resistive / joule heating. Sintering apparatus and procedures are disclosed in U.S. Patent Application Publication No. 2010 / 0156008(A1), which is incorporated herein by reference.

[0353] Sintering the powder layers under pressure forms a single co-compressed multi-layer body. According to the disclosed method, at least one layer of the first powder mixture, at least one layer of the second powder mixture, and at least one layer of the third powder mixture are simultaneously formed in-situ into the first, second, and third layers of the multi-layer sintered ceramic body, respectively, during step f) of the method. This single-step, simultaneous sintering of at least one of the first, second, and third fired powder mixtures into at least one of the first, second, and third layers of the multi-layer sintered ceramic body can provide enhanced adhesion, high mechanical strength, and improved flatness of the multi-layer sintered ceramic body. The CTE matching of the at least one first layer 100, the at least one second layer 102, and the at least one third layer 103, particularly over the range of sintering temperatures disclosed herein, prevents the generation of stresses due to CTE mismatch at the interfaces between the at least one second layer 102, the at least one first layer 100, and the at least one third layer 103 during cooling after sintering and during any thermal excursions according to the disclosed methods, thus enabling the formation of large sized multilayer sintered ceramic bodies (and components formed therefrom) having high strength, plasma resistance, and high interfacial adhesion.

[0354] During sintering, a volume reduction typically occurs, so that the sintered ceramic body may have a volume that is approximately one-third the volume of the starting powder mixture when placed into the sintering apparatus tool set.

[0355] The temperature of the sintering machine according to the present disclosure is usually measured in the graphite die of the machine, preferably as close as possible to the powder mixture being processed, so that the temperature indicated is actually realized in the powder mixture being sintered.

[0356] The order of application of pressure and temperature may vary as disclosed herein. In one embodiment, the indicated pressure may be applied, then heat may be applied to achieve the desired sintering temperature. In another embodiment, heat may be applied to achieve the desired sintering temperature, then the indicated pressure may be applied. In a further embodiment, the temperature and pressure may be applied simultaneously to the powder mixture to be sintered and ramped up until the indicated value is reached.

[0357] The disclosed method may include a pre-sintering step having a specific heating ramp of 1-100°C / min, preferably 2-50°C / min, preferably 3-25°C / min, preferably 3-10°C / min, more preferably 5-10°C / min, until a specific pre-sintering time is reached.

[0358] The disclosed method may include a pre-sintering step having a specific pressure gradient of 0.50 MPa / min to 30 MPa / min, preferably 0.75 MPa / min to 10 MPa / min, more preferably 1 to 5 MPa / min, until a specific pre-sintering time is reached.

[0359] The methods disclosed herein may include a pre-sintering step having a specific heating gradient as described above and a specific pressure gradient as described above.

[0360] In the pre-sintering step, the temperature and pressure are maintained for a period of 10 minutes to 360 minutes.

[0361] Induction or radiant heating methods can also be used to heat the sintering apparatus to indirectly heat the powder in the toolset.

[0362] Step h) of the method disclosed herein includes optionally annealing the multi-layer sintered ceramic body (or a component formed therefrom) by applying heat to raise the temperature of the multi-layer sintered ceramic body to an annealing temperature at which annealing is performed, and i) lowering the temperature of the annealed multi-layer sintered ceramic body (or a component formed therefrom). In some embodiments, the method disclosed herein may further include an optional annealing step. In the optional annealing step according to embodiments disclosed herein, the multi-layer sintered ceramic body may be removed from the sintering apparatus and subjected to an annealing procedure by annealing in a furnace at a temperature of about 900 to about 1800°C, preferably about 1250 to about 1700°C, preferably about 1300 to about 1650°C, preferably about 1400 to about 1600°C.

[0363] In an embodiment, the optional annealing of the multilayer sintered ceramic body may be carried out at a heating and / or cooling rate of 0.5°C / min to 50°C / min, preferably 0.5°C / min to 25°C / min, more preferably 0.5°C / min to 10°C / min, more preferably 0.5°C / min to 5°C / min, more preferably 1°C / min to 50°C / min, more preferably 3°C / min to 50°C / min, more preferably 5°C / min to 50°C / min, more preferably 25°C / min to 50°C / min, preferably 1°C / min to 10°C / min, preferably 2°C / min to 10°C / min, preferably 2°C / min to 5°C / min.

[0364] The duration of the optional annealing step may be from 1 to 24 hours, preferably from 1 to 18 hours, preferably from 1 to 16 hours, preferably from 1 to 8 hours, preferably from 4 to 24 hours, preferably from 8 to 24 hours, preferably from 12 to 24 hours, preferably from 4 to 12 hours, preferably from 6 to 10 hours.

[0365] In one embodiment, the optional annealing according to the present disclosure may be carried out in a sintering apparatus after the sintering process. The optional annealing process may be preferably carried out under oxidizing conditions such as forced convection or in air. The annealing results in improved chemical and physical properties of the multi-layer sintered ceramic body or parts made therefrom through reduction of oxygen vacancies for stoichiometric correction and reduction of stress in the sintered body or part. The optional process step of annealing the sintered multi-layer corrosion-resistant component is carried out in an oxidizing atmosphere, whereby the annealing process may provide increased albedo, improved mechanical handling and reduced porosity.

[0366] In some embodiments, the annealing step may be performed by conventional methods used for annealing glasses, ceramics, and metals, and the degree of refinement may be selected by the annealing temp...

Claims

1. A multilayer sintered ceramic body, comprising: At least one first layer comprising polycrystalline YAG (yttrium aluminum garnet), the at least one first layer comprising polycrystalline YAG comprising pores, the pores having a maximum size of 0.1 to 5 μm; at least one second layer comprising alumina and zirconia, the zirconia comprising at least one of stabilized zirconia and partially stabilized zirconia; at least one third layer comprising YAG, alumina and zirconia; Equipped with the at least one second layer is disposed between the at least one first layer and the at least one third layer; The absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first and second layer is between 0 and 0.75×10 as measured in accordance with ASTM E228-17. -6 / °C, the at least one first, second and third layers form a single sintered ceramic body; the at least one first layer comprises polycrystalline YAG in an amount of 90-99.9% by volume; The at least one second layer comprises alumina in an amount of 70-95 volume percent, and at least one of stabilized zirconia and partially stabilized zirconia in an amount of 5-30 volume percent.

2. 2. The multilayer sintered ceramic body of claim 1, wherein the absolute value of the difference in thermal expansion coefficient between the at least one first and second layer is 0 to 0.7×10 −6 / ° C.

3. 10. The multi-layer sintered ceramic body of claim 1, wherein an absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first and second layer is maintained over a temperature range of 200-1400°C.

4. The multi-layer sintered ceramic body of any one of claims 1 to 3, wherein the at least one first layer has a density of 4.47 to 4.56 g / cc as measured in accordance with ASTM B962-17.

5. The multilayer sintered ceramic body according to any one of claims 1 to 3, wherein the at least one first layer has a Sa of 0.0005 to 2 μm, measured according to ISO standard 25178-2-2012, or a Sz of 0.3 to 5 μm, measured according to ISO standard 25178-2-2012.

6. 4. The multilayer sintered ceramic body according to claim 1, wherein the at least one second layer comprises alumina in an amount of 70 to 90 volume % and at least one of stabilized zirconia and partially stabilized zirconia in an amount of 10 to 30 volume %, based on the volume of the at least one second layer.

7. The multi-layer sintered ceramic body of any one of claims 1 to 3, wherein the at least one second layer comprises partially stabilized zirconia.

8. The multilayer sintered ceramic body according to any one of claims 1 to 3, having a maximum dimension of 100 to 625 mm.

9. 4. The multilayer sintered ceramic body according to claim 1, wherein the at least one second layer comprises alumina in an amount of 80 to 95 volume % and at least one of stabilized zirconia and partially stabilized zirconia in an amount of 5 to 20 volume %, based on the volume of the at least one second layer.

10. 4. The multilayer sintered ceramic body according to claim 1, wherein the at least one first layer is comprised of polycrystalline YAG in an amount of 98-99.9% by volume, as measured using XRD (X-ray diffraction), SEM (scanning electron microscope) and image processing methods, and the remainder comprising impurities and at least one crystalline phase selected from the group consisting of aluminum oxide, yttrium oxide, YAM (yttrium aluminum monoclinic) and YAP (yttrium aluminum perovskite) and combinations thereof.

11. 4. The multilayer sintered ceramic body according to claim 1, wherein the at least one first layer comprising polycrystalline YAG comprises pores, the pores having a maximum size of 0.1 to 1 μm as measured using a SEM (scanning electron microscope).

12. The at least one first layer comprising polycrystalline YAG has a thickness of 2 to 800 μm as measured using a SEM (scanning electron microscope). 2 / mm 2 The multilayer sintered ceramic body according to any one of claims 1 to 3, having a cumulative pore size distribution of:

13. 4. The multilayer sintered ceramic body according to claim 1, wherein the at least one first layer comprising polycrystalline YAG has a porosity by surface area percentage of 0.0005 to 2% as measured using SEM (scanning electron microscope).

14. 4. The multilayer sintered ceramic body according to claim 1, wherein the at least one first layer comprising polycrystalline YAG has a total impurity content of 5 to less than 50 ppm by weight of the at least one first layer, as measured using ICP-MS (Inductively Coupled Plasma Mass Spectroscopy).

15. The multi-layer sintered ceramic body of any one of claims 1 to 3, wherein the at least one second layer has a density of 4.19 to 4.46 g / cc as measured in accordance with ASTM B962-17.

16. 4. The multilayer sintered ceramic body of claim 1, wherein the at least one second layer is comprised of at least one of stabilized zirconia and partially stabilized zirconia in an amount of 16 volume percent, impurities, and the balance alumina, and has a density of 4.31 to 4.33 g / cc as measured in accordance with ASTM B962-17.

17. The at least one second layer has a thermal resistance of 6.98×10 over a temperature range of 200° C. to 1400° C. as measured according to ASTM E228-17. -6 / ℃~9.26×10 -6 17. The multilayer sintered ceramic body of claim 16 having a coefficient of thermal expansion (CTE) of 1 / °C.

18. The at least one second layer has a thermal conductivity of 7×10 at a frequency of 1 MHz at ambient temperature as measured according to ASTM D150. -4 17. The multilayer sintered ceramic body of claim 16, having a dielectric loss of:

19. 4. The multilayer sintered ceramic body according to claim 1, wherein the at least one second layer has a total impurity content of 5 to 200 ppm based on the mass of the at least one second layer, measured using ICP-MS method (Inductively Coupled Plasma Mass Spectroscopy).

20. 4. The multilayer sintered ceramic body according to claim 1, wherein the at least one first layer has a thickness d1, the at least one second layer has a thickness d2, and the at least one third layer has a thickness d3, and the thickness d2 of the at least one second layer is 60% to 85% of the combined thickness of the at least one first, second and third layer.

21. 1. A method for making a multi-layer sintered ceramic body, the method comprising: a. combining powders comprising yttria and alumina to form a first powder mixture; b. combining an alumina powder with at least one of a partially stabilized zirconia powder and a stabilized zirconia powder to form a second powder mixture; c) combining an alumina powder, an yttria powder, and at least one of an unstabilized zirconia, a partially stabilized zirconia, and a stabilized zirconia powder to form at least one third powder mixture; d. firing at least one of the first, second, and third powder mixtures by applying heat to raise the temperature of at least one of the powder mixtures to a firing temperature and maintaining the firing temperature to form at least one first, second, and third fired powder mixture; e. separately disposing the first, second and third powder mixtures within an internal volume defined by a toolset of a sintering machine to form at least one layer of the first powder mixture, at least one layer of the second powder mixture and at least one layer of the third powder mixture and creating a vacuum condition within the internal volume, the toolset comprising a die including a sidewall including an inner wall and an outer wall, and upper and lower punches operatively coupled to the die, the inner wall having a diameter defining the internal volume capable of receiving the powder, each of the upper and lower punches having an outer wall defining a diameter smaller than a diameter of the inner wall of the die, thereby defining a gap between each of the upper and lower punches and the inner wall of the die as at least one of the upper and lower punches moves within the internal volume of the die, the gap being between 10 μm and 100 μm in width; f. applying pressure to the layers of the first, second and third powder mixtures while heating to a sintering temperature and sintering to form a multi-layer sintered ceramic body, wherein the at least one layer of the first powder mixture forms at least one first layer, the at least one layer of the second powder mixture forms at least one second layer, and the at least one layer of the third powder mixture forms at least one third layer; g. Reducing the temperature of the multilayer sintered ceramic body, the at least one first layer comprises polycrystalline YAG (yttrium aluminum garnet), the at least one second layer comprises alumina and zirconia, the zirconia comprising at least one of stabilized zirconia and partially stabilized zirconia, the at least one third layer comprises YAG, alumina, and at least one of unstabilized zirconia, stabilized zirconia, and partially stabilized zirconia, the at least one second layer being disposed between the at least one first layer and the at least one third layer; the absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first and second layer is 0 to 0.75×10 −6 / ° C. as measured according to ASTM E228-17; the at least one first layer comprises polycrystalline YAG in an amount of 90-99.9% by volume; The method wherein the at least one second layer comprises alumina in an amount of 70-95 volume percent, and at least one of stabilized zirconia and partially stabilized zirconia in an amount of 5-30 volume percent.

22. 22. The method of claim 21, wherein the first, second and third powder mixtures have a combined total impurity content of 200 ppm or less as measured using ICP-MS (Inductively Coupled Plasma Mass Spectroscopy).

23. 23. The method of claim 21 or 22, wherein the second powder mixture comprises partially stabilized zirconia or stabilized zirconia in an amount of 15% to 34% by weight, based on the weight of the second powder mixture.

24. 23. The method of claim 21 or 22, wherein the first, second and third powder mixtures are crystalline as determined by X-ray diffraction methods.

25. 23. The method of claim 21 or 22, wherein the second powder mixture comprises partially stabilized zirconia.

26. 23. The method of claim 21 or 22, wherein the second powder mixture comprises partially yttria stabilized zirconia.

27. 23. The method of claim 21 or 22, wherein the second powder mixture comprises 3 mole percent partially yttria stabilized zirconia.

28. 23. The method of claim 21 or 22, wherein the pressure applied to the first, second and third layers of powder mixture is between 5 MPa and 100 MPa.

29. The method according to claim 21 or 22, wherein the temperature of the calcination step is from 600°C to 1200°C.

30. The method according to claim 21 or 22, wherein the sintering temperature is from 1000 to 1700°C.

31. h) annealing the multi-layer sintered ceramic body by applying heat to raise the temperature of the multi-layer sintered ceramic body until an annealing temperature is reached; i. reducing the temperature of the annealed multi-layer sintered ceramic body; 23. The method of claim 21 or 22, further comprising:

32. 23. The method of claim 21 or 22, further comprising machining the multi-layer sintered ceramic body to produce a multi-layer sintered ceramic component in the shape of a window, a lid, a dielectric window, an RF window, a ring, a focus ring, a process ring, a deposition ring, a nozzle, an injector, a gas injector, a showerhead, a gas distribution plate, a diffuser, an ion suppressor element, a chuck, an electrostatic wafer chuck (ESC), and a puck for use in a plasma processing chamber.

Citation Information

Patent Citations

  • Corrosion resistant member

    JP2002080270A

  • Safety cover

    JP2002356837A

  • Multilayer body having yttria - alumina compound oxide film, yttria - alumina compound oxide film, corrosion- resistant member, corrosion-resistant film and method for manufacturing yttria - alumina compound oxide film

    JP2003277051A

  • Composite sintered compact and its manufacturing method

    JP2004217478A

  • Corrosion-resistant components and manufacturing methods

    JP2019504470A